Anthropogenic microparticles across intertidal, shallow and mesophotic reef sediments in the Southwestern Atlantic - Yasmin Barros; Marcelo O. Soares; Alejandro P. Ayala; Vasco S. Neto; Jessica Reichert; Ítalo B. Castro; Tommaso Giarrizzo; Rivelino M. Cavalcante (Marine Pollution Bulletin, 2026)

Collaborative science narrows knowledge gaps in marine biological invasions to advance a national framework - Romeu S. Ribeiro; Cristina Espírito Santo; Susana Celestino; Marta Mamede; João J. Castro; Teresa Cruz; Teresa Silva; David Jacinto; Cátia Bartilotti; Jorge Lobo-Arteaga; Miriam Tuaty-Guerra; João Canning-Clode; et al. (Marine Pollution Bulletin, 2026)

Intrafollicular hormonal environment of equine follicles aspirated for In Vitro Embryo production - K. Malin; A. de la Fuente; S. Meyers; K. Takahashi; S. Martin-Pelaez; C. Renaudin; G. Dujovne; B. Heil; T. de Castro; A.J. Conley; P. Dini (Journal of Equine Veterinary Science, 2026)

The ocean as a laboratory for animal intelligence - Maria Castro Mariano; Francisco Louro; Patrícia Pinto; João Grave; Victor Callais; Nicolas Collazo; Beatriz Pereira; Daniel Gouveia; Lisandra Tavares; Luís Almeida; Raúl Oliveira; Ana S. Carmo; et al. (acta ethologica, 2026)

Kogia Records in Brazilian Equatorial and Southwestern Atlantic Oceans - Joao Pedro M. Mura; Raphael B. Machado; Yasmin P. Viana; Natalia Rodrigues‐Soares; Giovanne A. Ferreira; Larissa Kelmer L. Kascher; Barbara S. Silva; Lucia O. Alencar; Gabrieli M. Rodrigues; Franciele R. de Castro; Daniela F. Godoy; Jose L. Pizzorno; et al. (Marine Mammal Science, 2026)
The pygmy ( Kogia breviceps ) and dwarf ( Kogia sima ) sperm whales are cryptic cetaceans characterized by inconspicuous surfacing behavior, small group sizes, and deep‐diving habits, making visual detection particularly challenging. Here, we present the first broad‐scale passive acoustic monitoring (PAM) assessment of Kogia spp. occurrence along the Brazilian coast, spanning both the Equatorial Atlantic Ocean (EAO) and Southwestern Atlantic Ocean (SWAO). Across 25 survey campaigns, 504 survey days, and more than 6441 h of acoustic recordings, 94 acoustic detections were identified, predominantly within the Brazilian Equatorial Margin (BEM), resulting in substantially higher detection‐per‐unit‐effort values in the EAO than in the SWAO. Two rare visual‐acoustic encounters of Kogia sima were also documented, including one detection incorporated into the dataset. A total of 2796 echolocation clicks were analyzed, exhibiting the characteristic narrow‐band high‐frequency acoustic profile of Kogia spp. (mean peak frequency = 126.2 ± 3.8 kHz; mean −3 dB bandwidth = 4.7 ± 2.56 kHz; mean inter‐click interval = 141 ± 97 ms). Detections occurred across a broad bathymetric range (9–4411 m), and kernel density analyses revealed spatial heterogeneity in occurrence patterns, with recurrent detection areas concentrated within the BEM. Collectively, these findings demonstrate the effectiveness of PAM for studying elusive deep‐diving cetaceans and provide an important baseline for future ecological monitoring, impact assessment, and conservation efforts targeting Kogia spp. in the western Atlantic.

Integrating cytotoxicity and NMR-based metabolomics to uncover bioactive aporphine alkaloids and pentacyclic triterpenoids from Siparuna guianensis - Salva Asghar; Cibele A. Cesila; Gracimerio J. Guarneire; Samira C. C. Ludgero; Sandra B. R. Castro; Alessandra P. Carli; Caio César S. Alves; Danielle F. Dias; Marisi G. Soares; Nerilson M. Lima (Natural Product Research, 2026)

Evaluation of water quality from tubular wells in Brazil - G. G. O. de Souza; J. W. G. Castro; R. S. da Cadorso; E. M. de Lima; J. F. L. de Pereira; M. P. da Silva; Y. T. C. da Santos; F. G. Rodriguês; J. G. M. da Costa; H. D. M. Coutinho; G. B. Brito (International Journal of Energy and Water Resources, 2026)

Calibration and validation of the safer evapotranspiration model using Landsat 8 and eddy covariance data in vineyards - Anderson L. S. Safre; Alfonso Torres-Rua; Joao Carlos Cury Saad; Antônio Heriberto de Castro Teixeira (Irrigation Science, 2026)
Accurate estimates of actual evapotranspiration (ET a ) are essential for irrigation management in vineyards. This study locally calibrated and validated the Simple Algorithm for Evapotranspiration Retrieving (SAFER) model for California vineyard systems using Landsat 8 imagery and multi-year eddy covariance (EC) measurements collected between 2013 and 2016 in the Central Valley of California. Two calibration approaches were implemented: k-fold cross-validation and a split-sample (two-year) strategy. SAFER performance was evaluated using both closed and unclosed energy balance EC fluxes to assess the influence of energy balance closure on model calibration and validation. Energy balance closure ratios ranged from 0.67 to 0.95, with moderate interannual variability and lower closure observed during some periods. Local calibration of SAFER resulted in regression coefficients that differed substantially from the original parametrization. Compared to the original coefficients, root mean square error (RMSE) was reduced by approximately 71–77%, with values below 0.70 mm d − 1 for both calibration approaches. Model validation showed strong agreement between SAFER ET a and EC observations after calibration. RMSE ranged from 0.57 to 0.71 mm d − 1 and mean absolute error (MAE) ranged from 0.46 to 0.55 mm d − 1 . Overall, the results indicate that SAFER provides reliable estimates of daily vineyard ET a when locally calibrated, supporting its application for field-scale irrigation management in perennial cropping systems.

Enhanced efficacy of carvacrol and thymol in combination with benzalkonium chloride for the control of the cattle tick Rhipicephalus microplus - Caio P. Tavares; Glayane de Jesus S. Castro; Lívio M. Costa-Junior; Alexandra Martins dos S. Soares (Veterinary Parasitology, 2026)

Screening of cutaneous secretions from Leptodactylus vastus Lutz, 1930 (Anura: Leptodactylidae): identification of bioactive proteins and anticoagulant activity - Tulíbia Laurindo Silva; Géssica Gomes Barbosa; Pollyanna Michelle da Silva; Thiago Lucas da Silva Lira; Carlos José Correia de Santana; Patrícia Maria Guedes Paiva; Ana Patrícia Silva de Oliveira; Thâmarah de Albuquerque Lima; Romero Marcos Pedrosa Brandão Costa; Mariana S. Castro; Thiago Henrique Napoleão (Toxicon, 2026)

Bioactive properties of paraprobiotics and modelling their antilisterial activity in a miniature laboratory model of white cheese over refrigerated storage - Mahmoud Yolmeh; Fakhreddin Salehi; Yuri Matheus Silva Amaral; Ruann Janser Soares de Castro; Anderson S. Sant’Ana (Food Bioscience, 2026)

Microplastic in bivalves from the heavily contaminated Guanabara Bay, Rio de Janeiro, Brazil - Victor Vasques Ribeiro; Yonara Garcia; Caio César Achiles do Prado; Amanda Pereira Santos; Raimara S. Gomes; Andreia N. Fernandes; Ítalo Braga Castro (Environmental Research, 2026)

Rethinking expertise on climate cooling technologies - María Inés Carabajal; Aylén Bavosa Castro; Edson Bezerra; Eduarda Calado Barbosa; Camillo Fiore; Gian Franco Lisanti; Guillermo Marín Penella; Julieta Nasi; Gabriela Raggio; Julia S. Guivant; Sophie Haines; Thomas Douglas; et al. (Environmental Science & Policy, 2026)

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

First records of spinturnicid mites (Mesostigmata: Spinturnicidae) in Tocantins State, Brazil - Luís Fernando da Cruz; Letícia de Biasi; Liege R. Siqueira; Ana Beatriz Pais Borsoi; Ingrid Benevides Machado; Ademar Ferreira da Silva; Marinete Amorim; Gilberto S. Gazêta; Fernando de Castro Jacinavicius; Darci Moraes Barros-Battesti; Ricardo Bassini-Silva (Biologia, 2026)

Optimization of wastewater treatment plant considering the uncertainty of treatment process effectiveness - Jannsen Arnier P. Friala; Ashlee Julienne I. Sigua; Francis Dominic S. Escalona; Adriane Paul C. Castro; Jeremy Gabriel Uy; Jayne Lois San Juan (Environmental Modelling & Software, 2026)

Optimising realised genetic gain with low forward predictive ability across cycles for cooking time and correlated traits in common bean based on multivariate genomic selection - Renu Saradadevi; Winnyfred Amongi; Clare Mukankusi; Allan S. Male; Jean-Claude Rubyogo; Eric Huttner; Felipe A. Castro-Urrea; Li Li; Kadambot H. M. Siddique; Wallace A. Cowling (Theoretical and Applied Genetics, 2026)
Key message Rapid genetic gain was achieved for cooking time in common bean based on multivariate genomic analysis, but forward predictive ability was low and phenotyping remains essential to secure genetic gain. Abstract Common beans ( Phaseolus vulgaris L.) are a major source of protein and energy in sub-Saharan Africa, but their long cooking time (CKT) imposes social, economic, environmental and health burdens. This study aimed to accelerate genetic gain for shorter CKT while maintaining or improving other seed traits such as seed iron (Fe) and zinc (Zn) content, water absorption capacity (WAC) and 100-seed weight (SW100) across rapid cycles of early-generation genomic selection. Two related founder populations were selected from the African bean panel and intercrossed in 2020 (population A) and 2021 (population B), followed by rapid two-year cycles of augmented S 0 -derived family selection based on an index and optimal contributions selection. Best linear unbiased predictions (BLUPs) of breeding values were obtained from pedigree (ABLUP), genomic (GBLUP) and single-step (HBLUP) multivariate linear mixed model analysis across two cycles. Realised genetic gain from cycle 1 to cycle 2 was high for CKT (average -8.0 min y −1 ) and favourably correlated with WAC (average + 7.7% y −1 ), but detrimental genetic correlations limited gain in Fe, Zn and SW100. Genomic and single-step models resulted in high accuracy of BLUPs based on prediction error variance. Forward predictive ability for CKT across cycles was low, but rank correlation of realised and predicted HBLUPs for CKT in cycle 2B S 0 seedlings was moderate-high (0.734) when phenotypes for Fe, Zn, WAC and SW100 in cycle 2B were included in the analysis. Desired genetic gains in CKT, Fe and Zn in future cycles will require high levels of phenotyping in each cycle, although easy-to-measure correlated traits such as WAC and SW100 may assist genetic gain in all traits.

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

A bromoform-based Investigational Veterinary Product reduced methane emissions and increased feed conversion efficiency of yearling steers when delivered via drinking water - W.L. de Souza; S.P. Quigley; A.L. Bates; R.J. Batley; M.A.O. Castro; J.M. Gasparina; O. Gillies; P. Guerreiro; P.S. Alvarez-Hess; M.J. Auldist; S. Jacques; R. Tognelli; et al. (Animal Feed Science and Technology, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Petasma as a Reliable External Indicator of Male Sexual Maturity in Penaeus schmitti : Integrating Morphological, Biometric and Histological Analyses - H. Castro‐Neto; C. Craveiro; M. G. do Rêgo; P. G. V. Oliveira; R. Soares; S. Peixoto (Fisheries Management and Ecology, 2026)
Understanding male sexual maturity in penaeid shrimp is crucial for stock assessment and size‐based management; however, maturity criteria remain heavily biased toward females and rarely validated for males. This study evaluated whether petasma fusion is a reliable external indicator of male sexual maturity in white shrimp Penaeus schmitti from Northeast Brazil and estimated size at first maturation using an integrative morphometric, histological, and statistical approach. Forty‐five males were classified according to petasma condition, morphometrically measured, histologically examined along the reproductive tract, and analyzed using individual‐level binomial logistic regression. The estimated cephalothorax length at first maturation was CL 50 = 2.24 cm (95% CI: 2.06–2.43), with a strong model performance (Nagelkerke R 2 = 0.80). Histological analysis revealed complete categorical agreement between external morphology and internal reproductive status: all males with unfused petasma lacked mature spermatozoa and exhibited only early germ cells, whereas all males with fused petasma presented the complete spermatogenic series and fully differentiated spermatozoa in the terminal ampulla. The relationship between petasma length and body size showed negative allometry, indicating a proportionally smaller investment in petasma growth relative to somatic growth. ANCOVA detected a significant maturity effect on the intercept, but not on the slope, demonstrating a discrete proportional change in petasma dimensions at maturation, rather than a change in growth trajectory. These findings demonstrate that petasma fusion is a robust and nondestructive indicator of physiological maturity in male P. schmitti . The results of the analysis combining petasma, histology, and length at first maturity indicated that petasma is a reliable indicator for validating physiological maturity and that male reproductive indicators should be formally incorporated into penaeid fishery management structures.

Non‐Stationary Dry‐Spell Hazard Probabilities for Spain - S. M. Vicente‐Serrano; S. Beguería; A. Royo; A. El Kenawy; M. Franquesa; A. Halifa‐Marin; M. Adell‐Michavila; A. Crespillo; D. Pérez‐Pajuelo; F. Domínguez‐Castro; C. Azorin‐Molina; L. Gimeno; et al. (International Journal of Climatology, 2026)
This study provides a comprehensive assessment of long‐term changes in dry‐spell dynamics across Spain for the period 1961–2024, using both classical non‐parametric methods and a novel non‐stationary probabilistic framework applied to exceedance series of dry‐spell durations. Using daily precipitation data from a dense network of quality‐controlled stations, dry‐spells were identified based on four thresholds (0.1, 1, 5, and 10 mm) to characterize their duration statistics, and generalized Pareto distributions (GPDs) were fitted under both stationary and non‐stationary specifications. A systematic percentile‐based evaluation was performed to determine optimal exceedance thresholds, and a bootstrap‐based significance test was applied to compare stationary and non‐stationary return levels. Complementary analyses examined trends in annual frequency, mean duration, and maximum dry‐spell length. Results consistently reveal that dry‐spell behaviour across Spain is dominantly stationary. Only a very small fraction of stations show significant non‐stationary effects in the GPD location parameter, whereas non‐stationary scale, shape, or full‐parameter models provide no robust improvement and introduce substantial uncertainty. Traditional trend analyses corroborate this finding: most stations (> 70%–85%, depending on threshold) exhibit no statistically significant changes in dry‐spell frequency, mean duration, or maximum duration. Spatial patterns of change are weak, and return levels associated with long recurrence periods (e.g., 50 years) remain highly stable throughout 1961–2024. Overall, these results support long‐term stationarity in the probability of extreme dry‐spells across Spain.

Cystic endometrial hyperplasia in dairy goats: morphological changes and expressions of estrogen receptor-α and progesterone receptor - Agustín Avellaneda-Cáceres; Laura S. Aguirre; Gabriela V. Sandoval; Diego M. Medina; Ana L. Quintana; Francisco Acuña; Gimena Gomez Castro; Claudio G. Barbeito; Juan F. Micheloud (Research in Veterinary Science, 2026)

New findings on the performance of anaerobic reactors: Ecotoxicological assessment of sublethal effects of antibiotic mixtures in wastewater on freshwater invertebrates - Gleyson B. Castro; Mateus Cottorello-Fonsêca; Tallyson T.C. de Souza; David S. Alexandre; Juliano J. Corbi (Journal of Environmental Chemical Engineering, 2026)

Trees just go “nuts”: prioritizing carbon allocation to yield in almond trees - Shreya S. Veeravelli; Andrew J. McElrone; Ian R. Wright; Mina Momayyezi; Kyle R. Knipper; Nicolas E. Bambach; Sebastian Castro Bustamante; Andrew J. Gal; Sat Darshan S. Khalsa; Ranjith Karunakaran; Hung T. T. Nguyen; Morgan E. Furze (Planta, 2026)
Main conclusion Almond trees prioritize C to yield rather than stem growth, and their overall lower NSC stores compared to forest trees may have consequences for resilience under environmental variability. Abstract Perennial tree crops store nonstructural carbohydrates (NSCs) as energy reserves that can be used to persist during both predictable periods of reduced activity like dormancy and more unpredictable periods associated with stress. For deciduous tree crops, which lose their leaves at the start of dormancy, the NSC reserves accrued by that time are critically important for fueling respiration but may also influence processes in the following growing season. To quantify the seasonal NSC fluctuation surrounding dormancy and its influence on downstream processes like growth and yield, we conducted a comparative study of four almond varieties in a commercial orchard (California, USA). Sugar and starch concentrations were quantified in branch, stem, and coarse root when entering and exiting dormancy. We then assessed the correlation between these NSC data and metrics of stem growth and yield in the following growing season. We further explored long-term trade-offs between stem growth and yield using historical data from 2017 to 2022. Overall, total NSC concentrations significantly decreased during the dormant season in all organs. We observed a significant positive correlation between branch total NSC concentration when entering dormancy and yield the next year. However, we unexpectedly found that stem total NSC concentrations when entering dormancy were negatively correlated with stem growth the next year, suggesting that stem reserves were primarily used to support wintertime respiration or translocated to other organs. A long-term trade-off between stem growth and yield was evident; as yield increased, basal area increment tended to decrease. Additionally, we found whole-tree NSC storage to be lower in almond trees compared to temperate forest trees, reflecting prioritization to yield over NSC storage. Overall, these findings advance our understanding of crop tree carbon physiology and provide insight into the resilience of different almond cultivars under changing environmental conditions.

Is Genista anxantica (Fabaceae, Genisteae) worth of taxonomic recognition? An integrative approach - E. Del Guacchio; R. Vallariello; E. Di Iorio; S. Tomasello; O. De Castro (Plant Biosystems, 2026)
Genista anxantica is an extremophile taxon described by Michele Tenore and strictly endemic to the mephitic fields in Ansanto Valley (Mefite, Rocca San Felice, province of Avellino, Campania region, SW Italy). Its taxonomic distinctness from the widespread G. tinctoria subsp. tinctoria , initially undoubted, has later been long debated. Recent population genetic evidence suggests that the Mefite population represents an ecotype within G. tinctoria , shaped by extreme ecological conditions. In this contribution, we integrate morphological data and ploidy estimation by flow cytometry with ecological and genetic information to reassess its taxonomical status. Our results highlight the distinctness of G. anxantica as a local, genetically established variant adapted to a peculiar ecology. Accordingly, we propose the subspecific rank. The name G. anxantica is typified on a specimen preserved in Tenore’s herbarium (NAP, Botanical Garden of Naples).

The haunting challenge of the trends and pathway assessments on newly introduced non-indigenous species in European seas - Okko Outinen; Peter A.U. Stæhr; Romeu S. Ribeiro; Aina Carbonell; Robert Comas-González; Lydia Png-Gonzalez; Maite Vázquez-Luis; Ann-Britt Florin; Rahmat Naddafi; Arjan Gittenberger; Hans Jakobsen; Ana C. Costa; et al. (Marine Pollution Bulletin, 2026)

Differentiation of Lesueurigobius sanzi and L. suerii through otolith morphometric analysis - Jaime S. Rubiales-Gómez; Jairo Castro-Gutiérrez; Carlos Rodríguez-García; Jesica Sarmiento-Carbajal; Remedios Cabrera-Castro (Estuarine, Coastal and Shelf Science, 2026)

Benthic diatoms and phytoplankton diversity in urban streams and ponds: charting a course for conservation - A. T. Castro-Castellon; M. J. Hill; E. Conroy; A. Daw; H. Gurung; J. S. Hernández-Avilés; S. J. Hobbs; V. H. Salinas-Camarillo; I. Thornhill (Biodiversity and Conservation, 2026)
Benthic diatom and phytoplankton communities are key indicators of freshwater ecosystem health and change but remain understudied. A better understanding of their distribution and abundance drivers is crucial for effective biodiversity assessment and conservation. This study adopts a novel, multi-ecosystem approach to examine the seasonal (2019–2020) diversity of benthic diatom assemblages in urban streams and phytoplankton assemblages in ponds across Bristol (UK) and the local environmental factors shaping these communities. Among ponds, winter recorded significantly fewer phytoplankton taxa than summer and autumn. Among streams, patterns of benthic diatom beta diversity indicated higher turnover in autumn than in winter, and among pond habitats, turnover dominated in the summer and autumn seasons, but nestedness explained more of the composition variation in winter. No significant differences in Local Contributions to Beta Diversity (LCBD) were recorded between seasons for either streams or ponds. However, among streams, LCBD was consistently high at sites with elevated phosphorus, indicating how nutrient enrichment can shape unique assemblages. In streams, nitrate emerged as the principal driver of diatom diversity and composition during the autumn season, whilst, pH, ammonium, zinc, and potassium distinguished diatom communities during the winter. In ponds, pH influenced phytoplankton assemblages in summer, possibly through nutrient and inorganic carbon availability changes. However, no strong environmental–species relationships were identified in autumn or winter, suggesting biotic interactions may be more influential during these seasons. We highlight the need for more comprehensive, long-term monitoring for the inclusion of diatoms and phytoplankton in urban freshwater management and conservation strategies.

Combined Analysis of Gait Cycle and Imaging Parameters in Patients with Lumbar Disc Herniation: An Exploratory Study - Inês F. Mendes; Rita N. S. Fernandes; André P. G. Castro; Nuno A. R. Cristino (Annals of Biomedical Engineering, 2026)
This exploratory study investigates the association between imaging findings, clinical symptoms and gait parameters in patients with lumbar disc herniation (LDH). To explore this hypothesis, this study aims (1) to study how IVD height and intervertebral angle measurements obtained from MRI compare with those obtained from X-ray imaging; (2) to compare spatiotemporal gait parameters between LDH patients and healthy individuals and (3) to study if gait parameters vary in relation to clinical and imaging-derived measurements in LDH patients. Patients in this study underwent lumbar spine X-ray imaging and MRI, completed the Oswestry Disability Index (ODI) and Numerical Pain Rating Scale (NPRS) and participated in a gait analysis assessment. Measurements of IVD height and intervertebral angle revealed unexpected higher values in X-ray scans when compared to MRI, particularly in anterior IVD height and upper lumbar levels, providing important hints for the analysis of the initial imaging exam (usually X-ray scan). In addition, the analyzed gait parameters were altered in most LDH patients, with reduced walking speed, cadence, stride length and single support time and increased double support time, comparatively to healthy controls. A general tendency was found between intense radicular pain and high disability (NPRS and ODI scores, respectively) – both reflecting the impact of the clinical condition – and significant IVD pathology – evident on imaging – and altered gait parameters. However, some cases showed inconsistencies between clinical symptoms, imaging findings and gait parameters, suggesting that the relationship between the mentioned parameters is not always consistent. These findings underscore the importance of a multidimensional approach in evaluating LDH biomechanics, integrating clinical and gait parameters, while identifying potential discrepancies between imaging modalities for better initial assessment and follow-up.

Microplastics in a mosaic of Marine Protected Areas from southeastern Brazil: An assessment based on filter-feeding bivalves - Yonara Garcia; Victor Vasques Ribeiro; Caio César Achiles do Prado; Maria Teresa Castilho Mansor; Alexander Turra; Raimara S. Gomes; Andreia N. Fernandes; Ítalo Braga Castro (Marine Pollution Bulletin, 2026)

Machine learning-assisted integration to evaluate the impact of fruit pre-washing, direct ozone treatment of coconut water, and storage temperature on physicochemical quality, enzymatic and microbiological inactivation - Eugénio da Piedade Edmundo Sitoe; Larissa Pereira Margalho; Patrícia Monteiro Evangelista; Max Suel Alves dos Santos; Wilma Custódio Fumo; Matheus da Silva Mourão; Alanna Vitória Rocha Eliziário; Ruann Janser Soares de Castro; Anderson S. Sant’Ana (Journal of Food Engineering, 2026)

Unleashing the power of connection: How farmers’ emotional connection to soil empowers their soil conservation practices - Alexander Neaman; Jhon Talaverano-Tello; Claudia Navarro-Villarroel; Isidora Naranjo-López; Dmitry S. Ermakov; Mónica Castro (Journal of Environmental Management, 2026)

Detection of Anisakis spp. (Nematoda, Anisakidae) in frozen and processed hake products marketed in Spain - R. González-Soñora; A. Ramilo; R. Ríos-Castro; E. Abollo; S. Pascual (International Journal of Food Microbiology, 2026)

The dynamics of coastal macroalgal assemblages after the Fundão dam disaster: challenges and lessons from impact assessment - Ivan M. Carneiro; Guilherme M. Castro; Fernando C. Cardoso; Julia P. Curvêllo; Rodrigo T. Carvalho; Leonardo T. Salgado; Julia Kaiser; Paulo S. Salomon; Rodrigo L. Moura (Environmental Monitoring and Assessment, 2026)
Anthropogenic marine disasters impair biodiversity, ecosystem services provisioning, and socioeconomic development, with long-lasting consequences. Robust impact assessment, however, depends on understanding the spatiotemporal variability of the indicators used to detect change. Here, we present the results of a monitoring program (2018–2025) targeted at two Coastal and Marine Protected Areas located 40 km south of the Doce River mouth (Eastern Brazil), which were affected by the discharge of iron ore tailings from the Fundão dam collapse in 2015. Besides assessing the dynamics of the benthic assemblages, we revealed a high variability among sampling units (residual), along with relevant variability across seasons, sites, and their interactions. Wave height and distance from rivers were the most influential drivers explaining assemblage variability. Before–after contrasts based on pre-disaster data from the literature indicate shifts in the assemblage structure. However, because baseline data are limited, the observed changes cannot be conclusively attributed to the disaster. An overview of marine areas under long-term ecological monitoring in Brazil revealed a concerning mismatch with the distribution of mining, oil and gas, port, and nuclear activities. Rethinking funding for baseline data collection and monitoring of disaster-prone marine areas, primarily from industries that are often responsible for marine disasters, constitutes a necessary step toward effective solutions.

Translational medicine protocol for proteomics clinical research on snakebite envenoming: contributions for develop studies in mechanisms and new biomarkers - Joeliton S. Cavalcante; Juliana Sartorelo Almeida; João Victor C. Coutinho; Edgar E. Neri Castro; Manuela B. Pucca; Alejandro Alagón; Rui Seabra Ferreira Junior (Archives of Toxicology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Mapping biocultural diversity: An integrative spatial approach to inform conservation and management decisions - Irene Otamendi-Urroz; Juan Miguel Requena-Mullor; Cristina Quintas-Soriano; Graeme S. Cumming; Antonio J. Castro (Ambio, 2026)
Effective conservation and sustainable management require metrics that capture the coupled dynamics of biological and cultural systems. Quantifying and mapping this biocultural diversity remains difficult due to its multidimensional and context-dependent nature. This study introduces the Biocultural Index for Refugia Exploration (BIRE), an integrative spatial approach combining biological and socio-cultural variables to map biocultural diversity. Using publicly available datasets, BIRE applies a percentile-based scoring system to identify biocultural diversity hotspots at the municipal scale. Tested in two contrasting Spanish regions (Almería and Navarra), BIRE revealed distinct spatial patterns, with higher values representing hotspots in rural and mountainous municipalities and lower values (coldspots) in urbanized areas. The index proved robust, flexible, and replicable across diverse social-ecological contexts. BIRE offers a policy-relevant framework linking scientific evidence with decision-making processes. In doing so, BIRE can guide targeted interventions in sustainable management, conservation, and planning, supporting decision-makers in identifying and prioritizing key areas.

Dendropsophin 1, an antimicrobial peptide from skin secretion of the tree frog Dendropsophus columbianus, exhibits tissue repair potential - Isabella S. Cassimiro; Bruno A. Ferreira; Simone R. Deconte; Taís C. Lima; Francyelle B.R. Moura; Mariana S. Castro; Fernanda A. Araújo (Toxicon, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Influence of almond’s canopy-induced shadows on actual evapotranspiration estimation by the TSEB model using sUAS multispectral and thermal imagery - M. R. Duran-Gomez; A. Torres-Rua; L. Hipps; W. Kustas; N. E. Bambach; K. Knipper; I. Wright; A. J. McElrone; J. H. Prueger; J. G. Alfieri; C. Coopmans; K. Meza; et al. (Irrigation Science, 2026)
Over the past decade, the estimation of water requirements in almond orchards has improved through the application of remote sensing models like the Two-Source Energy Balance (TSEB) model using various remote sensing platforms. However, there is limited understanding of how canopy-induced shadows influence surface reflectance and thermal infrared (TIR) signals particularly from small Unmanned Aircraft System (sUAS) imagery in energy balance models, and the effect on Latent Heat Flux (LE) estimations. This study evaluates LE estimates from the Priestley-Taylor TSEB model (TSEB-PT) with and without shadow filtering using sUAS-based multispectral and TIR imagery. It establishes a baseline for the impact of shadow filtering on model inputs and performance. Datasets were collected in 2021 and 2022, as part of the USDA led Tree-crop Remote sensing of Evapotranspiration eXperiment (T-REX) in almonds orchards across California. LAI-2200 C Plant Canopy Analyzer measurements facilitated the calibration of an empirical Leaf Area Index (LAI) model based on canopy fractional cover (FC) and NDVI (R 2 = 0.68). Shadow filtering caused land surface temperature (LST) differences up to 5 °C in young to semi-mature orchards (FC 0.40–0.80). In contrast, mature orchards (FC > 0.80) showed minimal influence due to the limited shadow occurrence on the imagery. Shadows appeared to reduce surface albedo (α alb ), mainly in interrow areas, thereby affecting the absorption of radiation and the partitioning of energy balance components. Their presence in sUAS imagery also hindered canopy delineation, impacting the accuracy of key TSEB inputs derived from canopy physical characteristics. Thus, the influence of shadow on TSEB estimated LE was more significant in lower fractional tree covers. While LE estimated by TSEB-PT without shadow filtering showed better agreement with observations, combining instantaneous TIR imagery with solar-noon shortwave data is recommended for accurate ETa assessment using sUAS datasets. These baseline results can be improved with more advanced formulations, supporting continued research on E/T partitioning and water stress in almond orchards under varying environmental conditions, particularly when there is advection of hot dry air.

Tirzepatide enhances liver structural integrity by promoting mitochondrial dynamics and mitophagy via PINK1/PRKN and SIRT3/NRF2 pathways in an obese-diabetic-menopausal mouse model - Ilitch A. Marcondes-de-Castro; Thatiany S. Marinho; Marcia B. Aguila; Carlos A. Mandarim-de-Lacerda (Tissue and Cell, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Reforestation strategies integrating tropical timber production can offset costs and finance forest restoration in the Brazilian Atlantic Forest - João Paulo Bispo Santos; Pedro Henrique Santin Brancalion; Mark S. Ashton; Florencia Montagnini; Claudia Fontana; Allana Katiussya Silva Pereira; Mário Tomazello-Filho; Vinicius Castro Souza; Daniel Piotto; Ricardo Ribeiro Rodrigues (Forest Ecology and Management, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Thermoregulation strategies and microhabitat structure as determinants of susceptibility to heat waves in two sympatric Mediterranean lizards - S. Blázquez-Castro; R. Barrientos; S. Reguera; I. Barja; R. Megía-Palma (Climatic Change, 2026)

Glycerol-supplemented medium promotes transition of Cupriavidus necator from heterotrophic to lithoautotrophic growth - I. Castro Gonzalez; N. Gorret; L. Lauterbach; S. E. Guillouet (Biotechnology Letters, 2026)

Replacing natural savannas with eucalyptus and soybeans changes the matrix use and reduces bat taxonomic and functional diversity in the Amazonian savannas - Bruna S. Xavier; Karen Mustin; Tiago M. Marques; Marcelo M. Ferreira; Renato R. Hilário; José J. Toledo; Isaí J. Castro; Jorge M. Palmeirim; Ana M.C. Santos; Marcus V. Vieira; William D. Carvalho (Agriculture, Ecosystems & Environment, 2026)

Strategies to build trustworthiness and increase diversity in colorectal cancer biospecimen research: a multi-phase, multi-site qualitative study - Kristi L. Roybal; Brett Nava-Coulter; Jane Roberts; Destiny Harden; Saul Castro; Anna Revette; Maria Connolly; Gina Johnson; Jennifer A. Rountree; Suzanne Brodney; Kimberly Schoolcraft; David A. Drew; et al. (Journal of Community Genetics, 2026)

The ornithine-arginine cycle supported a toxic, metalimnic Planktothrix rubescens bloom - Brittany N. Zepernick; David J. Niknejad; Emily E. Chase; Blessing A. Abiodun; Meaghan J. Adler; Katelyn A. Houghton; Jason L. Olavesen; Qudus Sarumi; Alexander R. Truchon; Jillian L. Walton; Jack H. Cheshire; Keara Stanislawczyk; et al. (Harmful Algae, 2026)

Drivers of seedling emergence and early growth of 12 European oak species: Results from a cross-continental experiment - Alexandro B. Leverkus; María Medina; Alba Lázaro-González; Laura Levy; Olivia Lorente-Casalini; Marino P. Reyes Martín; Enrique Andivia; Alessandro Bizzarri; Henrik Böhlenius; Vito E. Cambria; Claudia Cocozza; Branislav Cvjetković; et al. (Forest Ecology and Management, 2026)

Enantioselective toxicity of 3,4-methylenedioxypyrovalerone in Daphnia magna: Assessment of morphophysiological, behavioural, biochemical and reproductive responses - Ariana Pérez-Pereira; Ana R. Carvalho; Pedro A. Costa; Bruno B. Castro; João S. Carrola; Virgínia M.F. Gonçalves; Ana R.L. Ribeiro; Ana Sofia Almeida; Carla Fernandes; Maria E. Tiritan; Cláudia Ribeiro (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Replacing the natural savanna matrix with eucalyptus plantations and soybean fields changes the seed rain promoted by bats in Amazonian savannas - Bruna S. Xavier; Jeferson Vizentin-Bugoni; Marcelo M. Ferreira; Tiago M. Marques; Renato R. Hilário; José J. Toledo; Isaí J. Castro; Karen Mustin; Jorge M. Palmeirim; Marcus V. Vieira; William D. Carvalho (Biological Conservation, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Zika Virus Reprograms Microglial Mitochondrial Metabolism to Support Immune Activation and Viral Replication: Omega-3 DHA Counteracts Neuroinflammation and Viral Persistence - Heloísa Antoniella Braz-de-Melo; Fernanda Gomes Lago; Rafael Corrêa; Igor de Oliveira Santos; Paula Maria Quaglio Bellozi; Raquel das Neves Almeida; Wagner Fontes; Mariana S. Castro; Aline Maria Araújo Martins; Raphaela Menezes de Oliveira; Nadia Martins Serpa Rossi; Gabriel Pasquarelli-do-Nascimento; et al. (Molecular Neurobiology, 2026)

Historical Temperature Stability and Environmental Drivers Shape Patterns of Phylogenetic Diversity in Cactaceae - Afonso Kempner; Rodrigo Castro‐Souza; Dieison André Moi; Danilo Trabuco do Amaral; Rosane Garcia Collevatti; Sidney F. Gouveia; Isabel A. S. Bonatelli; Thadeu Sobral‐Souza (Journal of Biogeography, 2026)
Aim We aim to investigate the environmental drivers shaping macroecological patterns of phylogenetic structure in plants, using the cactus family (Cactaceae) as a model group. Major Taxa and Location Cactus family (Cactaceae), comprising 1892 species, distributed across the American continent (approximately 42 million km 2 ). Methods We compiled a robust dataset of 435,694 occurrence records and estimated two complementary metrics of phylogenetic structure: the standardised effect size of mean phylogenetic distance (ses.MPD, reflecting deep/basal lineages) and mean nearest taxon distance (ses.MNTD, reflecting recent/tip lineages). We also assessed the effects of climatic, topographic, and soil‐related variables on phylogenetic structure metrics at regional and continental scale. Results Phylogenetic structure in cacti is shaped by complex spatial interactions among environmental drivers varying across scales. Northern Mesoamerica—including central and northern Mexico and the southwestern United States—showed the highest ses.MPD but some of the lowest ses.MNTD values. This indicates that these regions harbour deeply divergent lineages while local communities remain composed of closely related species. Other regions, such as high‐elevation areas in South America, also showed high ses.MPD and ses.MNTD, indicating both deep and recent phylogenetic divergence. ses.MPD and ses.MNTD responded differently to environmental gradients, indicating that basal and tip lineages are influenced by different factors. Historical temperature stability (calculated as the temperature delta between the last glacial maximum and the present) was the strongest predictor of phylogenetic structure, mainly on a regional scale. Solar radiation and elevation, at the continental scale, also contributed to these patterns, indicating that topographic complexity and climatic drives recent phylogenetic divergence. Main Conclusions Cactus phylogenetic diversity is primarily driven by historical temperature stability but results from the combined influence of multiple environmental drivers acting across scales. These scale‐dependent effects reveal that cactus communities reflect both contemporary conditions and long‐term evolutionary constraints. Given the link between PD, ecosystem functioning, and conservation value, high‐PD regions, especially those with stable climates and heterogeneous topography, should be prioritized for conservation.

Reproductive success over Calliandra fasciculata Benth. floral anthesis: evidence of adaptive generalization - Rodrigo Santiago; Pedro J. Bergamo; Vinícius L.G. Brito; Marsal D. Amorim; Lucas B. Castro; Sabrina A. Lopes; Cinthia S. Novaes; Larissa C. Mendes; Gizele C.A. Silva; Danila M. Silva; Ilmara A.O. Ferreira; Bernardo O. Dias; et al. (Flora, 2025)

Unveiling enantioselective mechanisms of toxicity of butylone in Daphnia magna - Renata Vidal; Ana R. Carvalho; Juliana Faria; Joana Barbosa; Virgínia M.F. Gonçalves; Maria E. Tiritan; Cristina Couto; João S. Carrola; Bruno B. Castro; Adrián M.T. Silva; Ana R.L. Ribeiro; Cláudia Ribeiro (Aquatic Toxicology, 2025)

Andrographolide increases adult hippocampal neurogenesis and prolongs contextual fear memory - Laura F. Jaimes; Matheus C. Passos; Lara M. Z. Mansk; Caio M. de Castro; Julián T. F. Vega; Leonardo de O. Guarnieri; Flávio A. G. Mourão; Alexander Birbrair; Victor R. Santos; Márcio F. D. Moraes; Grace S. Pereira (Psychopharmacology, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Developing science-informed maps and climate service for extreme rainfall in Spain - S. M. Vicente-Serrano; S. Beguería; F. Reig; A. Royo; M. Arretxea; M. Gil; B. Latorre; A. El Kenawy; M. Franquesa; A. Halifa-Marin; M. Adell-Michavila; A. Crespillo; et al. (Natural Hazards, 2025)
This study introduces the first high-resolution hazard probability maps of extreme precipitation for Spain, marking a significant step toward a national climate service for hydrometeorological extremes. Using long-term daily precipitation records from a dense network of stations and incorporating topographic data, the methodology combines the Generalized Pareto distribution with universal kriging to spatially interpolate distribution parameters. These maps offer reliable estimates of extreme precipitation quantiles, validated against station-level observations, and are based on a stationary modelling framework—an approach supported by recent findings showing the temporal stability of such extremes in Spain and considered more robust than non-stationary alternatives. Distinct spatial patterns emerge, with intense daily precipitation distributed mainly along the Mediterranean coast and high total event precipitation in the northwest and southwest, reflecting the influence of varied weather systems. To support decision-making, the study aggregates these high-resolution data at the provincial level, aligning risk information with administrative boundaries, and enhancing its relevance for policy and planning. Furthermore, the maps are made accessible via an interactive online platform ( https://retornolluvias.csic.es ), enabling users to explore localized hazard probabilities, thereby supporting adaptation in water management and civil protection, among others.

Vermicompost, hydrogel, and beneficial soil microorganisms promote vetiver growth and microbial activity in Cu-impacted tailings - Sofia I. A. Pereira; Ana Faria; Ana S. S. Sousa; Nadine Sousa; Paula M. L. Castro; Helena Moreira (Environmental Sustainability, 2025)

Valorization of wastewater-derived biopolymers for use as soil amendments in agriculture - Catarina Miranda; Sofia I. A. Pereira; Ana S. S. Sousa; Philipp Wilfert; Mark van Loosdrecht; António Martins; Paula M. L. Castro; Catarina L. Amorim (Environmental Science and Pollution Research, 2025)

Assessment of antimicrobial, antiproliferative, and chemotactic properties of ranatuerin 2-PMe from cutaneous secretion of Lithobates palmipes (Spix, 1824) (Anura, Ranidae) - Géssica Gomes Barbosa; Carlos José Correia de Santana; Tulíbia Laurindo Silva; Welthon de Souza Teotonio; Lucas Fontes; Raquel Takaya; Ricardo Bentes de Azevedo; Patrícia Maria Guedes Paiva; Osmindo Rodrigues Pires Júnior; Wagner Fontes; Mariana S. Castro; Thiago Henrique Napoleão (Toxicon, 2025)

Antioxidant, UV-blocking, and biodegradable pectin films containing selenium nanoparticles for sustainable food packaging - Guilherme A.M. Jesus; Michael C. Castro; Paulo R. Souza; Johny P. Monteiro; Roberta M. Sabino; Shyam S. Sablani; Alessandro F. Martins; Elton G. Bonafé (Food Hydrocolloids, 2025)

How does the enhancement of carbon sequestration by non-native forests affect other ecosystem services? - Pilar Castro-Díez; Adrián Lázaro-Lobo; Romina D. Fernandez; Álvaro Alonso; Paula Cruces; Verónica Cruz-Alonso; Gary N. Ervin; Antonio Gallardo; Elena Granda; Daniel Gómez-Gras; Hélia Marchante; Daniel Moreno-Fernández; et al. (New Forests, 2025)

Gibberellin Regulates Sugar Metabolism and Modifies Cell Wall Composition in Soybean (Glycine max L. Merrill) - Raysa M. J. Sousa; Juliane M. Henschel; Diego S. Batista; Tatiane D. Silva; Sérgio H. S. Felipe; Gabriela Torres-Silva; Paulo V. L. Souza; Silvio A. Cândido-Sobrinho; Kristhiano Chagas; Kamila M. Castro; Evandro A. Fortini; Ludmila N. F. Correia; et al. (Journal of Plant Growth Regulation, 2025)

Hydro‐Functional Traits and Their Dissimilarity to the Neighbourhood Buffer Tree Growth Against the 2018–2020 Central European Drought - Lena Sachsenmaier; Florian Schnabel; Fon R. Tezeh; Pablo Castro Sánchez‐Bermejo; Nico Eisenhauer; Olga Ferlian; Sylvia Haider; Ronny Richter; Sharath S. Paligi; Bernhard Schuldt; Christian Wirth (Global Change Biology, 2025)
Climate change is predicted to increase the frequency and duration of drought events, threatening the functioning of Central European forests. While diverse forests often promote long‐term growth stability, their performance during extreme drought events remains debated. Understanding the effects of forest diversity on tree growth during drought requires not only a consideration of tree interactions with direct neighbouring trees but also of the species' morphological and physiological characteristics, i.e., a trait‐based approach. Contrasting species‐specific drought responses might be driven by hydro‐functional traits, which shape a tree's hydraulic safety and stomatal control strategy. We investigated individual tree growth before, during, and after the unprecedented 2018–2020 Central European drought, from a hydro‐functional perspective. We analysed annual growth data from 2611 trees in a temperate tree diversity experiment (MyDiv experiment, Germany), measured 14 hydro‐functional traits, and modelled individual tree growth across the years 2016–2021, considering the interaction of climatic conditions with hydro‐functional trait syndromes. Our results reveal that traits related to hydraulic safety and stomatal control potential were key drivers of tree growth across drought and non‐drought years. During the severe multi‐year drought, the growth of focal trees increased with either higher hydraulic safety or tighter stomatal control potential. Trait syndromes that were less advantageous under normal conditions provided beneficial effects under drought stress, reflecting a trade‐off in performance across conditions. Additionally, we found that hydro‐functional dissimilarity between a tree and its surrounding neighbors provided benefits for tree growth during drought. Therefore, our study suggests that planting tree mixtures with distinct hydro‐functional strategies can enhance resistance to future droughts.

Bioconversion of vine shoots into renewable products using ohmic heating extraction and autohydrolysis - Diego Cardoza; Joana S. Gomes-Dias; Sara G. Pereira; Inmaculada Romero; Eulogio Castro; Cristina M.R. Rocha (Sustainable Chemistry and Pharmacy, 2025)

Pilot-scale production of high-purity struvite fertilizer from livestock waste: Outcomes of the RE-LIVE WASTE project in Cyprus - Nomiki I. Kallikazarou; Olympia Nisiforou; Despoina A. Kokkinidou; Loukas Koutsokeras; Christodoulos Michael; José L. Castro; Andreas S. Anayiotos; Georgios Constantinides; George Botsaris; Ioannis A. Fotidis; Maria G. Antoniou (Journal of Environmental Management, 2025)

Consumption of yogurts containing buriti pulp and fermented milks containing orange bagasse increases the response of the endogenous antioxidant system and the expression of heat shock proteins in healthy rats - Juliana S. Graça; Bruna G. Castro; Caroline Heckler; Patrícia B. Batista; Rafael L. Camargo; Marianna M. Furtado; Luísa Freire; Mayra F. Melo; Maria Paula M.B.B. Gonçalves; Amanda M.T.M. Moya; Cínthia B.B. Cazarin; Tatiana C. Pimentel; et al. (Food Research International, 2025)

Design, manufacturing, and performance of innovative aluminium-backed BIPV facade modules: a case-study in Germany - S. Jahreis; B. Jaeckel; R. Koepge; J. Fröbel; P. Schenk; M. Pander; R. Castro (Energy and Buildings, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Enhanced biodegradation of petroleum in seawater using an autochthonous microbial consortium from the northeast coast of Brazil affected by the Venezuelan oil spill - José Evandro S. Pereira; João Vitor B. Borowski; Amanda P. Napp; Maiara M. Oliveira; Igor D.A. Ribeiro; Luzia Gabrielle Z. de Castro; Charley C. Staats; Augusto Schrank; Luciane M.P. Passaglia; Vânia Maria Maciel Melo; Lucymara Fassarella Agnez-Lima; Marilene H. Vainstein (Chemosphere, 2025)

Migration of oceanic fronts in the Pacific Southern Ocean during the Mid-Pleistocene transition - Maria Julia de Castro; Igor M. Venancio; Thiago P. Santos; Douglas V.O. Lessa; João M. Ballalai; Ana Luiza S. Albuquerque (Marine Micropaleontology, 2025)

Evaluation of resistance to charcoal rot in different phenological stages of the common bean crop - Jane C. S. Santos; Jerônimo C. Borel; Antonio E. S. Costa; Amanda N. Menezes; Mateus S. Castro; Kethelen G. S. Viana; Francine H. Ishikawa (European Journal of Plant Pathology, 2025)

Cross-canyon variability in zooplankton backscattering strength in a river-influenced upwelling area - Macarena Díaz-Astudillo; Manuel I. Castillo; Pedro A. Figueroa; Leonardo R. Castro; Ramiro Riquelme-Bugueño; Iván Pérez-Santos; Oscar Pizarro; Gonzalo S. Saldías (Ocean Science, 2025)
Zooplankton are a key component of food webs in upwelling systems. Their distribution is influenced not only by mesoscale and climate dynamics but also by topography and local currents. Submarine canyons that incise the continental shelf can act as conduits, transporting deep, nutrient-rich waters to shallower regions and promoting coastal biological productivity. Consequently, these canyons facilitate the advection and accumulation of zooplankton. We aimed to describe the spatio-temporal variability in zooplankton distribution (using net samples and acoustic data) and their association with local currents in a long, narrow submarine canyon located in the highly productive continental shelf off central Chile. The backscattering strength (Sv), a proxy for zooplankton biomass, was highly variable on both diurnal and spatial scales. Higher Sv and abundances were found at night, following the classic diel vertical migration pattern. Zooplankton were not uniformly distributed within the canyon. In the surface and mid-depth layers, the canyon walls accumulated more zooplankton than the center, particularly during the nighttime. Within the canyon, the currents were asymmetrical and frequently reversed direction. When the positive along-canyon current was stronger on the northern slope, Sv was also higher on that wall. This pattern was especially evident in the section closer to the canyon head. We show that the Biobio Canyon is a highly dynamic environment where oceanographic conditions can rapidly shift. Our findings suggest a feasible mechanism for zooplankton retention driven mainly by along-canyon flow asymmetry and vertical migrations.

Multiple anthelmintic drug resistance in the canine hookworm Ancylostoma caninum: AAVP position paper and research needs - Timothy G. Geary; Jason Drake; John S. Gilleard; Jeba R.J.Jesudoss Chelladurai; Pablo D. Jimenez Castro; Ray M. Kaplan; Antoinette E. Marsh; Craig R. Reinemeyer; Guilherme G. Verocai (Veterinary Parasitology, 2025)

Dynamics and interrelationships between antibiotic resistance, organic micropollutants and bacterial communities in full-scale rural constructed wetlands - A. Margarida Teixeira; Diana Matos; Norberta Coelho; Lahiruni M. Halwatura; Ivone Vaz-Moreira; Paula M.L. Castro; Diana S. Aga; Célia M. Manaia (Journal of Cleaner Production, 2025)

Fermented brewer's spent grain as a sustainable feed ingredient impacts meagre (Argyrosomus regius) growth, intermediary metabolism, digestive enzymes, oxidative stress, and intestinal histology - T. Estevão-Rodrigues; H. Fernandes; S. Moutinho; A. Couto; I. Belo; C. Castro.; P. Pousão; J.M. Salgado; A. Oliva-Teles; H. Peres (Animal Feed Science and Technology, 2025)

Adenomatous polyposis in a cow associated to mutations in the adenomatous polyposis coli (APC) tumour-suppressor gene - O. Quesada-Canales; A. Castro-Alonso; E. Plamenova Stefanova; M. Andrada; J. Díaz-Delgado; S. Zhao; K.L. Ho (Journal of Comparative Pathology, 2025)

Laboratory experiments on the visible to near- infrared (VNIR) spectroscopy of water ice and lunar highland simulant mixtures: Effects of particle size, particle shape, phase angle, and ice abundance - N. de Castro; S. Li (Icarus, 2025)

Lower inoculum sizes of phosphorus-solubilizing bacteria benefit maize growth and soil enzyme activity in P-fertilized soils - Sofia I. A. Pereira; Ana S. S. Sousa; Aldo B. Felpeto; Andreia Miguel; João C. Pinto; Paula M. L. Castro; Helena Moreira (Symbiosis, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Cytotoxic and metabolic effects of organic extracts from airborne fine particulate matter (PM2.5) in neuronal cells - Tatiana Silva; Célia Alves; Margarita G. Evtyugina; Ana S. Dias; Guilherme Martins Pereira; Pérola de Castro Vasconcellos; Maria de Fátima Andrade; Helena Oliveira; Iola F. Duarte (Environmental Toxicology and Pharmacology, 2025)

Body development, ingestive behaviour, and physiological responses of Nelore and Crossbred heifers - C. S. Santos; A. R. D. L. Souza; A. L. J. Ferraz; F. A. M. Sterza; R. V. Rohod; M. F. Castro; L. S. Amorim; M. C. E. Queiroz; G. B. Almeida; M. V. M. Oliveira; A. R. D. Santos; D. M. Oliveira (Tropical Animal Health and Production, 2025)

How septoria leaf blotch affects nitrogen dynamics, grain yield and protein concentration in wheat - S. I. Golik; A. C. Castro; H. M. Pardi; M. R. Simón (Cereal Research Communications, 2025)

Wastewater-Based Epidemiology for Analysis of Human Papillomavirus Infections in a Uruguayan Urban Area - C. Fernandez-Sabatella; G. Corrales; L. Monzon; E. Andrade; N. Sica; E. Cardozo; N. Baccardatz; J. Jacques; S. Castro; M. Castells; M. Victoria; R. Colina (Food and Environmental Virology, 2025)

Challenges for coral restoration in Southwestern Atlantic reefs: guidelines for ethical and sustainable practices - Miguel Mies; Guilherme O. Longo; Adalto Bianchini; Emiliano N. Calderon; Clovis B. Castro; Samuel C. Faria; Ronaldo B. Francini-Filho; Flávia M. Guebert; Marcelo V. Kitahara; Carlos H. F. Lacerda; Tito M. C. Lotufo; Laura F. B. Marangoni; et al. (Biodiversity and Conservation, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

In vitro antitumor effects of aqueous extract and protease inhibitors from Sterculia striata st. Hil. et naud and metabolite profiling - Tadeu F. Braga Junior; Nerilson M. Lima; Gabriela P. Carli; Roberta M Cachuba; Gracimério J Guarneire; Beatriz J Tabai; Roberta M Abrão; Samuel G Barbosa; Lucas S. Machado; Jander S Nunes; Fabiana S. Machado; Teresinha de Jesus A. S. Andrade; et al. (Natural Product Research, 2025)

The use of egg quality parameters to evaluate the effect of a diet supplemented with algae and antioxidants in turbot (Scophthalmus maximus) - S. Ramos-Júdez; E. Fatsini; C. Marrero-Alemán; C. García-Pichel; P. Parente; D. Medina; C. Castro; E. Cabrita; C. C.V. Oliveira (Aquaculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Effects of dietary supplementation with slow-release urea coated with carnauba wax on intake, ingestive behavior, selectivity, ruminal parameters, performance and carcass traits of lambs - Tainan da Silva Batista; Leilson R. Bezerra; Pedro H.S. Mazza; Analivia M. Barbosa; Beatriz S.C. de Castro; Melissa D. Ferrer; Ana Carolina Ferreira; Jasiel S. de Morais; Edson C. da Silva Filho; Ronaldo L. Oliveira (Small Ruminant Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Synthesis, Characterization, and Biomolecular Interactions of a novel Copper(II) Complex: DNA and BSA Binding Studies - Amineh Mashkoori; Maryam Mohamadi; S. Yousef Ebrahimipour; Jesus Castro (Journal of Fluorescence, 2025)

Microbiome adaptation of aerobic granular sludge allows process resilience during the treatment of seawater-based wastewater with pharmaceuticals - Catarina Miranda; Alexandra S. Maia; Maria Elizabeth Tiritan; Paula M.L. Castro; Catarina L. Amorim (Journal of Water Process Engineering, 2025)

Fluoroquinolone and sulfonamide antibiotics (single and mixtures) impair the motor function of zebrafish larvae at environmentally relevant concentrations - Gleyson B. Castro; Juliano J. Corbi; Mateus Cottorello-Fonsêca; Daniela Correia; Demetrio Raldúa; David S. Alexandre; Thandy Junio da Silva Pinto; Eva Prats; Melissa Faria (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Can macro- or meso-scale coping capacity variables improve the classification of building flood losses? - D. Rodríguez Castro; M. Cools; S. Roucour; P. Archambeau; D. Molinari; A. R. Scorzini; C. Dessers; S. Erpicum; M. Pirotton; J. Teller; B. Dewals (Natural Hazards, 2025)

Regulatory role of annexin A1 in NLRP3 inflammasome activation in atopic dermatitis: insights from keratinocytes in human and murine studies - Rebeca D. Correia-Silva; Mab P. Corrêa; Maria Eduarda de Castro; Joaquim S. Almeida; Solange C. G. P. D’Ávila; Sonia M. Oliani; Karin V. Greco; Cristiane D. Gil (Journal of Molecular Medicine, 2025)

Valorization of residual ashes from boiler combustion process into activated carbon for adsorption of food industry wastewater - L. E. N. Castro; L. R. Matheus; W. G. Sganzerla; L. M. S. Colpini (International Journal of Environmental Science and Technology, 2025)

Allocation and use of body energy reservoirs in striped dolphins and Blainville's beaked whales: Snowball effect in negative energetic balance - Yara Bernaldo de Quirós; Marina Arregui; Manuel Arbelo; Ayoze Castro‐Alonso; Nakita Câmara; Zachary S. Clayton; Francesco M. A. Consoli; Andreas Fahlman; Martina Palomino‐Schätzlein; Raquel Puig‐Lozano; Miguel A. Rivero; Eva Sierra; et al. (Marine Mammal Science, 2025)
Climate change, overfishing, and other anthropogenic activities can negatively impact the energetic balance and body condition of cetaceans. Still, cetaceans must meet their energetic demands for survival, which are more expensive to maintain in the marine environment. The resilience of cetaceans to negative energy balance periods is unknown. We analyzed where striped dolphins, a medium‐sized dolphin with shallow‐intermediate diving habits, and Blainville's beaked whales, a larger odontocete with an extreme diving profile, store their energy reserves and how they use that energy. We performed dissections of body mass compartments of fresh dead adults of similar total body lengths but different body masses, determined the lipid and protein content of blubber and muscle, and calculated oxygen stores and the aerobic dive limit. Proteins in muscle were the largest source of energy stores for both species, followed by lipids in the blubber and muscle. Both species catabolized blubber and muscle simultaneously when losing body mass to avoid impairing other important functions. When these functions are impaired, a cascade of increased field metabolic rate and decreased energy intake may occur, decreasing their resilience to environmental challenges and making them more susceptible to diseases, ultimately resulting in death by starvation.

Bromelain as a natural anti-inflammatory drug: a systematic review - Taline Alves Nobre; Athanara Alves de Sousa; Irislene Costa Pereira; Álina Mara Carvalho Pedrosa-Santos; Luana de Oliveira Lopes; Nicole Debia; Heba A. S. El-Nashar; Mohamed El-Shazly; Muhammad Torequl Islam; João Marcelo de Castro e Sousa; Francisco Leonardo Torres-Leal (Natural Product Research, 2025)

Homologous acetylenic acetogenins from Porcelia macrocarpa R.E. (Fries) displayed potent activity against amastigotes from Trypanosoma cruzi - Ivanildo A. Brito; Erica V. Castro Levatti; Luis O. Regasini; Edgard A. Ferreira; Flavia B. Lopes; João Paulo S. Fernandes; João M. Batista; Andre G. Tempone; João Henrique G. Lago (Phytochemistry, 2025)

Investigating the ability of standard tests to detect improvements in behavior after a 9-week training program in shelter dogs – A pilot study - Ana Catarina Vieira de Castro; Mariah Malone; Miriam Casaca; Urša Blenkuš; Lurdes Gomes; Parizad Baria-Unwalla; I.Anna S. Olsson (Journal of Veterinary Behavior, 2025)

Trade-offs for healthy and sustainable diets in Europe: Social-ecological dynamics in an intensive agricultural system - A. Jiménez-Aceituno; M.D. López-Rodríguez; A.J. Castro; S. Cortés-Calderón; D. Collste; G. Aparicio; L. Rölfer; M.A. Bote; L. Marín; M.A. Gómez-Tenorio; B. González-Martín (Global Food Security, 2025)

Cost-effective alternatives to facilitate biomonitoring and bioassessment of neotropical streams - Francisco Valente-Neto; Renato B. Dala-Corte; Almir M. Cunico; André L.B. Magalhães; Bruno S. Godoy; Cecília G. Leal; Diego M.P. Castro; Diego R. Macedo; Dilermando P. Lima-Junior; Éder A. Gubiani; Fabio de O. Roque; Fabrício B. Teresa; et al. (Science of The Total Environment, 2025)

Histopathological and diagnostic aspects of glanders based on a case series from Brazil - A.F.C. Nassar; D.P. Chiebao; C. Del Fava; S. Miyashiro; V. Castro; R.A. Ogata; J.M. Yamamora; C.A.S. Monteiro; E.J.B. Monteiro (Journal of Equine Veterinary Science, 2025)

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

Nowhere to hide: massive corals’ mortality after cumulative heat stress in a putative climate change refugium - Fernando C. Cardoso; Ivan M. Carneiro; Guilherme M. Castro; Gabriel O. Cardoso; Aline Shimada; Myllena S. Pereira; Livia B. Villela; Paulo S. Salomon; Rodrigo L. Moura (Coral Reefs, 2025)

PFAS biodegradation by Labrys portucalensis F11: Evidence of chain shortening and identification of metabolites of PFOS, 6:2 FTS, and 5:3 FTCA - Mindula K. Wijayahena; Irina S. Moreira; Paula M.L. Castro; Sarah Dowd; Melissa I. Marciesky; Carla Ng; Diana S. Aga (Science of The Total Environment, 2025)

Evaluating the precise grapevine water stress detection using unmanned aerial vehicles and evapotranspiration-based metrics - V. Burchard-Levine; I. Borra-Serrano; J. M. Peña; W. P. Kustas; J. G. Guerra; J. Dorado; G. Mesías-Ruiz; M. Herrezuelo; B. Mary; L. M. McKee; A. I. de Castro; S. Sanchez-Élez; et al. (Irrigation Science, 2025)
Precise irrigation management requires accurate knowledge of crop water demand to adequately optimize water use efficiency, especially relevant in arid and semi-arid regions. While unoccupied aerial vehicles (UAV) have shown great promise to improve the water management for crops such as vineyards, there still remains large uncertainties to accurately quantify vegetation water requirements, especially through physically-based methods. Notably, thermal remote sensing has been shown to be a promising tool to evaluate water stress at different scales, most commonly through the Crop Water Stress Index (CWSI). This work aimed to evaluate the potential of a UAV payload to estimate evapotranspiration (ET) and alternative ET-based crop water stress indices to better monitor and detect irrigation requirements in vineyards. As a case study, three irrigation treatments within a vineyard were implemented to impose weekly crop coefficient (Kc) of 0.2 (extreme deficit irrigation), 0.4 (typical deficit irrigation) and 0.8 (over-irrigated) of reference ET. Both the original Priestley-Taylor initialized two-source energy balance model (TSEB-PT) and the dual temperature TSEB (TSEB-2T), which takes advantage of high-resolution imagery to discriminate canopy and soil temperatures, were implemented to estimate ET. In a first step, both ET models were evaluated at the footprint level using an eddy covariance (EC) tower, with modelled fluxes comparing well against the EC measurements. Secondly, in-situ physiological measurements at vine level, such as stomatal conductance (g st ), leaf (Ψ leaf ) and stem (Ψ stem ) water potential, were collected simultaneously to UAV overpasses as plant proxies of water stress. Different variants of the CWSI and alternative metrics that take advantage of the partitioned ET from TSEB, such as Crop Transpiration Stress Index (CTSI) and the Crop Stomatal Stress Index (CSSI), were also evaluated to test their statistical relationship against these in-situ physiological indicators using the Spearman correlation coefficient ( ρ ). Both TSEB-PT and TSEB-2T CWSI related similarly to in-situ measurements (Ψ leaf : ρ ~ 0.4; Ψ stem : ρ ~ 0.55). On the other hand, stress indicators using canopy fluxes (i.e. CTSI and CSSI) were much more effective when using TSEB-2 T (Ψ leaf : ρ = 0.45; Ψ stem : ρ = 0.62) compared to TSEB-PT (Ψ leaf : ρ = 0.18; Ψ stem : ρ = 0.49), revealing important differences in the ET partitioning between model variants. These results demonstrate the utility of physically-based models to estimate ET and partitioned canopy fluxes, which can enhance the detection of vine water stress and quantitatively assess vine water demand to better manage irrigation practices.

Evaluation of impacts of biosolids application and drainage water management on soil N2O and CH4 emissions using the flux gradient method - Qiurui Zhu; Eric A. Davidson; Jacob G. Hagedorn; Mark S. Castro; Thomas R. Fisher; Rebecca J. Fox; Shannon E. Brown; James W. Lewis (Agriculture, Ecosystems & Environment, 2025)

Impact of common interest group participation and aquaculture development programs on fish productivity and net returns: evidence from Nile tilapia farming - Castro N. Gichuki; S. Wagura Ndiritu; Achom Barbara Emodoi (Aquaculture International, 2025)
Development programs have intensified support for the aquaculture sector to improve production and productivity, as well as food security and diet quality for smallholder farmers. This paper examines the impact of farmers’ participation in Common Interest Groups (CIGs) and the effects of aquaculture development support programs on the net returns and productivity of tilapia fish in Kenya. The study used household-level data of 506 members of the CIG who were randomly selected for the treatment group and benefited from Aquaculture Business Development Program (ABDP) interventions. The analysis employed an endogenous switching regression model to account for selection bias. The results reveal that membership in CIGs and receiving fish production interventions have resulted in a 32.3% increase in tilapia fish sales returns and a 6.6% increase in tilapia fish yields. Specifically, ABDP interventions are aimed at providing fish producers with ponds and cages had a significant and beneficial effect on fish yields and income returns. This finding suggests that policies with targeted interventions that support aquaculture infrastructure can play a significant role in increasing the incomes of smallholder farmers and reducing rural poverty in Kenya.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

A Probabilistic View of Forbidden Links: Their Prevalence and Their Consequences for the Robustness of Plant–Hummingbird Communities - François Duchenne; Elisa Barreto; Esteban A. Guevara; Holger Beck; Carolina Bello; Rafaela Bobato; Daniela Bôlla; Emanuel Brenes; Nicole Büttner; Ana P. Caron; Nelson Chaves‐Elizondo; María J. Gavilanes; et al. (Ecology Letters, 2025)
The presence in ecological communities of unfeasible species interactions, termed forbidden links, due to physiological or morphological exploitation barriers has been long debated, but little direct evidence has been found. Forbidden links are likely to make ecological communities less robust to species extinctions, stressing the need to assess their prevalence. Here, we used a dataset of plant–hummingbird interactions, coupled with a Bayesian hierarchical model, to assess the importance of exploitation barriers in determining species interactions. We found evidence for exploitation barriers between flowers and hummingbirds across the 32 studied communities; however, the proportion of forbidden links changed drastically among communities because of changes in trait distributions. The higher the proportion of forbidden links, the more they decreased network robustness because of constraints on interaction rewiring. Our results suggest that exploitation barriers are not rare in plant–hummingbird communities and have the potential to limit the rescue of species experiencing partner extinction.

Participatory mapping of uses and ecosystem services as a useful tool for the identification of conflicts in Marine Protected Areas: The case of the Cíes Islands archipelago (NW Spain) - J. Molina-Urruela; E. Fernández; A.J. Castro; M. Expósito-Granados; A. Ovejero-Campos; S. Villasante; G. Méndez-Martínez (Ocean & Coastal Management, 2024)

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Monitoring macroplastics in aquatic and terrestrial ecosystems: Expert survey reveals visual and drone-based census as most effective techniques - L. Gallitelli; P. Girard; U. Andriolo; M. Liro; G. Suaria; C. Martin; A.L. Lusher; K. Hancke; MCM Blettler; O. Garcia-Garin; I.E. Napper; L. Corbari; et al. (Science of The Total Environment, 2024)

Sediment recycling during the Holocene marine transgression in Ría de Vigo (NW Iberia): multiproxy evidence and environmental implications - C. Muñoz Sobrino; A. Castro-Parada; V. Cartelle; N. Martínez-Carreño; C. Delgado; N. Cazás; I. Lázaro; S. García-Gil (Quaternary Science Reviews, 2024)

Development and evaluation of fermented milk with Lactobacillus acidophilus added to concentrated cranberry (Vaccinium macrocarpon) juice with the potential to minimize the recurrence of urinary tract infections - Karina de Fátima Bimbatti; Ramon da Silva Rocha; Isabela Zanatta Braido; Isadora de Castro Lima; Paula Benoso; Marcelo Thomazini; Paulo José do Amaral Sobral; Fabiana Faleiros; Carmen S. Favaro-Trindade (Food Research International, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Protease inhibitors characterisation by SDS-PAGE and MALDI-TOF from Alocasia macrorrhizos and their modulation of macrophage immune-inflammatory properties - Isac H. Cordeiro; Nerilson M. Lima; Elaine C. Scherrer; Gabriela P. Carli; Teresinha de Jesus A. S. Andrade; Sandra B. R. Castro; Marcone A. L. de Oliveira; Caio Cesar S. Alves; Alessandra P. Carli (Natural Product Research, 2024)

Beyond counting calls: estimating detection probability for Antarctic blue whales reveals biological trends in seasonal calling - Franciele R. de Castro; Danielle V. Harris; Susannah J. Buchan; Naysa Balcazar; Brian S. Miller (Frontiers in Marine Science, 2024)
We explore the utility of estimating the density of calls of baleen whales for better understanding acoustic trends over time. We consider as a case study stereotyped ‘song’ calls of Antarctic blue whales ( Balaenoptera musculus intermedia ) on their Antarctic feeding grounds over the course of a year-long, continuous recording from 2014. The recording was made in the Southern Ocean from a deep-water autonomous hydrophone moored near the seafloor in the Eastern Indian sector of the Antarctic. We estimated call density seasonally via a Monte-Carlo simulation based on the passive sonar equation, and compared our estimates to seasonal estimates of detection rate, which are commonly reported in acoustic studies of Antarctic blue whales. The resulting seasonal call densities at our Antarctic site were strongly influenced by seasonally varying noise levels, which in turn yielded seasonal differences in detection range. Incorporating the seasonal estimates of detection area into our analysis revealed a pattern of call densities in accord with historic (non-acoustic) knowledge of Antarctic blue whale seasonal distribution and migrations, a pattern that differed from seasonal detection rates. Furthermore, our methods for estimating call densities produced results that were more statistically robust for comparison across sites and time and more meaningful for interpretation of biological trends compared to detection rates alone. These advantages came at the cost of a more complex analysis that accounts for the large variability in detection range of different sounds that occur in Antarctic waters, and also accounts for the performance and biases introduced by automated algorithms to detect sounds. Despite the additional analytical complexities, broader usage of call densities, instead of detection rates, has the potential to yield a standardized, statistically robust, biologically informative, global investigation of acoustic trends in baleen whale sounds recorded on single hydrophones, especially in the remote and difficult to access Antarctic.

Deadwood decomposition in burnt mediterranean pine reforestations across an elevation gradient: A 15-year study - R. Juan-Ovejero; M.P. Reyes-Martín; A. Elghouat; A.B. Leverkus; S. Seibold; J. Castro (Forest Ecology and Management, 2024)

Digitalising BIPV energy simulation: A cross tool investigation - Rebecca Jing Yang; Yusen Zhao; Sujan Dev Sureshkumar Jayakumari; Astrid Schneider; S. Prithivi Rajan; Jonathan Leloux; Philippe Alamy; Gavin Prasetyo Raharjo; Fedele Rende; Tharushi Samarasinghalage; Ana Marcos Castro; Nuria Martin Chivelet; et al. (Energy and Buildings, 2024)

A case study of depolymerization in silicates: Melting of quartz and zircon crystallization at high pressure - A. Sánchez-Navas; S. Melchor; J. Ortega-Castro; I. Vidal-Daza; A. Castro (Chemical Geology, 2024)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

SpinelVA. A new perspective for the visual analysis and classification of spinel group minerals - Antonella S. Antonini; Leandro Luque; Gabriela R. Ferracutti; Ernesto A. Bjerg; Silvia M. Castro; María Luján Ganuza (Earth Science Informatics, 2024)

Dynamic livelihoods, gender and poverty in marine protected areas: Case study from Zanzibar, Tanzania - Felicity Pike; Lars Lindström; Josefin Ekstedt; Narriman S. Jiddawi; Maricela de la Torre-Castro (Ambio, 2024)
Livelihood initiatives are common within marine protected areas (MPAs) aiming for poverty alleviation or higher income opportunities. However, results can be mixed in reality, as well as change over time. Furthermore, who benefits is a key consideration, as results can vary based on inequalities, including gender. Here, the monetary outcomes of different livelihood strategies were investigated across three MPA regions in Zanzibar, Tanzania. Using a quantitative approach, the results show that livelihoods have shifted in a six-year period, with livelihood strategies differing in poverty incidence and income. Livelihood initiatives, namely seaweed farming and tourism, did not provide significantly higher monetary returns compared to long-standing livelihoods, such as fisheries. Seaweed farming showed income stability but a high poverty incidence predominantly within women-headed households. During the study period, men primarily remained in fisheries, whilst women shifted to small-scale businesses and fisheries, largely exiting seaweed farming. This underscores a need for adaptive, gender sensitive management within fast changing coastal contexts.

Organ-specific proteomes of Selaginella convoluta provide insights into its desiccation tolerance mechanisms - Fernanda Priscila Santos Reginaldo; Luiz Fernando Rodrigues de Souza; Daisy Sotero Chacon; Marlon Dias Mariano Santos; Taffarel Melo Torres; Ivanice Bezerra da Silva; Alan de Araújo Roque; Carlos André O. Ricart; Mariana S. Castro; Paulo Costa Carvalho; Wagner Fontes; Marcelo Valle de Sousa; et al. (Plant Biosystems, 2024)

Proteomic features of gray matter layers and superficial white matter of the rhesus monkey neocortex: comparison of prefrontal area 46 and occipital area 17 - Paola B. Castro-Mendoza; Christina M. Weaver; Wayne Chang; Maria Medalla; Kathleen S. Rockland; Lisa Lowery; Elizabeth McDonough; Merina Varghese; Patrick R. Hof; Dan E. Meyer; Jennifer I. Luebke (Brain Structure and Function, 2024)
In this novel large-scale multiplexed immunofluorescence study we comprehensively characterized and compared layer-specific proteomic features within regions of interest of the widely divergent dorsolateral prefrontal cortex (A46) and primary visual cortex (A17) of adult rhesus monkeys. Twenty-eight markers were imaged in rounds of sequential staining, and their spatial distribution precisely quantified within gray matter layers and superficial white matter. Cells were classified as neurons, astrocytes, oligodendrocytes, microglia, or endothelial cells. The distribution of fibers and blood vessels were assessed by quantification of staining intensity across regions of interest. This method revealed multivariate similarities and differences between layers and areas. Protein expression in neurons was the strongest determinant of both laminar and regional differences, whereas protein expression in glia was more important for intra-areal laminar distinctions. Among specific results, we observed a lower glia-to-neuron ratio in A17 than in A46 and the pan-neuronal markers HuD and NeuN were differentially distributed in both brain areas with a lower intensity of NeuN in layers 4 and 5 of A17 compared to A46 and other A17 layers. Astrocytes and oligodendrocytes exhibited distinct marker-specific laminar distributions that differed between regions; notably, there was a high proportion of ALDH1L1-expressing astrocytes and of oligodendrocyte markers in layer 4 of A17. The many nuanced differences in protein expression between layers and regions observed here highlight the need for direct assessment of proteins, in addition to RNA expression, and set the stage for future protein-focused studies of these and other brain regions in normal and pathological conditions.

Polycyclic aromatic hydrocarbons in seawater after the mysterious oil spill of 2019 on the Pernambuco coast, northeast Brazil - Thayane Cristina da S. Moreira; Ana Flávia B. de Oliveira; Pedro Gabriel C. de Lucena; Estefani S. do Nascimento; Leonardo M.F. de Almeida; Cristiane Maria V. de Araújo-Castro; Lino Angel V. Rojas; Gilvan T. Yogui; Eliete Zanardi-Lamardo; Jandyson M. Santos (Marine Pollution Bulletin, 2024)

Antimicrobial resistance patterns of Staphylococcus spp. isolated from clinical specimens of companion animals in Northern Portugal, 2021–2023 - D. Araújo; R. Oliveira; B.L. Silva; J. Castro; C. Ramos; F. Matos; C. Almeida; S. Silva (The Veterinary Journal, 2024)

Reconciling the soil stewardship paradox: Knowledge without care, care without knowledge - Alexander Neaman; Claudia Navarro-Villarroel; Francisca Poblete-Ramos; Nilo Lizardi; Elliot Burnham; Olga Huerta-Salinas; Sarah Zabel; Dmitry S. Ermakov; Mónica Castro; Siegmar Otto (Geoderma Regional, 2024)

Fed-batch fermentation of sugarcane biomass applied for biomolecules production in fluidized bed reactor - F.A.F. Antunes; C.A. Prado; M.J.A. Fernandez; R.F. Grigório; A.S. Silva; A.E. Mera; M.J. Castro-Alonso; T.M. Rocha; S. Sanchez-Muñoz; J.C. Santos; S.S. da Silva (Bioresource Technology Reports, 2024)

Toxicity of butylone and its enantiomers to Daphnia magna and its degradation/toxicity potential using advanced oxidation technologies - Ana R. Carvalho; Ana M. Morão; Virgínia M.F. Gonçalves; Maria Elizabeth Tiritan; Ana M. Gorito; M.Fernando Pereira; Adrián M.T. Silva; Bruno B Castro; João S. Carrola; Maria M. Amorim; Ana R.L. Ribeiro; Cláudia Ribeiro (Aquatic Toxicology, 2024)

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Biodegradable PBAT/PLA blend films incorporated with turmeric and cinnamomum powder: A potential alternative for active food packaging - Layara L.R.L. de Castro; Lauriene G.L. Silva; Iago R. Abreu; Cristiano J.F. Braz; Samara C.S. Rodrigues; Regilda S. dos R. Moreira-Araújo; Rudy Folkersma; Laura H. de Carvalho; Renata Barbosa; Tatianny S. Alves (Food Chemistry, 2024)

Reducing citrus effluent toxicity: Biological-electrochemical treatment with diamond anode - Débora S. Vilar; Hugo H. Correia da Silva; Aline R. Dória; Nádia H. Torres; José H. Vallim; Vera L.S. Salgado de Castro; Juliana Heloisa Pinê Américo-Pinheiro; Giancarlo R. Salazar-Banda; Katlin I. Barrios Eguiluz; Luiz Fernando R. Ferreira (Environmental Pollution, 2024)

New hard tick (Acari: Ixodidae) reports and detection of Rickettsia in ticks from Sierra Nevada de Santa Marta, Colombia - Ángel Oviedo; Miguel M. Rodríguez; Fernando S. Flores; Lyda R. Castro (Experimental and Applied Acarology, 2024)
The Sierra Nevada de Santa Marta (SNSM), located in northern Colombia, is considered a geographical island with high levels of biodiversity and endemism. However, little is known about tick species and their associated microorganisms at the SNSM. In this study we sampled host-seeking ticks in areas of the town of Minca within the SNSM. We collected 47 ticks identified as Amblyomma pacae , Amblyomma longirostre , Amblyomma ovale , Amblyomma mixtum , Haemaphysalis juxtakochi , Ixodes sp. cf. Ixodes affinis and Ixodes sp. Of these ticks, we tested for Rickettsia spp. by amplifying the gltA , SCA1 , and 16S rRNA genes via PCR. Rickettsia amblyommatis was detected in one pool of 3 larvae and in a female of A. pacae . Additonally, we isolated Rickettsia sp. belonging to the group of spotted fevers in larvae of A. longirostre . This study reports new findings of six species of ticks and two species of Rickettsia within the SNSM.

Large-scale crops are sources of polyphagous pest populations for small farmers at the landscape level: an isotope tracing model - Érika C. S. Castro; Nícholas F. Camargo; Danyelle R. Novaes; Marina A. M. Pereira; Gabriela B. Nardoto; Pedro H. B. Togni (Journal of Pest Science, 2024)

Precision and accuracy of common coral reef sampling protocols revisited with photogrammetry - Ivan M. Carneiro; João A. Sá; Pamela M. Chiroque-Solano; Fernando C. Cardoso; Guilherme M. Castro; Paulo S. Salomon; Alex C. Bastos; Rodrigo L. Moura (Marine Environmental Research, 2024)

Bacterial nanocellulose spheres coated with meta acrylic copolymer: Vaccinium meridionale swartz extract delivery for colorectal cancer chemoprevention - M. Osorio; L. Posada; E. Martínez; V. Estrada; G. Quintana; Maria E. Maldonado; S. Peresin; J. Orozco; C. Castro (Food Hydrocolloids, 2024)

A spatial framework for improved sanitation to support coral reef conservation - Caitlin D. Kuempel; Jacqueline Thomas; Amelia S. Wenger; Stacy D. Jupiter; Andrés F. Suárez-Castro; Nabeela Nasim; Carissa J. Klein; Ove Hoegh-Guldberg (Environmental Pollution, 2024)

Safety Assessment of the Potential Probiotic Bacterium Limosilactobacillus fermentum J23 Using the Mexican Fruit Fly (Anastrepha ludens Loew, Diptera: Tephritidae) as a Novel In Vivo Model - Cecilia Castro-López; Carlos Pascacio-Villafán; Martin Aluja; Hugo S. García; Aarón F. González-Córdova; Belinda Vallejo-Cordoba; Adrián Hernández-Mendoza (Probiotics and Antimicrobial Proteins, 2024)

The role of snow in scavenging aerosol particles: A physical-chemical characterization - C. Blanco-Alegre; A.I. Calvo; A. Castro; F. Oduber; E. Alonso-Blanco; C. Alves; M. Cerqueira; R. López; F. Lucarelli; S. Nava; G. Calzolai; R. Fraile (Science of The Total Environment, 2024)

Bread fermentation monitoring through NIR spectroscopy and PLS-DA. Determining the optimal fermentation point in bread doughs - D. Castro-Reigía; I. García; S. Sanllorente; L.A. Sarabia; J.M. Amigo; M.C. Ortiz (Journal of Food Engineering, 2024)

The terroir of Brazilian Coffea canephora: Characterization of the chemical composition - Bárbara Zani Agnoletti; Lucas Louzada Pereira; Enrique Anastácio Alves; Rodrigo Barros Rocha; Danieli Gracieri Debona; Marcos Valério Vieira Lyrio; Taís Rizzo Moreira; Eustáquio Vinicius Ribeiro de Castro; Emanuele Catarina da S. Oliveira; Paulo Roberto Filgueiras (Food Research International, 2024)

Improvement in Sunlight-Irradiated Photocatalytic Activity and Stability of Ca10(PO4)6(OH)2/g-C3N4 for Dye Mixture Degradation - Mário A. M. Castro; José Victor S. Galvão; Débora F. S. Morais; Marcio D. Teodoro; Ricardo P. Souza; Maurício R. D. Bomio; Fabiana V. Motta (Water, Air, & Soil Pollution, 2024)

Hydrometeors Distribution in Intense Precipitating Cloud Cells Over the Earth’s During Two Rainfall Seasons - Shailendra Kumar; Jose Luis Flores‑Rojas; Aldo S. Moya-Álvarez; Daniel Martínez-Castro; Yamina Silva (Journal of the Indian Society of Remote Sensing, 2024)

Removing color while lowering toxicity: the case for decolorization of textile dyes and simulated effluents with yeasts - M. Mendes; A. C. Cassoni; S. Alves; P. Moreira; M. E. Pintado; P. M. L. Castro (International Journal of Environmental Science and Technology, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Modeling the interannual variability in Maipo and Rapel river plumes off central Chile - Julio Salcedo-Castro; Antonio Olita; Freddy Saavedra; Gonzalo S. Saldías; Raúl C. Cruz-Gómez; Cristian D. De la Torre Martínez (Ocean Science, 2023)
River plumes have a direct influence on coastal environments, impacting coastal planktonic and benthic communities, including fishery resources. In general, the main drivers of river plume dynamics are the river discharge and the alongshore wind stress, whereas the tides and topography play a secondary role. In central Chile, rivers flowing into the eastern Pacific have a relatively short path on land, with a high slope and a mixed snow–rain regime. This study aims to understand the interannual variability in the plumes of the Maipo and Rapel rivers in the coastal/shelf area off central Chile and their influence on local ocean dynamics. We used the Coastal and Regional Ocean Community (CROCO) model, with 1 km horizontal resolution and 20 sigma levels, to simulate the ocean dynamics for the period 2003–2011. The results show that the plume's area coverage and coastal ocean salinity are strongly correlated with the river discharges. The predominant northeastward winds control the plumes' orientation toward the northwest. However, episodes of southeastward winds in winter can reverse the plumes' direction, promoting their attachment to the coast and southward transport. Results also show a salification trend linked to the severe droughts hitting central Chile during the studied period. This salification determines a change in local dynamics which could be more frequent in future scenarios of climate change with a significant lack of rain and river discharges along central Chile.

Quantification of soil N2O and CH4 fluxes using the flux gradient method on a drainage water managed farm on the eastern shore of Maryland - Qiurui Zhu; Eric A. Davidson; Jacob G. Hagedorn; Mark S. Castro; Thomas R. Fisher; Rebecca J. Fox; Shannon E. Brown; James W. Lewis (Agricultural and Forest Meteorology, 2023)

Who are the superhosts? The chemical and structural profiles of superhosts of galling arthropods and the gaps in gall studies - Gabriela S. Martins; Leticia P. Nobrega; Rayssa R. M. Castro; Filipe R. Valeriano; Leonardo G. Sant’Anna; Pedro E. F. Barbosa; Bruno G. Ferreira (Arthropod-Plant Interactions, 2023)

Long‐term observed changes of air temperature, relative humidity and vapour pressure deficit in Bolivia, 1950–2019 - B. Fernández‐Duque; S. M. Vicente‐Serrano; O. Maillard; F. Domínguez‐Castro; D. Peña‐Angulo; I. Noguera; C. Azorin‐Molina; A. El Kenawy (International Journal of Climatology, 2023)
This study analyzes the long‐term observed changes of mean (Tmean), maximum (Tmax) and minimum (Tmin) air temperatures, relative humidity (RH) and vapour pressure deficit (VPD) at different elevation ranges across Bolivia from 1950 to 2019. The linear trends in air temperature series present a significant increase, with no substantial seasonal or spatial differences. On an annual basis, RH exhibited a non‐significant decrease (−0.08% decade −1 ), while VPD showed a significant increase (0.01 hPa decade −1 ) ( p

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Results from the Radiation Assessment Detector on the International Space Station: Part 3, combined results from the CPD and FND - C. Zeitlin; A.J. Castro; K.B. Beard; B.M. Hayes; M. Abdelmelek; D. Laramore; A.S. Johnson; N. Stoffle; R.F. Wimmer-Schweingruber; S. Löffler; R.R. Rios (Life Sciences in Space Research, 2023)

Encephalic meningioangiomatosis in a dog with high-grade undefined glioma - Brenda O. Silveira; Stella M.P. de Melo; Fernanda G. Cony; Guilherme C. Serena; Vanessa de C. Pereira; Lucas T. de Castro; Vitória S. Wodzik; Marcele B. Bandinelli; Welden Panziera; Saulo P. Pavarini (Journal of Comparative Pathology, 2023)

Reduced flow model and transmissibility upscaling in multi-layered faulted reservoirs - Eduardo S. Castro; Josué S. Barroso; Marcio A. Murad; João N.C. Guerreiro (Computers & Geosciences, 2023)

Hepatocellular carcinoma induced by hepatocyte Pten deletion reduces BAT UCP-1 and thermogenic capacity in mice, despite increasing serum FGF-21 and iWAT browning - Álbert S. Peixoto; Mayara F. Moreno; Érique Castro; Luiz A. Perandini; Thiago Belchior; Tiago E. Oliveira; Thayna S. Vieira; Gustavo R. Gilio; Caroline A. Tomazelli; Bianca F. Leonardi; Milene Ortiz-Silva; Luciano P. Silva Junior; et al. (Journal of Physiology and Biochemistry, 2023)

Whose values count? A review of the nature valuation studies with a focus on justice - M Schaafsma; S Ahn; AJ Castro; N Dendoncker; A Filyushkina; D González-Jiménez; Mariaelena Huambachano; N Mukherjee; TH Mwampamba; J Ngouhouo-Poufoun; I Palomo; R Pandit; et al. (Current Opinion in Environmental Sustainability, 2023)

Key Stress Response Mechanisms of Probiotics During Their Journey Through the Digestive System: A Review - Cecilia Castro-López; Haydee E. Romero-Luna; Hugo S. García; Belinda Vallejo-Cordoba; Aarón F. González-Córdova; Adrián Hernández-Mendoza (Probiotics and Antimicrobial Proteins, 2023)

An enhancement in the management practices of geoduck clam Panopea globosa: The estimation of reference points in the short and long term - Estefani Larios-Castro; Enrique Morales-Bojórquez; Sergio S. González Peláez; Juan Gabriel Díaz-Uribe; Marlene A. Luquin-Covarrubias; Héctor Villalobos (Ocean & Coastal Management, 2023)

P21-22: Evaluation of the neurotoxicity and electrophysiological effect of new ixodicidal carbamates in a murine model - A. G. Martínez González; S. M. Gómez Castro; J. F. Lazcano Reyes; V. Vázquez Valadez; M. Muñoz Guzmán; E. Angeles; F. Alba Hurtado; M. G. Prado Ochoa (Toxicology Letters, 2023)

P21-13: Evaluation of neurotoxicity induced by new generation carbamates in domestic animals - S. M. Gómez Castro; G. A. Martínez González; A. M. Velázquez Sanchez; C. Cuenca Verde; E. Angeles; V. H. Vázquez Valadez; F. Alba Hurtado; M. G. Prado Ochoa (Toxicology Letters, 2023)

An Inter-professional Plant-based Culinary Medicine Program for Nutrition and Medical Students - L. Castro; S. Joshi; M. McMacken; K. Woolf (Journal of the Academy of Nutrition and Dietetics, 2023)

Place-based solutions for global social-ecological dilemmas: An analysis of locally grounded, diversified, and cross-scalar initiatives in the Amazon - Marina Londres; Carl Salk; Krister P. Andersson; Maria Tengö; Eduardo S. Brondizio; Gabriela Russo Lopes; Sacha M.O. Siani; Adriana Molina-Garzón; Taís Sonetti-González; Diego Rázuri Montoya; Célia Futemma; Fábio de Castro; et al. (Global Environmental Change, 2023)

Sustainable bioethanol production from first- and second-generation sugar-based feedstocks: Advanced bibliometric analysis - Cláudia Elisa César Guimarães; Francisco Simão Neto; Viviane de Castro Bizerra; Jean Gleison Andrade do Nascimento; Roberta Bussons Rodrigues Valério; Paulo Gonçalves de Sousa Junior; Ana Kátia de Sousa Braz; Rafael Leandro Fernandes Melo; Juliana de França Serpa; Rita Karolinny Chaves de Lima; Artemis Pessoa Guimarães; Maria Cristiane Martins de Souza; et al. (Bioresource Technology Reports, 2023)

Gelatin-based films incorporated with buriti oil (Mauritia flexuosa L.) as active packaging for artisanal cheese conservation - Heriberto A. Anjos; Domingos A.M. Castro; Agenor G. dos Santos-Neto; Jefferson Romáryo Duarte da Luz; Maria das Graças Almeida; Maria Terezinha S. Leite Neta; Narendra Narain; Alessandra A.C. Pagani; Elton Franceschi; Maria Lucila Hernández-Macedo; Jorge A. López (Bioresource Technology Reports, 2023)

Varietal response to soybean target spot (Corynespora cassiicola) in the Brazilian Neotropical Savannah - Érica de Castro Costa; Justino J. Dias-Neto; Lincoln V. A. S. Bizerra; Nédio Tormen; Pierce A. Paul; Adalberto C. Café-Filho (Phytoparasitica, 2023)

Geometric morphometrics as a tool to identify Dasypodini osteoderms: Implications for the oldest records of Dasypus - Juan S. Salgado-Ahumada; Marcos D. Ercoli; Alicia Álvarez; Mariela C. Castro; Martín R. Ciancio (Journal of Mammalian Evolution, 2023)

Potential probiotic lactobacilli strains isolated from artisanal Mexican Cocido cheese: evidence-based biosafety and probiotic action-related traits on in vitro tests - Cecilia Castro-López; Alfonso García-Galaz; Hugo S. García; Aarón F. González-Córdova; Belinda Vallejo-Cordoba; Adrián Hernández-Mendoza (Brazilian Journal of Microbiology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Geochemical mapping by stream sediments of the NW portion of Quadrilátero Ferrífero, Brazil: Application of the exploratory data analysis (EDA) and a proposal for generation of new gold targets in Pitangui gold district - Eduardo Duarte Marques; Cassiano Costa Castro; Renato de Assis Barros; Júlio César Lombello; Marcelo de Souza Marinho; Joanna Chaves S. Araújo; Everton A.M. Santos (Journal of Geochemical Exploration, 2023)

Dereplication of Siparuna brasiliensis extract with in vivo anti-inflammatory activity - Leandro A. Castro; Nerilson M. Lima; Gracimério J. Guarneire; Gabriela P. Carli; Allyne Aparecida S. Castro; Teresinha de Jesus A. S. Andrade; Sandra B. R. Castro; Boniek Gontijo Vaz; Caio Cesar S. Alves; Alessandra P. Carli (Natural Product Research, 2023)

Exploring the prevalence and antibiotic resistance profile of Klebsiella pneumoniae and Klebsiella oxytoca isolated from clinically ill companion animals from North of Portugal - D. Araújo; J. Castro; F. Matos; R. Oliveira; C. Ramos; C. Almeida; S. Silva (Research in Veterinary Science, 2023)

Contribution of TGFß and of a cocktail of TGFß and the pro-inflammatory cytokines IL-1, IL- 6 and TNFα to the establishment of a fibrotic phenotype in endometrial fibroblasts of mares - Yat S. Wong; Pamela Poblete; Lidice Mendez; Ana C. Mancanares; Lleretny Rodriguez-Alvarez; Fernando E. Saravia; Fidel O. Castro (Journal of Equine Veterinary Science, 2023)

Molecular detection of Burkholderia mallei in different geographic regions of Brazil - Paula A. Pereira Suniga; Cynthia Mantovani; Maria G. Santos; Juliana S. Gomes Rieger; Emanuelle B. Gaspar; Fernando Leandro dos Santos; Rinaldo A. Mota; Karla P. Chaves; Andréa A. Egito; José Carlos O. Filho; Alessandra F. Castro Nassar; Lenita Ramires dos Santos; et al. (Brazilian Journal of Microbiology, 2023)

Assessment of virus concentration methods for detecting SARS-CoV-2 IN wastewater - André V. C. Ribeiro; Camille F. Mannarino; Eduardo S. G. de Castro; Tatiana Prado; Fernando C. Ferreira; Tulio M. Fumian; Marize P. Miagostovich (Brazilian Journal of Microbiology, 2023)

Assessing high quality agricultural lands through the ecosystem services lens: Insights from a rapidly urbanizing agricultural region in the western United States - Sarah Halperin; Antonio J. Castro; Cristina Quintas-Soriano; Jodi S. Brandt (Agriculture, Ecosystems & Environment, 2023)

Quantification of Wood Biomass in an Area of Sustainable Annual Production in the Brazilian Semiarid Region Aiming at Generating Renewable Energy - R. C. Santos; F. G. C. Pareyn; C. P. S. Santos; D. Minini; S. M. G. Rocha; F. J. O. Souza; L. F. C. Cezario; A. F. Dias Júnior; R. V. O. Castro (BioEnergy Research, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Sulfolipid substitution ratios of Microcystis aeruginosa and planktonic communities as an indicator of phosphorus limitation in Lake Erie - Robbie M. Martin; Maddie K. Denney; Helena L. Pound; Justin D. Chaffin; George S. Bullerjahn; R. Michael L. McKay; Arthur Zastepa; Katarina A. Jones; Hector F. Castro; Shawn R. Campagna; Steven W. Wilhelm (Limnology and Oceanography, 2023)
Phosphorus (P) availability frequently limits primary production in lakes, influences the physiology of phytoplankton, shapes community structure, and can stimulate or constrain the formation of cyanobacterial blooms. Given the importance of P, numerous methods are available to assess P stress in phytoplankton communities. Marine phytoplankton are known to substitute sulfolipids for phospholipids in response to P limitation. We asked whether sulfolipid substitution might serve as an additional indicator of P stress in freshwater phytoplankton communities. The question was addressed using cultures of Microcystis aeruginosa , Lake Erie microcosms, and surveys of lipid profiles in Lake Erie during a Microcystis spp. bloom. Peak area response ratios of the intact polar lipids sulfoquinovosyldiacylglycerol (SQDG) to phosphatidylglycerol (PG) were used as the metric of lipid substitution. In cultures of M. aeruginosa NIES‐843, the SQDG : PG ratio increased from ~ 0.9 to ~ 3.3 with decreasing P concentration. In P‐limited communities, the SQDG : PG ratio increased from ~ 6 to ~ 11 after 48 h in microcosm controls, while P amendments reduced the ratio to ~ 3. In Lake Erie surveys, the SQDG : PG ratio ranged from ~ 0.4 to ~ 7.4 and was negatively correlated (Pearson r = −0.62) with total dissolved P. The SQDG : PG ratio was not correlated with concentrations of chlorophyll a , soluble reactive P, or N : P molar ratios. These results demonstrated that M. aeruginosa and Microcystis ‐dominated communities remodel lipid profiles in response to P scarcity, providing a potential short‐term, time‐integrated biomarker of nutrient history and P stress in fresh waters.

Assessment of eutrophication from phosphorus remobilization after resuspension of coastal sediments from an urban tropical estuary - Christiane do N. Monte; Ana Paula de Castro Rodrigues; Matheus Cavalcante Silva; Luana J. S. Ferreira; Gustavo Monte; Carla Semiramis Silveira; Renato Campello Cordeiro; Wilson Machado (Environmental Science and Pollution Research, 2023)

Metabolic profiling by LC-DAD-MS, FTIR, NMR and CE-UV of polyphenols with potential against skin pigmentation disorder - Isac H. Cordeiro; Nerilson M. Lima; Elaine C. Scherrer; Gabriela P. Carli; Teresinha de Jesus A. S. Andrade; Sandra B. R. Castro; Marcone A. L. de Oliveira; Caio Cesar S. Alves; Alessandra P. Carli (Natural Product Research, 2023)

Bioremediation of coastal aquaculture effluents spiked with florfenicol using microalgae-based granular sludge – a promising solution for recirculating aquaculture systems - Ana S. Oliveira; Marta Alves; Frederico Leitão; Marta Tacão; Isabel Henriques; Paula M.L. Castro; Catarina L. Amorim (Water Research, 2023)

Bioaccessibility of glucosinolates, isothiocyanates and inorganic micronutrients in cruciferous vegetables through INFOGEST static in vitro digestion model - J. Martínez-Castro; A. de Haro-Bailón; S. Obregón-Cano; I.Mª. García Magdaleno; A. Moreno Ortega; F. Cámara-Martos (Food Research International, 2023)

Penicillium amapaense sp. nov., section Exilicaulis, and new records of Penicillium labradorum in Brazil isolated from Amazon River sediments with potential applications in agriculture and biotechnology - Ingride Jarline S. da Silva; Thiago F. Sousa; Claudia Afras de Queiroz; Gleucinei dos Santos Castro; Fernanda F. Caniato; Lívia S. de Medeiros; Célio F. F. Angolini; Rogério E. Hanada; Hector Henrique Ferreira Koolen; Gilvan Ferreira da Silva (Mycological Progress, 2023)

Acaricidal action of ozone on larvae and engorged females of Rhipicephalus microplus: a dose-dependent relationship - R. A. Castro; O. P. Neto; A. L. S. Mendes; L. H. Moreira (Experimental and Applied Acarology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Characteristics of cloud properties over South America and over Andes observed using CloudSat and reanalysis data - Shailendra Kumar; Jose Luis Flores; Aldo S. Moya-Álvarez; Daniel Martinez-Castro; Yamina Silva (International Journal of Remote Sensing, 2023)

Pathological Aspects and Immunohistochemical Evaluation of Troponin C in the Cardiovascular System of Dogs With Pheochromocytoma - Fernando F. Argenta; Mônica Slaviero; Lauren S. de Mello; Joanna V.Z. Echenique; Alexia A. Zorzan; Fernanda G. Cony; Marcele B. Bandinelli; Márcio B. de Castro; Saulo P. Pavarini; David Driemeier; Luciana Sonne (Topics in Companion Animal Medicine, 2023)

Characterization of proteases in the seminal plasma and spermatozoa of llama - L. Sari; X. Castro-González; R. Zampini; S. Apichela; M. Ratto; M. Argañaraz (Theriogenology, 2023)

Bovine embryos release extracellular vesicles with differential miRNA signature during the compaction and blastulation stages - Bárbara Melo-Báez; Edwin A. Mellisho; Yat S. Wong; Joel Cabezas; Diego Caamaño; Constanza Aguilera; Gonzalo Riadi; Fidel O. Castro; Lleretny Rodriguez-Alvarez (Reproductive Biology, 2023)

Changing risk of arboviral emergence in Catalonia due to higher probability of autochthonous outbreaks - L. López; C. Dommar; A. San José; L. Meyers; S. Fox; L. Castro; X. Rodó (Ecological Modelling, 2023)

Losartan impairs HTR-8/SVneo trophoblast migration through inhibition of angiotensin II-induced pro-inflammatory profile in human endometrial stromal cells - Rosario Macchi; Agustina D. Sotelo; Andrea C. Parrado; Luciana S. Salaverry; Guillermo A. Blanco; Marisa S. Castro; Estela B. Rey-Roldán; Andrea M. Canellada (Toxicology and Applied Pharmacology, 2023)

Inflammatory stimulus worsens the effects of UV-A exposure on J774 cells - Orlando Chiarelli-Neto; Michelle Lima Garcez; Christiane Pavani; Waleska Martins; Fernanda Cristina de Abreu Quintela Castro; Roberta Passamani Ambrosio; Flavia Carla Meotti; Mauricio S. Baptista (Journal of Photochemistry and Photobiology B: Biology, 2023)

New applications of an old individual-based model for biological dynamics - Fabíola Keesen; Alcides Castro e Silva; Carlos Felipe S. Pinheiro; Everaldo Arashiro; Yan Ligeiro; Carlos Eduardo de Viveiros Grelle (Ecological Modelling, 2023)

Population dynamics and movements of Atlantic tarpon, Megalops atlanticus, in the Parnaíba Delta Protected Area, Brazil: challenges for local fishery management planning - Cezar A. F. Fernandes; Francisca E. A. Cunha; Carlos E. L. S. Silva; Alan C. S. Araújo; Rafael L. Pereira; Daniel F. Viana; Werlanne M. S. Magalhães; M. A. P. Gondolo; Daniel M. P. de Castro; Aaron Adams; Jiangang Luo; Jerald S. Ault; et al. (Environmental Biology of Fishes, 2023)

Influence of pigeon pea (Cajanus cajan) on oviposition behaviour of Diceraeus melacanthus stink bug, an important pest of soybean and maize crops in South America - M. Borges; M. F. F. Michereff; R. A. Laumann; G. T. Santana; B. S. Castro; C. C. Silva; M. C. Blassioli-Moraes (Arthropod-Plant Interactions, 2023)

Assessment of the impact of the bus fleet and transportation infrastructure works on the air quality in Rio de Janeiro (Olympic Games 2016) - Elizanne P. S. Justo; Maria Fernanda Cáceres Quijano; Karmel Beringui; Luciana Baptista Ventura; Guilherme Martins Pereira; Pérola de Castro Vasconcellos; Adriana Gioda (Air Quality, Atmosphere & Health, 2023)

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Metabolomics during the spontaneous fermentation in cocoa (Theobroma cacao L.): An exploraty review - César R. Balcázar-Zumaeta; Efraín M. Castro-Alayo; Ilse S. Cayo-Colca; Guillermo Idrogo-Vásquez; Lucas D. Muñoz-Astecker (Food Research International, 2023)

A global analysis of viviparity in squamates highlights its prevalence in cold climates - Anna Zimin; Sean V. Zimin; Richard Shine; Luciano Avila; Aaron Bauer; Monika Böhm; Rafe Brown; Goni Barki; Gabriel Henrique de Oliveira Caetano; Fernando Castro Herrera; David G. Chapple; Laurent Chirio; et al. (Global Ecology and Biogeography, 2022)
Aim Viviparity has evolved more times in squamates than in any other vertebrate group; therefore, squamates offer an excellent model system in which to study the patterns, drivers and implications of reproductive mode evolution. Based on current species distributions, we examined three selective forces hypothesized to drive the evolution of squamate viviparity (cold climate, variable climate and hypoxic conditions) and tested whether viviparity is associated with larger body size. Location Global. Time period Present day. Taxon Squamata. Methods We compiled a dataset of 9061 squamate species, including their distributions, elevation, climate, body mass and reproductive modes. We applied species‐level and assemblage‐level approaches for predicting reproductive mode, both globally and within biogeographical realms. We tested the relationships of temperature, interannual and intra‐annual climatic variation, elevation (as a proxy for hypoxic conditions) and body mass with reproductive mode, using path analyses to account for correlations among the environmental predictors. Results Viviparity was strongly associated with cold climates at both species and assemblage levels, despite the prevalence of viviparity in some warm climates. Viviparity was not clearly correlated with climatic variability or elevation. The probability of being viviparous exhibited a weak positive correlation with body size. Conclusions Although phylogenetic history is important, potentially explaining the occurrence of viviparous species in regions that are warm at present, current global squamate distribution is characterized by a higher relative abundance of viviparity in cold environments, supporting the prediction of the “cold‐climate” hypothesis. The roles of climatic variation and hypoxia are less important and not straightforward. Elevation probably exerts various selective pressures and influences the prevalence of viviparity primarily through its effect on temperature rather than on oxygen concentration.

Assessing bias in aerial surveys for cetaceans: Results from experiments conducted with the franciscana dolphin - Federico Sucunza; Daniel Danilewicz; Artur Andriolo; Franciele R. de Castro; Marta Cremer; Pablo Denuncio; Emanuel Ferreira; Paulo A. C. Flores; Paulo H. Ott; Martin S. Perez; Dan Pretto; Camila M. Sartori; et al. (Frontiers in Marine Science, 2022)
Line transect aerial surveys are widely used for estimating abundance of biological populations, including threatened species. However, estimates obtained with data collected from aircraft are often underestimated because of visibility bias and bias in estimating group sizes from a fast-moving platform. An assessment of multiple sources of bias in aerial surveys were carried out in Brazilian coastal waters by experiments on multiple survey platforms (i.e., boat, airplane and helicopter). These studies focused on evaluating visibility bias (perception and availability bias) and potential differences in the estimation of group sizes from different types of platforms used in franciscana ( Pontoporia blainvillei ) abundance surveys. The ultimate goal was to develop correction factors to improve accuracy of estimates of density and population size for this threatened dolphin. Estimates of density and group sizes computed from boats were assumed to be unbiased and were compared to estimates of these quantities obtained from an airplane in the same area and period. In addition, helicopter surveys were conducted in two areas where water turbidity differed (clear vs. murky waters) to determine surfacing-diving intervals of franciscana groups and to estimate availability for aerial platforms. Abundance computed from the aerial survey data underestimated the true abundance by about 4-5 times, with ~70% of the total bias resulting from visibility bias (~80% from availability bias and ~20% from perception bias) and ~30% from bias in estimates of group size. The use of multiple survey platforms in contrasting habitats provided the opportunity to compute correction factors that can be used to refine range wide abundance estimates of the threatened franciscana given certain assumptions are met. Visibility bias and group size bias were substantial and clearly indicate the importance for accounting for such correction factors to produce unequivocal population assessment based on aerial survey data.

Biosynthetic studies through feeding experiments in Eclipta prostrata (L.) L. hairy roots - Adriana A. Lopes; Giuliana R. S. Souza; Suzelei de Castro França; Miriam V. Lourenço (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Use of a recombinant positive control in the diagnostic of canine Ehrlichiosis from 16sRNA gen of Ehrlichia canis in Mexico City - S. E. Acevedo-Monroy; J. M. Méndez-Alemán; I. Castro-Mendoza; M. A. Mojica-Sánchez; A. Verdugo-Rodríguez (Archives of Microbiology, 2022)

Performance of Sentinel-2 SAFER ET model for daily and seasonal estimation of grapevine water consumption - Anderson L. S. Safre; Ayman Nassar; Alfonso Torres-Rua; Mayhar Aboutalebi; João C. C. Saad; Rodrigo L. Manzione; Antonio Heriberto de Castro Teixeira; John H. Prueger; Lynn G. McKee; Joseph G. Alfieri; Lawrence E. Hipps; Hector Nieto; et al. (Irrigation Science, 2022)

Effects of meteorological and land surface modeling uncertainty on errors in winegrape ET calculated with SIMS - Conor T. Doherty; Lee F. Johnson; John Volk; Meagan S. Mauter; Nicolas Bambach; Andrew J. McElrone; Joseph G. Alfieri; Lawrence E. Hipps; John H. Prueger; Sebastian J. Castro; Maria Mar Alsina; William P. Kustas; et al. (Irrigation Science, 2022)
Characterization of model errors is important when applying satellite-driven evapotranspiration (ET) models to water resource management problems. This study examines how uncertainty in meteorological forcing data and land surface modeling propagate through to errors in final ET data calculated using the Satellite Irrigation Management Support (SIMS) model, a computationally efficient ET model driven with satellite surface reflectance values. The model is applied to three instrumented winegrape vineyards over the 2017–2020 time period and the spatial and temporal variation in errors are analyzed. We illustrate how meteorological data inputs can introduce biases that vary in space and at seasonal timescales, but that can persist from year to year. We also observe that errors in SIMS estimates of land surface conductance can have a particularly strong dependence on time of year. Overall, meteorological inputs introduced RMSE of 0.33–0.65 mm/day (7–27%) across sites, while SIMS introduced RMSE of 0.55–0.83 mm/day (19–24%). The relative error contribution from meteorological inputs versus SIMS varied across sites; errors from SIMS were larger at one site, errors from meteorological inputs were larger at a second site, and the error contributions were of equal magnitude at the third site. The similar magnitude of error contributions is significant given that many satellite-driven ET models differ in their approaches to estimating land surface conductance, but often rely on similar or identical meteorological forcing data. The finding is particularly notable given that SIMS makes assumptions about the land surface (no soil evaporation or plant water stress) that do not always hold in practice. The results of this study show that improving SIMS by eliminating these assumptions would result in meteorological inputs dominating the error budget of the model on the whole. This finding underscores the need for further work on characterizing spatial uncertainty in the meteorological forcing of ET.

Inter-annual variability of land surface fluxes across vineyards: the role of climate, phenology, and irrigation management - N. Bambach; W. Kustas; J. Alfieri; F. Gao; J. Prueger; L. Hipps; L. McKee; S. J. Castro; M. M. Alsina; A. J. McElrone (Irrigation Science, 2022)
Irrigation and other agricultural management practices play a key role in land surface fluxes and their interactions with atmospheric processes. California’s Central Valley agricultural productivity is strongly linked to water availability associated with conveyance infrastructure and groundwater, but greater scrutiny over agricultural water use requires better practices particularly during extended and severe drought conditions. The future of irrigated agriculture in California is expected to be characterized neither by perpetual scarcity nor by widespread abundance. Thus, further advancing irrigation technologies and improving management practices will be key for California’s agriculture sustainability. In this study, we present micrometeorological observations from the Grape Remote Sensing Atmospheric Profile and Evapotranspiration eXperiment (GRAPEX) project. Daily, seasonal, and inter-seasonal surface flux patterns and relationships across five vineyards over three distinct California wine production regions were investigated. Vineyard actual evapotranspiration showed significant differences at the sub-daily and daily scale when comparisons across wine production regions and varieties were performed. Water use in vineyards in the Central Valley was about 70% greater in comparison to the vineyards at the North Coast area due to canopy size, atmospheric demand, and irrigation inputs. Inter-annual variability of surface fluxes was also significant, even though, overall weather conditions (i.e., air temperature, vapor pressure deficit, wind speed, and solar radiation) were not significantly different. Thus, not only irrigation but also other management practices played a key role in seasonal water use, and given these differences, we conclude that further advancing ground-based techniques to quantify crop water use at an operational scale will be key to facing California’s agriculture present and future water challenges.

Evapotranspiration uncertainty at micrometeorological scales: the impact of the eddy covariance energy imbalance and correction methods - N. Bambach; W. Kustas; J. Alfieri; J. Prueger; L. Hipps; L. McKee; S. J. Castro; J. Volk; M. M. Alsina; A. J. McElrone (Irrigation Science, 2022)
Under ideal conditions, evapotranspiration ( ET ) fluxes derived through the eddy covariance (EC) technique are considered a direct measure of actual ET . Eddy covariance flux measurements provide estimates at a temporal frequency that allows examining sub-daily, daily, and seasonal scale processes and relationships between different surface fluxes. The Grape Remote Sensing Atmospheric Profile and Evapotranspiration eXperiment (GRAPEX) project has collected micrometeorological and biophysical data to ground-truth new remote sensing tools for fine-tuning vineyard irrigation management across numerous sites since 2013. This rich dataset allows us to quantify the impact of different approaches to estimate daily ET fluxes, while accounting for energy imbalance. This imbalance results from the lack of agreement between the total available energy and turbulent fluxes derived by the EC technique. We found that different approaches to deal with this energy imbalance can lead to uncertainty in daily ET estimates of up to 50%. Over the growing season, this uncertainty can lead to considerable biases in crop water use estimates, which in some cases were equivalent to ~ 1/3rd of the total growing season applied irrigation We analyzed ET uncertainty relative to atmospheric meteorological, stability, and advective conditions, and highlight the importance of recognizing limitations of micrometeorological observational techniques, considered state of the art, to quantify ET for model validation and field-scale monitoring. This study provides a framework to quantify daily ET estimates’ uncertainty and expected reliability when using the eddy covariance technique for ground-truthing or model validation purposes.

Older adults’ episodic memory is related to a neurophysiological marker of brain cholinergic activity - Patrick S. R. Davidson; Galit Karpov; Lauriane Giguère; Alex W. Castro; François Tremblay (Experimental Brain Research, 2022)

Women and adaptive capacity to climate change in East African seascapes – Zanzibar as an example - Maricela de la Torre-Castro; Lars Lindström; Narriman S. Jiddawi; Felicity Pike; Astrid Max (Frontiers in Marine Science, 2022)
As the climate crisis persists, there is a crucial need to increase knowledge on adaptive capacity and the underlying factors building it. This is particularly important for disadvantaged groups, such as coastal women in East Africa. Women’s livelihoods in these seascapes are and will be more severely affected by climate change and the capacity of East African states to deal with these challenges is limited in terms of financial and human capital. In this research, we investigated the underlying factors building the adaptive capacity of coastal women in Zanzibar (Unguja Island), Tanzania. Coastal women (N=117) were interviewed in villages around the island to gather information about potential factors supporting adaptive capacity. This was analysed applying Cinner et al (2018) five domains typology for adaptive capacity, i.e. assets, flexibility, organizations, learning and agency. The results show that women had relatively low adaptive capacity, extended poverty and very high dependence on seaweed farming of red algae, a livelihood providing low income and already being seriously affected by climate variability and change. Women’s observations of key variables related to environmental changes corresponded to most scientific findings. It was, however, unclear how that knowledge is useful and enhances adaptive capacity. Adaptive capacity was generally low but individual differences were found in which ten women had a high income. The results show that the factors underlying adaptive capacity are complex and interact with each other, being positive, negative and unclear. Many of the identified factors deserve future research. This study adds to the pool of knowledge by addressing women (not only men); coastal ecosystems (as land and freshwater systems are more studied) and the individual level (since most studies focus on national and community levels). The study illustrates that institutional renewal, bridging and cooperation is possible in Zanzibar bringing good news to the region.

Morita–Baylis–Hillman adducts derived from thymol: synthesis, in silico studies and biological activity against Giardia lamblia - Francisco J. S. Xavier; Andressa B. Lira; Gabriel C. Verissimo; Fernanda S. de S. Saraiva; Abrahão A. de Oliveira Filho; Elaine M. de Souza-Fagundes; Margareth de F. F. M. Diniz; Maria A. Gomes; Aleff C. Castro; Fábio P. L. Silva; Claudio G. Lima-Junior; Mário L. A. A. Vasconcellos (Molecular Diversity, 2022)

Attitudes of Filipino parents of children with Down syndrome on noninvasive prenatal testing - Leniza G. de Castro-Hamoy; Ma-am Joy R. Tumulak; Maria Stephanie Fay S. Cagayan; Peter A. Sy; Nona Rachel C. Mira; Mercy Y. Laurino (Journal of Community Genetics, 2022)

Physicochemical and computational analysis of the melamine resin derivative for the glyphosate absorption from water using Langmuir-type model - L. Morales-Quintana; D. Bustos; J. Gallego; O. Valdes; L. Guzmán; F. M. Nachtigall; A. Marican; E. W. Hernández-Rodríguez; F. Avila-Salas; W. Bueno-Silva; L. S. Santos; R. I. Castro (International Journal of Environmental Science and Technology, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Behavioral Response of the Leaf-Cutting Ant Atta cephalotes (Hymenoptera: Formicidae) to Trichoderma sp. - K. M. Cotazo-Calambas; Andrea Niño-Castro; S. M. Valencia-Giraldo; J. S. Gómez-Díaz; J. Montoya-Lerma (Journal of Insect Behavior, 2022)

Movements of Hatchery-Reared Dusky Groupers Released in a Northeast Atlantic Coastal Marine Protected Area - Ana Filipa Silva; Bárbara Horta e Costa; José Lino Costa; Esmeralda Pereira; João Pedro Marques; João J. Castro; Pedro G. Lino; Ana Candeias-Mendes; Pedro Pousão-Ferreira; Inês Sousa; Luís Bentes; Jorge M. S. Gonçalves; et al. (Journal of Marine Science and Engineering, 2022)
No-take areas are key instruments to promote the effectiveness of Marine Protected Areas (MPAs), particularly concerning the protection of endangered species such as the dusky grouper (Epinephelus marginatus). However, despite the establishment of no-take areas and the prohibition of catching this species in a southwestern Portuguese MPA (SACVMP—‘Sudoeste Alentejano’ and ‘Costa Vicentina’ Marine Park) since 2011, there is still no evidence of population recovery. By using acoustic biotelemetry, this work aimed to evaluate the feasibility of restocking hatchery-reared adult dusky groupers in two no-take areas within the SACVMP. In 2019 and 2021, thirty groupers were tagged with acoustic transmitters and the site attachment and movements of the groupers were assessed in the releasing sites (no-take areas). None of the tagged fish settled down in either of the areas, leaving the no-take areas mainly at dusk and night. Some individuals displayed extended movements of more than a hundred kilometers along the Portuguese coast which was rarely reported for this species. At least in some coastal stretches, those movements were performed close to the shore, which may evidence the importance of coastal MPAs to protect and promote the connectivity of species more associated with rocky reef habitats. Following studies should focus on the conditions that promote site attachment and fidelity by hatchery-reared dusky groupers so that future large-scale restocking programs can be successful in MPAs with appropriate habitats.

Setting Performance Indicators for Coastal Marine Protected Areas: An Expert-Based Methodology - Mariana Cardoso-Andrade; Henrique Queiroga; Mafalda Rangel; Inês Sousa; Adela Belackova; Luís Bentes; Frederico Oliveira; Pedro Monteiro; Nuno Sales Henriques; Carlos M. L. Afonso; Ana F. Silva; Bernardo R. Quintella; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) require effective indicators to assess their performance, in compliance with the goals of relevant national and international commitments. Achieving and prioritizing shortlists of multidisciplinary indicators demands a significant effort from specialists to depict the multiple conservation and socioeconomic interests, and the large complexity of natural systems. The present paper describes a structured expert-based methodology (process and outputs) to co-define a list of multidisciplinary MPA performance indicators. This work was promoted by the management authority of coastal MPAs in mainland Portugal to gather a consensual and feasible list of indicators that would guide the design of a future national monitoring program. Hence, Portuguese coastal MPAs served as a case study to develop such a process between 2019 and 2020. In the end, participants (1) agreed on a shortlist of prioritized indicators ( i.e. , environmental, governance, and socioeconomic indicators) and (2) defined minimum monitoring frequencies for the indicators in this list, compatible with the potential replicability of the associated survey methods. The present approach recommends that management plans incorporate monitoring procedures and survey methods, with a validated list of indicators and associated monitoring periodicity, agreed among researchers, MPA managers and governance experts. The proposed methodology, and the lessons learned from it, can support future processes aiming to define and prioritize MPA performance indicators.

Actinobacteria isolated from wastewater treatment plants located in the east-north of Algeria able to degrade pesticides - Oumeima Boufercha; Irina S. Moreira; Paula M. L. Castro; Allaoueddine Boudemagh (World Journal of Microbiology and Biotechnology, 2022)

Mapping Lioz Limestone in Monuments at Rio de Janeiro, Brazil - Amanda G. S. Mozer; Nuria F. Castro; Kátia L. Mansur; Roberto Carlos C. Ribeiro (Geoheritage, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Review: Hydrogeology of Northern Mendoza (Argentina), from the Andes to the eastern plains, in the context of climate change - Maria Laura Gomez; G. Hoke; S. D’Ambrosio; S. Moreiras; A. Castro (Hydrogeology Journal, 2022)

Do CMIP models capture long-term observed annual precipitation trends? - S. M. Vicente-Serrano; R. García-Herrera; D. Peña-Angulo; M. Tomas-Burguera; F. Domínguez-Castro; I. Noguera; N. Calvo; C. Murphy; R. Nieto; L. Gimeno; J. M. Gutierrez; C. Azorin-Molina; et al. (Climate Dynamics, 2022)
This study provides a long-term (1891–2014) global assessment of precipitation trends using data from two station-based gridded datasets and climate model outputs evolved through the fifth and sixth phases of the Coupled Model Intercomparison Project (CMIP5 and CMIP6, respectively). Our analysis employs a variety of modeling groups that incorporate low- and high-top level members, with the aim of assessing the possible effects of including a well-resolved stratosphere on the model’s ability to reproduce long-term observed annual precipitation trends. Results demonstrate that only a few regions show statistically significant differences in precipitation trends between observations and models. Nevertheless, this pattern is mostly caused by the strong interannual variability of precipitation in most of the world regions. Thus, statistically significant model-observation differences on trends (1891–2014) are found at the zonal mean scale. The different model groups clearly fail to reproduce the spatial patterns of annual precipitation trends and the regions where stronger increases or decreases are recorded. This study also stresses that there are no significant differences between low- and high-top models in capturing observed precipitation trends, indicating that having a well-resolved stratosphere has a low impact on the accuracy of precipitation projections.

RI75, a curcumin analogue, inhibits tumor necrosis factor-α and interleukin-6 production and exhibits antiallodynic and antiedematogenic activities in mice - Sarah O. A. M. Costa; Ianny B. Rodrigues; Alysson V. Braga; Bárbara C. M. Barbosa; Roger R. L. Silva; Felipe F. Rodrigues; Ivo S. F. Melo; Marcela Í. Morais; Brenda F. M. Castro; Armando S. Cunha Júnior; Vinícius G. Maltarollo; Renata B. Oliveira; et al. (Inflammopharmacology, 2022)

Genetic description of VanD phenotype vanA genotype in vancomycin-resistant Enterococcus faecium isolates from a Bone Marrow Transplantation Unit - Ana Paula Marchi; Lauro Vieira Perdigão Neto; Marina Farrel Côrtes; Victor Augusto Camarinha de Castro Lima; Roberta Cristina Ruedas Martins; Lucas Augusto Moyses Franco; Flavia Rossi; Vanderson Rocha; Anna S. Levin; Silvia Figueiredo Costa (Brazilian Journal of Microbiology, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Ant diversity studies in Brazil: an overview of the myrmecological research in a megadiverse country - F. A. Schmidt; C. R. Ribas; R. M. Feitosa; F. B. Baccaro; A. C. M. de Queiroz; T. G. Sobrinho; Y. Quinet; K. S. Carvalho; T. Izzo; M. S. de Castro Morini; A. Nogueira; H. M. Torezan-Silingardi; et al. (Insectes Sociaux, 2022)

Determination of Fipronil and Fipronil-Sulfone in Surface Waters of the Guandu River Basin by High-Performance Liquid Chromatography with Mass Spectrometry - Thais P. Ferreira; Glauco F. Bauerfeldt; Rosane N. Castro; Viviane S. Magalhães; Melina C. C. Alves; Fábio B. Scott; Yara P. Cid (Bulletin of Environmental Contamination and Toxicology, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Opportunities Surrounding the Use of Sargassum Biomass as Precursor of Biogas, Bioethanol, and Biodiesel Production - Jorge Gabriel Orozco-González; Fernando Amador-Castro; Angela R. Gordillo-Sierra; Tomás García-Cayuela; Hal S. Alper; Danay Carrillo-Nieves (Frontiers in Marine Science, 2022)
Climate change (along with other factors) has caused an increase in the proliferation of brown algal mats floating freely along the Atlantic Ocean since 2011. These brown algae mats are composed of sea plants from the Sargassum genus. The gargantuan agglomeration of biomass flows alongside currents and lands in beaches belonging to the Eastern coasts of the Mexican Caribbean and several other countries in the region. These events, dubbed golden tides, harm the local economy and environment. Current elimination approaches involve the mechanical harvesting of the Sargassum and ultimate landfill disposal. However, explorations into the commercial application of other brown algae have elucidated the potential of Sargassum as a feedstock for valorization. This review informs the trends, challenges, and opportunities presented by the coastal invasion of this biomass. Primarily, the potential use of this material is as a precursor in biorefineries where multiple value-added products are generated concurrent with the ultimate production of biofuels.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

South America climate change revealed through climate indices projected by GCMs and Eta-RCM ensembles - Michelle Simões Reboita; Cassia Akemi Castro Kuki; Vitor Hugo Marrafon; Christie Andre de Souza; Glauber Willian S. Ferreira; Thales Teodoro; José Wanderley Marangon Lima (Climate Dynamics, 2022)

Resistance exercise intervention on muscular strength and power, and functional capacity in acute hospitalized older adults: a systematic review and meta-analysis of 2498 patients in 7 randomized clinical trials - Marcelo A. S. Carneiro; Cristiane M. C. Franco; Alan L. Silva; Pâmela Castro-e-Souza; Gabriel Kunevaliki; Mikel Izquierdo; Edilson S. Cyrino; Camila S. Padilha (GeroScience, 2021)

Prevalence of Listeria monocytogenes fecal carriers in HIV-infected and -uninfected pregnant women from Brazil - Isabelle Geoffroy Ribeiro Freitag; Rodrigo de Castro Lisbôa Pereira; Elizabeth S. Machado; Ernesto Hofer; Deyse Christina Vallim; Cristina Barroso Hofer (Brazilian Journal of Microbiology, 2021)

Proteome of Erythroxylum pungens (Erythroxylaceae): an endemic species of the semiarid Caatinga - Daisy Sotero Chacon; Ivanice Bezerra da Silva; Taffarel Melo Torres; Gabrielle Macedo Pereira; Letícia Gondim Lambert Moreira; Luiz Fernando Rodrigues de Souza; Fernanda Priscila Santos Reginaldo; Alan de Araújo Roque; José Angelo S. Zuanazzi; Renata Libonati; Julia A. Rodrigues; Filippe L.M Santos; et al. (Plant Biosystems, 2021)

Sampling efforts for determining fish species richness in megadiverse tropical regions - Paulo S. Pompeu; Débora R. de Carvalho; Cecília G. Leal; Rafael P. Leitão; Carlos Bernardo M. Alves; Daniela F. Braga; Miriam A. Castro; Nara T. Junqueira; Robert M. Hughes (Environmental Biology of Fishes, 2021)

Exploring genetic diversity of lowland avocado (Persea americana Mill.) as a genetic reservoir for breeding - Eduardo Sandoval-Castro; Ayesha Y. Peraza-Magallanes; Richard S. Dodd; Vanessa E. T. M. Ashworth; Abraham Cruz-Mendívil; Carlos L. Calderón-Vázquez (Genetic Resources and Crop Evolution, 2021)

Effect of salinity on growth, survival, and serum osmolality of red snapper, Lutjanus campechanus - Harsha S. C. Galkanda-Arachchige; Robert P. Davis; Sidra Nazeer; Leonardo Ibarra-Castro; D. Allen Davis (Fish Physiology and Biochemistry, 2021)

Sediments in the mangrove areas contribute to the removal of endocrine disrupting chemicals in coastal sediments of Macau SAR, China, and harbour microbial communities capable of degrading E2, EE2, BPA and BPS - Irina S. Moreira; Alexandre Lebel; Xianzhi Peng; Paula M. L. Castro; David Gonçalves (Biodegradation, 2021)

Amazonia as the Origin and Diversification Area of Didelphidae (Mammalia: Metatheria), and a Review of the Fossil Record of the Clade - Mariela C. Castro; Murilo J. Dahur; Gabriel S. Ferreira (Journal of Mammalian Evolution, 2021)
Didelphidae is the largest New World radiation of marsupials, and is mostly represented by arboreal, small- to medium-sized taxa that inhabit tropical and/or subtropical forests. The group originated and remained isolated in South America for millions of years, until the formation of the Isthmus of Panama. In this study, we present the first reconstruction of the biogeographic history of Didelphidae including all major clades, based on parametric models and stratified analyses over time. We also compiled all the pre-Quaternary fossil records of the group, and contrasted these data to our biogeographic inferences, as well as to major environmental events that occurred in the South American Cenozoic. Our results indicate the relevance of Amazonia in the early diversification of Didelphidae, including the divergence of the major clades traditionally ranked as subfamilies and tribes. Cladogeneses in other areas started in the late Miocene, an interval of intense shifts, especially in the northern portion of Andes and Amazon Basin. Occupation of other areas continued through the Pliocene, but few were only colonized in Quaternary times. The comparison between the biogeographic inference and the fossil records highlights some further steps towards better understanding the spatiotemporal evolution of the clade. Finally, our results stress that the early history of didelphids is obscured by the lack of Paleogene fossils, which are still to be unearthed from low-latitude deposits of South America.

Correction to: Metabarcoding meiofauna biodiversity assessment in four beaches of Northern Colombia: effects of sampling protocols and primer choice - Lyda R. Castro; Rachel S. Meyer; Beth Shapiro; Sabrina Shirazi; Samuel Cutler; Ana M. Lagos; Sigmer Y. Quiroga (Hydrobiologia, 2021)

Metabarcoding meiofauna biodiversity assessment in four beaches of Northern Colombia: effects of sampling protocols and primer choice - Lyda R. Castro; Rachel S. Meyer; Beth Shapiro; Sabrina Shirazi; Samuel Cutler; Ana M. Lagos; Sigmer Y. Quiroga (Hydrobiologia, 2021)

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

Detection of porcine circovirus type 2 (PCV2) in the Philippines and the complexity of PCV2-associated disease diagnosis - Agnes dela Cruz; Chiara Palmieri; Rachel Azul; Christina Legaspi; Suzan Lola; Tamsin S. Barnes; Christopher R. Parke; Conny Turni; John I. Alawneh; Augusto S. Baluyut; Voltaire G. Basinang; Jose E. David; et al. (Tropical Animal Health and Production, 2021)

Interaction Between Marine Fauna and the Small Pelagic Fishery in the Coastal Environment of the Gulf of California, Mexico - Enrique Morales-Bojórquez; Manuel O. Nevárez-Martínez; Gabriela García-Alberto; Héctor Villalobos; Hugo Aguirre-Villaseñor; Estefani Larios-Castro; Sergio S. González-Peláez; Dana I. Arizmendi-Rodríguez; María de los Ángeles Martínez-Zavala (Frontiers in Marine Science, 2021)
The first steps have been taken to analyze the effects of small pelagic harvests on the Gulf of California ecosystem. The primary goal of this study was to estimate the latitudinal differences in regionalized baselines of endangered and threatened marine species attracted to a purse seine in a Mexican fishery of small pelagic fish. We also analyzed the spatial patterns in fishing effort in the Gulf of California. Seven zones were analyzed in the Gulf of California, including the east and west coasts, and a total of 3,051 fishing sets were analyzed during January 2013 and July 2014; the data provided a comprehensive picture of the distribution of the fishing effort, small pelagic fishes harvested, and the presence of species attracted to the fishing sets. The region in the upper Gulf of California showed a low presence of individuals, and the east coast recorded more sightings than the west coast; consequently the fishing effort was mainly distributed in the east coast. The number of individuals for several species sighted and counted by fishing set was used for each zone in the Gulf of California, and a conservative baseline based on the Pennington estimator was computed. It provided an average value of endangered and threatened marine species attracted to a purse seine for each zone. The Pennington estimator is recommended due to the precision of the confidence intervals and the nature of the uncertainty in the data collection based on sightings.

KIR2DL4 genetic diversity in a Brazilian population sample: implications for transcription regulation and protein diversity in samples with different ancestry backgrounds - Emiliana Weiss; Heloisa S. Andrade; Juliana Rodrigues Lara; Andreia S. Souza; Michelle A. Paz; Thálitta H. A. Lima; Iane O. P. Porto; Nayane S. B. Silva; Camila F. Bannwart Castro; Rejane M. T. Grotto; Eduardo A. Donadi; Celso T. Mendes-Junior; et al. (Immunogenetics, 2021)

Effect of Anadenanthera colubrina protease inhibitors as an antiinflamatory mediator - Gracimério J Guarneire; Oswaldo Cardoso Junior; Nerilson Marques Lima; Emanuel Aguilar Santos; Caio Aguiar Schulze; Wellington Pereira Silva; João Pedro Oliveira Batista; Gabriela de Paula Carli; Sandra Br Castro; Caio Cesar S Alves; Alessandra P Carli (Natural Product Research, 2021)

Application of the Theory of Critical Distances for the Fracture Assessment of a Notched Limestone Subjected to Different Temperatures and Mixed Mode with Predominant Mode I Loading Conditions - J. Justo; J. Castro; S. Cicero (Rock Mechanics and Rock Engineering, 2021)

Biotechnological Potential of Eugenol and Thymol Derivatives Against Staphylococcus aureus from Bovine Mastitis - Daiana O. S. Nunes; Rafaelle Vinturelle; Francislene J. Martins; Thiago F. dos Santos; Alessandra Leda Valverde; Carlos Magno R. Ribeiro; Helena C. Castro; Evelize Folly (Current Microbiology, 2021)

Miconia albicans and Curcuma longa herbal medicines positively modulate joint pain, function and inflammation in patients with osteoarthritis: a clinical study - Thiago P. O. Gomes; Jonathan I. N. Souza; Lucas C. Somerlate; Vanessa A. Mendonça; Nerilson M. Lima; Gabriela P. Carli; Sandra B. R. Castro; Teresinha de Jesus A. S. Andrade; João V. L. Dias; Marcone A. L. Oliveira; Caio C. S. Alves; Alessandra P. Carli (Inflammopharmacology, 2021)

Limonium mucronatum : plant communities and cytogenetic characterization of an endemic of the Moroccan Atlantic Coast - Laila Rhazi; Ana Rita Rebelo; Ana S. Róis; Sílvia Castro; João Loureiro; Mohammed El Madihi; Ana Paula Paes; Patrick Grillas; Mohammed Ibn Tattou; Ana D. Caperta (Plant Biosystems, 2021)

Application of rhamnolipid surfactant for remediation of toxic metals of long- and short-term contamination sites - C. S. C. Lopes; D. B. Teixeira; B. F. Braz; R. E. Santelli; L. V. A. de Castilho; J. G. C. Gomez; R. P. V. Castro; L. Seldin; D. M. G. Freire (International Journal of Environmental Science and Technology, 2021)

Spinel web: an interactive web application for visualizing the chemical composition of spinel group minerals - Antonella S. Antonini; María Luján Ganuza; Gabriela Ferracutti; M. Florencia Gargiulo; Kresimir Matković; Eduard Gröller; Ernesto A. Bjerg; Silvia M. Castro (Earth Science Informatics, 2021)

Bacterial Nanocellulose Mulch as a Potential Greener Alternative for Urban Gardening in the Small-Scale Food Production of Onion Plants - L. Cárcamo; S. Sierra; M. Osorio; J. Velásquez-Cock; L. Vélez-Acosta; C. Gómez-Hoyos; C. Castro; R. Zuluaga; P. Gañán (Agricultural Research, 2021)

Effects of Environmental Variables and Habitat Integrity on the Structure of the Aquatic Insect Communities of Streams in the Cerrado-Caatinga Ecotone in Northeastern Brazil - E. R. Castro; D. S. Veras; G. S. Lustosa; C. A. S. Azevêdo; L. Juen (Neotropical Entomology, 2021)

Rutin improves glutamate uptake and inhibits glutamate excitotoxicity in rat brain slices - Rafael S. Ferreira; Jéssica Teles-Souza; Cleide dos Santos Souza; Érica P. L. Pereira; Fillipe M. de Araújo; Alessandra Bispo da Silva; Juliana H. Castro e Silva; Yasmine Nonose; Yanier Núñez-Figueredo; Adriano M. de Assis; Diogo O. Souza; Maria de Fátima D. Costa; et al. (Molecular Biology Reports, 2021)

An interdisciplinary assessment of private conservation areas in the Western United States - Cristina Quintas-Soriano; Dainee M. Gibson; Jodi S. Brandt; María D. López-Rodríguez; Javier Cabello; Pedro A. Aguilera; Antonio J. Castro (Ambio, 2021)
Conservation easements are the fastest growing private conservation strategy in the United States. However, mechanisms to assess private land conservation as well as their support by the general public are not well understood. This study uses the ecosystem services framework for assessing existing private lands in Idaho and identifies areas for future conservation easements. Using conservation targets of the land trust as a guide for selecting ecosystem services, we (a) mapped the spatial delivery of conservation targets across public and private lands, (b) explored public awareness in terms of social importance and vulnerability, and (c) mapped future priority areas by characterizing conservation bundles. We found that public lands provided the highest levels of conservation targets, and we found no difference in conservation target provision between private areas and conservation easements. The spatial characterization of conservation target bundles identified potential future priority areas for conservation easements, which can guide planning of land trust conservation efforts.

Cubic-to-inverted micellar and the cubic-to-hexagonal-to-micellar transitions on phytantriol-based cubosomes induced by solvents - Mayra C. G. Lotierzo; Bruna R. Casadei; Raphael Dias de Castro; Barbara Malheiros; Leandro R. S. Barbosa (Drug Delivery and Translational Research, 2020)

In Situ Transesterification of Marine Microalgae Biomass via Heterogeneous Acid Catalysis - Savienne M. F. E. Zorn; Cristiano E. R. Reis; Heitor B. S. Bento; Ana Karine F. de Carvalho; Messias B. Silva; Heizir F. De Castro (BioEnergy Research, 2020)

Effects of leaf litter extracts from four tree species on aquatic invertebrates: an ecotoxicological risk assessment approach - A. Alonso; B. R. Vázquez de Aldana; P. Castro-Díez; S. Medina-Villar; M. E. Pérez-Corona (Aquatic Ecology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Correction to: Canopy dynamics in a tropical Atlantic forest mosaic in southeastern Brazil - Flávia P. Nunes; Silvana A. B. Castro; J. P. Lemos-Filho; Queila S. Garcia (Brazilian Journal of Botany, 2020)

Canopy dynamics in a tropical Atlantic forest mosaic in southeastern Brazil - Flávia P. Nunes; Silvana A. B. Castro; J. P. Lemos-Filho; Queila S. Garcia (Brazilian Journal of Botany, 2020)

Production of Value-Added Microbial Metabolites: Oleaginous Fungus as a Tool for Valorization of Dairy By-products - Carolina A. Braz; Ana K. F. Carvalho; Heitor B. S. Bento; Cristiano E. R. Reis; Heizir F. De Castro (BioEnergy Research, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Protective Effects of Agmatine Against Corticosterone-Induced Impairment on Hippocampal mTOR Signaling and Cell Death - Gislaine Olescowicz; Tuane B. Sampaio; Cristine de Paula Nascimento-Castro; Patricia S. Brocardo; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues (Neurotoxicity Research, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Effect of low-level flow and Andes mountain on the tropical and mid-latitude precipitating cloud systems: GPM observations - Shailendra Kumar; Aldo S. Moya-Álvarez; Carlos Del Castillo-Velarde; Daniel Martinez-Castro; Yamina Silva (Theoretical and Applied Climatology, 2020)

Effects of combined 5-HT2A and cannabinoid receptor modulation on a schizophrenia-related prepulse inhibition deficit in mice - Adriana M. Marques; Michele V. Macena; Aline R. Cardoso; Camila S. O. Hammes; Fernanda M. L. Pinheiro; Newton G. Castro; Gilda A. Neves (Psychopharmacology, 2020)

Biosorption of Rhodamine B Using a Low-Cost Biosorbent Prepared from Inactivated Aspergillus oryzae Cells: Kinetic, Equilibrium and Thermodynamic Studies - Flávia H. M. Souza; Vitória F. C. Leme; Giovanna O. B. Costa; Karine C. Castro; Tania R. Giraldi; Grazielle S. S. Andrade (Water, Air, & Soil Pollution, 2020)

Role of VEGFs in metabolic disorders - M. di Somma; M. Vliora; E. Grillo; B. Castro; E. Dakou; W. Schaafsma; J. Vanparijs; M. Corsini; C. Ravelli; E. Sakellariou; S. Mitola (Angiogenesis, 2020)

Shiga Toxin-Producing and Enteroaggregative Escherichia coli in Animal, Foods, and Humans: Pathogenicity Mechanisms, Detection Methods, and Epidemiology - Ana C. C. Paletta; Vinicius S. Castro; Carlos A. Conte-Junior (Current Microbiology, 2020)

Oxidative stress resistance in a short-lived Neotropical annual killifish - Robson S. Godoy; Luis Esteban K. Lanés; Bruna D. Castro; Vinicius Weber; Natália Wingen; Mateus M. Pires; Guendalina T. Oliveira; Leonardo Maltchik (Biogerontology, 2020)

Thirty days after anterior cruciate ligament transection is sufficient to induce signs of knee osteoarthritis in rats: pain, functional impairment, and synovial inflammation - Germanna M. Barbosa; Jonathan E. Cunha; Thiago L. Russo; Thiago M. Cunha; Paula A. T. S. Castro; Francisco F. B. Oliveira; Fernando Q. Cunha; Fernando S. Ramalho; Tania F. Salvini (Inflammation Research, 2020)

Promotion of the Geological Heritage of Araripe Unesco Global Geopark, Brazil: the Casa da Pedra Reference Center - I. S. Carvalho; M. H. Henriques; A. R. S. F. Castro; Y. R. Félix (Geoheritage, 2020)

Mangifera indica L. as Airborne Metal Biomonitor for Regions of the State of Espírito Santo (Brazil) - Leonardo Z. de Castro; Thaís R. B. da Silva; Silas N. Ronchi; Adriana A. T. Guimarães; Hermínio A. Nalini Júnior; Juliano S. Ribeiro; Silvia C. G. Coutinho; Elisangela F. Pimentel; Denise C. Endringer (Water, Air, & Soil Pollution, 2020)

Root proteome and metabolome reveal a high nutritional dependency of aluminium in Qualea grandiflora Mart. (Vochysiaceae) - Natalia F. Cury; Renata C. C. Silva; Michelle S. F. Andre; Wagner Fontes; Carlos A. O. Ricart; Mariana S. Castro; Conceição E. S. Silveira; Thomas C. R. Williams; Marcelo V. de Sousa; Luiz A. R. Pereira (Plant and Soil, 2020)

Role of inflammation, oxidative stress, and autonomic nervous system activation during the development of right and left cardiac remodeling in experimental pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; A. C. Bahr; P. Türck; A. L. de Castro; C. Campos-Carraro; F. Visioli; T. R. Fernandes-Piedras; K. R. Casali; C. M. C. Scassola; G. Baldo; et al. (Molecular and Cellular Biochemistry, 2020)

Lime and gypsum combination improves crop and forage yields and estimated meat production and revenue in a variable charge tropical soil - Carlos A. C. Crusciol; Rubia R. Marques; Antonio C. A. Carmeis Filho; Rogério P. Soratto; Claudio H. M. Costa; Jayme Ferrari Neto; Gustavo S. A. Castro; Cristiano M. Pariz; André M. Castilhos; Alan J. Franzluebbers (Nutrient Cycling in Agroecosystems, 2019)

Pollutant gas and particulate material emissions in ethanol production in Brazil: social and environmental impacts - Marcelo S. Sthel; Georgia A. Mothé; Marcenilda A. Lima; Maria P. P. de Castro; Israel Esquef; Marcelo G. da Silva (Environmental Science and Pollution Research, 2019)

Neurocognitive Impairment in mdx Mice - Clarissa M. Comim; Letícia Ventura; Viviane Freiberger; Paula Dias; Daiane Bragagnolo; Matheus L. Dutra; Ricardo A. Amaral; Ana Lucia S. Camargo-Fagundes; Patrícia A. Reis; Hugo C. Castro-Faria-Neto; Mariz Vainzof; Maria I. Rosa (Molecular Neurobiology, 2019)

Identification of Susceptible Rainfall-Induced Landslide Areas Based on Field Experiments and Multi-criteria Analysis in GIS Environment: A Proposal for Non-inventoried Areas - Leonardo C. Assis; Maria L. Calijuri; Mateus M. Salvador; Jackeline de S. Castro; Carolina F. Carvalho (Geotechnical and Geological Engineering, 2019)

Identification and characterization of atypical enteropathogenic and Shiga toxin-producing Escherichia coli isolated from ground beef and poultry breast purchased in Botucatu, Brazil - Rodrigo H. S. Tanabe; Melissa A. Vieira; Noelle A. B. Mariano; Regiane C. B. Dias; Rafael Ventin da Silva; Caroline M. Castro; Luis F. dos Santos; Carlos H. Camargo; Ricardo S. Yamatogi; Vera L. M. Rall; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2019)

Novel choline analog 2-(4-((1-phenyl-1H-pyrazol-4-yl)methyl)piperazin-1-yl)ethan-1-ol produces sympathoinhibition, hypotension, and antihypertensive effects - Ricardo Menegatti; Flávio S. Carvalho; Luciano M. Lião; Bianca Villavicencio; Hugo Verli; Aline A. Mourão; Carlos H. Xavier; Carlos H. Castro; Gustavo R. Pedrino; Octavio L. Franco; Iransé Oliveira-Silva; Nicole M. Ashpole; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Response of the WRF model to different resolutions in the rainfall forecast over the complex Peruvian orography - Aldo S. Moya-Álvarez; Daniel Martínez-Castro; Shailendra Kumar; René Estevan; Yamina Silva (Theoretical and Applied Climatology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Physiological responses of the red algae Gracilaria caudata (Gracilariales) and Laurencia catarinensis (Ceramiales) following treatment with a commercial extract of the brown alga Ascophyllum nodosum (AMPEP) - Jonatas M. C. Souza; Júlia Z. Castro; Alan T. Critchley; Nair S. Yokoya (Journal of Applied Phycology, 2019)

The Impact of the Right Coronary Artery Geometric Parameters on Hemodynamic Performance - N. Pinho; L. C. Sousa; C. F. Castro; C. C. António; M. Carvalho; W. Ferreira; R. Ladeiras-Lopes; N. D. Ferreira; P. Braga; N. Bettencourt; S. I. S. Pinto (Cardiovascular Engineering and Technology, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Vaginal biota number is smaller in tailed than docked hair ewes (Ovis aries), but is not affected by copulation - A. Orihuela; A. Fierros-García; C. Hallal-Calleros; S. R. Robles-Castro; R. Ungerfeld (Tropical Animal Health and Production, 2019)

Citalopram Reduces Aggregation of ATXN3 in a YAC Transgenic Mouse Model of Machado-Joseph Disease - Naila S. Ashraf; Sara Duarte-Silva; Emily D. Shaw; Patrícia Maciel; Henry L. Paulson; Andreia Teixeira-Castro; Maria do Carmo Costa (Molecular Neurobiology, 2019)

Reproductive dynamics of the white shrimp Litopenaeus schmitti (Burkenroad 1936) in a beach seine fishery in northeastern Brazil - Cecília Craveiro; Silvio Peixoto; Emanuell F. Silva; Leandro N. Eduardo; Alex S. Lira; Hildemário Castro-Neto; Flávia L. Frédou; Roberta Soares (Invertebrate Reproduction & Development, 2019)

Two New Species of the Spittlebug Genus Ocoaxo Fennah (Hemiptera: Cercopidae) from Mexico, and Keys for the Groups, Group Three, and First Subgroup - U Castro-Valderrama; G S Carvalho; D C Peck; J M Valdez-Carrasco; J Romero Nápoles (Neotropical Entomology, 2019)

Variations in Tissue Mercury Contents in Three Species of Adult Salamanders in Streams in Western Maryland - Mark S. Castro; Morgan Kaumeyer; Robert H. Hilderbrand (Archives of Environmental Contamination and Toxicology, 2019)

Spatial assessment of the performance of multiple high‐resolution satellite‐based precipitation data sets over the Middle East - Ahmed M. El Kenawy; Matthew F. McCabe; Juan I. Lopez‐Moreno; Yossef Hathal; S. M. Robaa; Ahmed L. Al Budeiri; Khan Zaib Jadoon; Abdou Abouelmagd; Ali Eddenjal; Fernando Domínguez‐Castro; Ricardo M. Trigo; Sergio M. Vicente‐Serrano (International Journal of Climatology, 2019)
This study presents the first comprehensive evaluation of the performance of three globally high‐resolution remotely sensed products in replicating the main characteristics of rainfall over the Middle East, with special emphasis on extreme wet events. Specifically, we employed daily observational data from a network of rain gauges ( N = 217), spanning the retrospective period 1998–2013 and covering six countries in the Middle East (i.e., Egypt, Iraq, Jordan, Libya, Saudi Arabia, and Syria), against data derived from three global satellite‐based precipitation products: the Version 7 TRMM (Tropical Rainfall Measuring Mission) Multi‐satellite Precipitation Analysis 3B42 product (TRMM‐3B42), the Climate Prediction Center MORPHing technique (CMORPH), and the Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks (PERSIANN). Alongside a range of conventional statistical error measures (e.g., bias, normalized root‐mean‐square error [nRMSE] and Spearman's rho correlation coefficient), this study also gives priority to evaluate the skill of these products in reproducing characteristics of extreme wet events (e.g., frequency, intensity, duration, onset, anomaly). Results demonstrate that TRMM‐3B42 generally performs well in estimating rainfall totals during the rainy season (ONDJFMA), with a mean bias of 0.05 mm, nRMSE of 0.15 mm, and Spearman's rho of 0.74 for the whole Middle East. In contrast, PERSIANN‐CDR and CMORPH‐BLD underestimate the observed rainfall. Importantly, TRMM‐3B42 outperforms other products in reproducing the frequency and intensity of the most extreme wet events, while PERSIANN‐CDR and CMORPH‐BLD fail to reproduce these key characteristics. Notably, all products perform poorly in reproducing the climatology of the anomalous wet events in the region, indicating that careful scrutiny must be warranted before using these products, particularly for hydrological modelling. Considering the daily resolution of these remotely sensed precipitation products and their reasonable spatial resolution (0.25 × 0.25°) in comparison to available in situ data over the Middle East, results of this work provide a solid scientific reference for national stakeholders and policy makers to decide on the most useful product for their specific applications (e.g., hydrological modelling, streamflow forecasts, water resources management, and hydrometeorological hazard assessment and mitigation).

Correlation between geometric parameters of the left coronary artery and hemodynamic descriptors of atherosclerosis: FSI and statistical study - N. Pinho; C. F. Castro; C. C. António; N. Bettencourt; L. C. Sousa; S. I. S. Pinto (Medical & Biological Engineering & Computing, 2019)

Growth and biochemical responses of tropical and subtropical strains of Gracilaria domingensis (Gracilariales, Rhodophyta) to temperature and irradiance variations - Julia Z. Castro; Nair S. Yokoya (Journal of Applied Phycology, 2019)

Immunological MHC supertypes and allelic expression: how low is the functional MHC diversity in free-ranging Namibian cheetahs? - N. Schwensow; A. Castro-Prieto; B. Wachter; S. Sommer (Conservation Genetics, 2019)

On the low-frequency variability of wintertime Euro-Atlantic planetary wave-breaking - Gabriele Messori; Paolo Davini; M. Carmen Alvarez-Castro; Francesco S. R. Pausata; Pascal Yiou; Rodrigo Caballero (Climate Dynamics, 2019)

Sugar transport systems in Kluyveromyces marxianus CCT 7735 - Fernando Augusto da Silveira; Raphael Hermano S. Diniz; Geraldo M. S. Sampaio; Rogelio L. Brandão; Wendel B. da Silveira; Ieso M. Castro (Antonie van Leeuwenhoek, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Enzyme-linked immunosorbent assay and agar gel immunodiffusion assay for diagnosis of equine infectious anemia employing p26 protein fused to the maltose-binding protein - Karin F. L. P. Fontes; Luiz C. Silva-Júnior; Sérgio A. Nascimento; Daniel P. Chaves; Jose W. Pinheiro-Júnior; Antonio C. Freitas; Roberto S. Castro; André L. S. Jesus (Archives of Virology, 2018)

Brain-Derived Neurotrophic Factor Prevents Depressive-Like Behaviors in Early-Symptomatic YAC128 Huntington’s Disease Mice - Victor Silva da Fonsêca; André R. da Silva Colla; Cristine de Paula Nascimento-Castro; Evelini Plácido; Julia Macedo Rosa; Marcelo Farina; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues; Patricia S. Brocardo (Molecular Neurobiology, 2018)

The Híbrido de Timor germplasm: identification of molecular diversity and resistance sources to coffee berry disease and leaf rust - R. A. Silva; L. Zambolim; I. S. L. Castro; H. S. Rodrigues; C. D. Cruz; E. T. Caixeta (Euphytica, 2018)

Use of chemometric analyses to assess biological wastewater treatment plants by protozoa and metazoa monitoring - A. Luís Amaral; Cristiano S. Leal; A. Isabel Vaz; J. Carvalho Vieira; Andreia C. Quinteiro; M. Lourdes Costa; L. Miguel Castro (Environmental Monitoring and Assessment, 2018)

Characterization of esterase activity from an Acetomicrobium hydrogeniformans enzyme with high structural stability in extreme conditions - Patricia S. Kumagai; Raissa F. Gutierrez; Jose L. S. Lopes; Julia M. Martins; David M. Jameson; Aline M. Castro; Luiz F. Martins; Ricardo DeMarco; Nelma R. S. Bossolan; B. A. Wallace; Ana P. U. Araujo (Extremophiles, 2018)

Pacific sea surface temperature related influences on North American monsoon precipitation within North American Regional Climate Change Assessment Program models - Carlos M. Carrillo; Christopher L. Castro; Gregg Garfin; Hsin‐I Chang; Melissa S. Bukovsky; Linda O. Mearns (International Journal of Climatology, 2018)
Climate inter‐annual variability over the North American monsoon (NAM) region is associated with El Niño‐Southern Oscillation (ENSO) and Pacific decadal variability (PDV), which drive a warm season atmospheric teleconnection response. Using the North American Regional Climate Change Assessment Program (NARCCAP) simulations, previous studies have found that regional models forced with an atmospheric reanalysis (NARCCAP Phase I) represent the NAM reasonably well as a climatological feature. However, when these same regional models are forced with global climate model projections (NARCCAP Phase II), their ability to represent the NAM as a salient feature substantially degrades. The present study evaluates NAM inter‐annual climate variability through the continental‐scale patterns of summer precipitation within the NARCCAP simulations (Phases I and II), in relation to ENSO–PDV, and the presence of the driving atmospheric teleconnection response. Multivariate statistical analyses are applied to sea surface temperature and precipitation data sets to determine dominant variability at continental scale, with focus on the southwest. The analysis reveals that NARCCAP Phase I simulations are able to portray the spatial pattern of precipitation associated with ENSO–PDV in a similar way to observations. However, all NARCCAP Phase II simulations, with the exception of the HRM(Hadcm3) regional–global model pair, fail to reproduce this climate variability. Although including all possible NARCCAP model simulations to generate a multi‐model ensemble mean would increase the statistical degree of confidence in climate projections, this type of result would not increase confidence in the physical climatology of model representations of warm season climate variability. More physically based, process‐oriented metrics are needed to evaluate model quality in assessing the uncertainty of future climate change in multi‐model ensemble products used for climate change impacts assessments.

Mercury Concentrations in Northern Two-Lined Salamanders from Stream Ecosystems in Garrett County, Maryland - Mark S. Castro; Robert H. Hilderbrand; Morgan Kaumeyer (Archives of Environmental Contamination and Toxicology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

A morphological database for 606 Colombian bird species - Paola Montoya; Mailyn A. Gonzalez; Elkin A. Tenorio; Juan Pablo López‐Ordóñez; Alejandro Pinto Gómez; Diego Cueva; Aldemar A. Acevedo Rincón; Camilo Angarita Yanes; Héctor Manuel Arango Martínez; Orlando Armesto; Jefry S. Betancur; Angela Caguazango Castro; et al. (Ecology, 2018)
Colombia is the country with the highest bird diversity in the world. Despite active research in ornithology, compelling morphological information of most bird species is still sparse. However, morphological information is the baseline to understand how species respond to environmental variation and how ecosystems respond to species loss. As part of a national initiative, the Instituto Alexander von Humboldt in collaboration with 12 Colombian institutions and seven biological collections, measured up to 15 morphological traits of 9,892 individuals corresponding to 606 species: 3,492 from individuals captured in field and 6,400 from museum specimens. Species measured are mainly distributed in high Andean forest, páramo, and wetland ecosystems. Seven ornithological collections in Colombia and 18 páramo complexes throughout Colombia were visited from 2013 to 2015. The morphological traits involved measurements from bill (total and exposed culmen, bill width and depth), wing (length, area, wingspan, and the distance between longest primary and longest secondary), tail (length and shape), tarsus (length), hallux (length and claw hallux), and mass. The number of measured specimens per species was variable, ranging from 1 to 321 individuals with a median of four individuals per species. Overall, this database gathered morphological information for >30% of Colombian bird diversity. No copyright, proprietary, or cost restrictions apply; the data should be cited appropriately when used.

Transgenerational Effects of Toxicants: An Extension of the Daphnia 21-day Chronic Assay? - B. B. Castro; A. R. Freches; M. Rodrigues; B. Nunes; S. C. Antunes (Archives of Environmental Contamination and Toxicology, 2018)

Atorvastatin Prevents Early Oxidative Events and Modulates Inflammatory Mediators in the Striatum Following Intranasal 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) Administration in Rats - Naiani F. Marques; Adalberto A. Castro; Gianni Mancini; Fernanda L. Rocha; Adair R. S. Santos; Rui D. Prediger; Andreza Fabro De Bem; Carla I. Tasca (Neurotoxicity Research, 2018)

Effectiveness of early-generation testing applied to upland rice breeding - Matheus S. Barros; Odilon P. Morais Júnior; Patrícia G. S. Melo; Orlando P. Morais; Adriano P. Castro; Flávio Breseghello (Euphytica, 2018)

Genotoxicity of spent pot liner as determined with the zebrafish (Danio rerio) experimental model - Tássia F. D. Castro; Isadora M. Paiva; Aline F. S. Carvalho; Isadora L. Assis; Marcel J. Palmieri; Larissa F. Andrade-Vieira; Silvana Marcussi; Luis D. Solis-Murgas (Environmental Science and Pollution Research, 2018)

Expression of Neuronal NO Synthase and the Hyperglycemic Reflex to Anoxic Stimulation of the Carotid Body in Normoglycemic and Hyperglycemic Rats - A. Hernández-Leal; H. R. Tejeda-Chávez; S. Montero; M. Lemus; E. Castro; M. Ramírez-Flores; E. Roces de Álvarez-Buylla (Neurophysiology, 2018)

Ascorbic acid toxicity is related to oxidative stress and enhanced by high light and knockdown of chloroplast ascorbate peroxidases in rice plants - Jamyla L. S. Castro; Yugo Lima-Melo; Fabricio E. L. Carvalho; Antonio G. S. Feitosa; Milton C. Lima Neto; Andréia Caverzan; Marcia Margis-Pinheiro; Joaquim A. G. Silveira (Theoretical and Experimental Plant Physiology, 2018)

Palatability of the Asian clam Corbicula fluminea (Müller 1774) in an invaded system - P. S. Castro; M. I. Ilarri; V. Modesto; C. Antunes; R. Sousa (Hydrobiologia, 2018)

The Scale-Dependent Role of Biological Traits in Landscape Ecology: A Review - Andrés Felipe Suárez-Castro; Jeremy S. Simmonds; Matthew G. E. Mitchell; Martine Maron; Jonathan R. Rhodes (Current Landscape Ecology Reports, 2018)

Comparison of four modeling tools for the prediction of potential distribution for non-indigenous weeds in the United States - Roger Magarey; Leslie Newton; Seung Cheon Hong; Yu Takeuchi; David Christie; Catherine S. Jarnevich; Lisa Kohl; Martin Damus; Steven I. Higgins; Leah Millar; Karen Castro; Amanda West; et al. (Biological Invasions, 2018)

First evidence of viral and bacterial oyster pathogens in the Brazilian coast - D F Mello; N M Danielli; F Curbani; V A Pontinha; S Suhnel; M A M Castro; S C Medeiros; N C Wendt; R Trevisan; A R M Magalhães; A L Dafre (Journal of Fish Diseases, 2018)

Wet and dry extremes in Quito (Ecuador) since the 17th century - F. Domínguez‐Castro; R. García‐Herrera; S. M. Vicente‐Serrano (International Journal of Climatology, 2018)
Wet and dry extremes in Quito (Ecuador) over the last 400 years are studied using two sources of information: the longest available instrumental rainfall series in northern South America (1891–2015) and the rogation ceremonies recorded in the Chapter Acts of Quito (1600–1822). The rogation ceremonies present a seasonal distribution that is related to the crops and to the typical distribution of rainfall over the year. August was the month with most pro serenitate rogations because farmers needed dry conditions for harvest, whereas excess rainfall at this time would lead to rotting and loss of the harvest. The pro pluvia rogations were markedly more frequent during January and February when farmers needed rain for sowing. This relationship between climate and farming activities makes Quito's rogations a good proxy for drought and extreme wet conditions during January–February–March (JFM) and wet conditions during June–July–August (JJA). Standardized precipitation index (SPI) was computed for the instrumental period. The 3‐month SPI showed a significant linear trend over the last 125 years (−0.4 per decade, p = 0.009). The five wettest periods were 1651–1657, 1663–1669, 1913–1919, 1950–1956, and 1981–1985. Droughts have intensified in frequency and length since the middle of the 20th century. The most important drought periods were 1692–1701, 1718–1723, 1976–1980, 1990–1993, and 2001–2006. The severest drought during the last 400 years occurred in 1692–1701 when a great famine devastated Quito and affected most of the central Andes.

The future of fish passage science, engineering, and practice - Ana T. Silva; Martyn C. Lucas; Theodore Castro‐Santos; Christos Katopodis; Lee J. Baumgartner; Jason D. Thiem; Kim Aarestrup; Paulo S. Pompeu; Gordon C. O'Brien; Douglas C. Braun; Nicholas J. Burnett; David Z. Zhu; et al. (Fish and Fisheries, 2018)
Much effort has been devoted to developing, constructing and refining fish passage facilities to enable target species to pass barriers on fluvial systems, and yet, fishway science, engineering and practice remain imperfect. In this review, 17 experts from different fish passage research fields (i.e., biology, ecology, physiology, ecohydraulics, engineering) and from different continents (i.e., North and South America, Europe, Africa, Australia) identified knowledge gaps and provided a roadmap for research priorities and technical developments. Once dominated by an engineering‐focused approach, fishway science today involves a wide range of disciplines from fish behaviour to socioeconomics to complex modelling of passage prioritization options in river networks. River barrier impacts on fish migration and dispersal are currently better understood than historically, but basic ecological knowledge underpinning the need for effective fish passage in many regions of the world, including in biodiversity hotspots (e.g., equatorial Africa, South‐East Asia), remains largely unknown. Designing efficient fishways, with minimal passage delay and post‐passage impacts, requires adaptive management and continued innovation. While the use of fishways in river restoration demands a transition towards fish passage at the community scale, advances in selective fishways are also needed to manage invasive fish colonization. Because of the erroneous view in some literature and communities of practice that fish passage is largely a proven technology, improved international collaboration, information sharing, method standardization and multidisciplinary training are needed. Further development of regional expertise is needed in South America, Asia and Africa where hydropower dams are currently being planned and constructed.

Substrate influence on aromatic plant growth in extensive green roofs in a Mediterranean climate - Cristina M. Monteiro; Cristina S. C. Calheiros; João P. Martins; Francisco M. Costa; Paulo Palha; Sara de Freitas; Nuno M. M. Ramos; Paula M. L. Castro (Urban Ecosystems, 2017)

Correction to: Stepwise strategy for monitoring toxic cyanobacterial blooms in lentic water bodies - Inês P. E. Macário; Bruno B. Castro; Maria I. S. Nunes; Cristina Pizarro; Carla Coelho; Fernando Gonçalves; Daniela R. de Figueiredo (Environmental Monitoring and Assessment, 2017)

Stepwise strategy for monitoring toxic cyanobacterial blooms in lentic water bodies - Inês P. E. Macário; Bruno B. Castro; Isabel M. S. Nunes; Cristina Pizarro; Carla Coelho; Fernando Gonçalves; Daniela R. de Figueiredo (Environmental Monitoring and Assessment, 2017)

Production of three symbiosis-related fatty acids by Symbiodinium types in clades A–F associated with marine invertebrate larvae - M. Mies; A. B. Chaves-Filho; S. Miyamoto; A. Z. Güth; A. A. Tenório; C. B. Castro; D. O. Pires; E. N. Calderon; P. Y. G. Sumida (Coral Reefs, 2017)

Plume composition and volatile flux of Nyamulagira volcano, Democratic Republic of Congo, during birth and evolution of the lava lake, 2014–2015 - N. Bobrowski; G. B. Giuffrida; S. Arellano; M. Yalire; M. Liotta; L. Brusca; S. Calabrese; S. Scaglione; J. Rüdiger; J. M. Castro; B. Galle; D. Tedesco (Bulletin of Volcanology, 2017)

Larval fish collected from sound‐scattering layers in an offshore tropical area - M. S. Castro; A. C. T. Bonecker (Journal of Fish Biology, 2017)
The composition of the larval fish assemblage in the sound‐scattering layer of the continental shelf waters off the coast of south‐eastern Brazil (12 and 22° S), a research project that is part of the Brazilian programme Avaliação do Potencial Sustentável de Recursos Vivos na Zona Econômica Exclusiva (REVIZEE), is described. Samples were collected during daylight hours and at dusk at five oceanographic stations in the winter of 1999 using an Isaacs‐Kidd Midwater Trawl (IKMT). The oceanographic stations were chosen based on the detection of plankton layers by acoustic observation. A total of 2192 larval fish were identified, comprising 52 families and 62 species. Maurolicus stehmanni (Sternoptychidae) was the most abundant species found within the study area, comprising 18·5% of all identified larvae, followed by Psilotris celsus (Gobiidae) at 10·9%.

First report of persistent dengue-1-associated autoimmune neurological disturbance: neuromyelitis optica spectrum disorder - Marzia Puccioni-Sohler; Alice M. M. Ornelas; Andrea S. de Souza; Mauro Jorge Cabral-Castro; Jessyca T.M.A. Ramos; Carolina Rosadas; Maria Cecilia F. Salgado; Alexandre A. Castiglione; Fernando Ferry; Jose Mauro Peralta; Carolina Moreira Voloch; Amilcar Tanuri; et al. (Journal of NeuroVirology, 2017)

Migratory preferences of humpback whales between feeding and breeding grounds in the eastern South Pacific - Jorge Acevedo; Anelio Aguayo‐Lobo; Judith Allen; Natalia Botero‐Acosta; Juan Capella; Cristina Castro; Luciano Dalla Rosa; Judith Denkinger; Fernando Félix; Lilian Flórez‐González; Frank Garita; Héctor M. Guzmán; et al. (Marine Mammal Science, 2017)
Latitudinal preferences within the breeding range have been suggested for Breeding Stock G humpback whales that summer in different feeding areas of the eastern South Pacific. To address this hypothesis, humpback whales photo‐identified from the Antarctic Peninsula and the Fueguian Archipelago (southern Chile) were compared with whales photo‐identified from lower latitudes extending from northern Peru to Costa Rica. This comparison was performed over a time span that includes 18 austral seasons. A total of 238 whales identified from the Antarctic Peninsula and 25 whales from the Fueguian Archipelago were among those photo‐identified at the breeding grounds. Our findings showed that humpback whales from each feeding area were resighted unevenly across the breeding grounds, which suggests a degree of spatial structuring in the migratory pathway. Humpback whales that feed at the Antarctic Peninsula were more likely to migrate to the southern breeding range between northern Peru and Colombia, whereas whales that feed at the Fueguian Archipelago were more likely to be found in the northern range of the breeding ground off Panama. Further photo‐identification efforts and genetic sampling from poorly sampled or unsampled areas are recommended to confirm these reported connectivity patterns.

Woody plant community structure in “Dense Cerrado” fragments in the Upper Basin of the Araguaia River (Central Brazil): relationship with habitat loss and geographical distance - Mariana N. Siqueira; Selma Simões de Castro; Alessandro R. Morais; Karla M. S. Faria (Brazilian Journal of Botany, 2017)

Influence of drinking water salinity on carcass characteristics and meat quality of Santa Inês lambs - Daniela P. V. Castro; Sandra M. Yamamoto; Gherman G. L. Araújo; Rafael S. B. Pinheiro; Mario A. A. Queiroz; Ítalo R. R. Albuquerque; José H. A. Moura (Tropical Animal Health and Production, 2017)

A fucan of a brown seaweed and its antitumoral property on HT-29 and immunomodulatory activity in murine RAW 264.7 macrophage cell line - Thuane de Sousa Pinheiro; Marilia da S. Nascimento Santos; Luiza Sheyla E. P. Will Castro; Almino Afonso de O. Paiva; Luciana G. Alves; Ana Katarina M. Cruz; Leonardo Thiago D. B. Nobre; Monique Gabriela das C. F. Alves; Edda Lisboa Leite (Journal of Applied Phycology, 2017)

Preparation of Activated Carbon from Sugarcane Bagasse Soot and Methylene Blue Adsorption - Luana A. R. Giusto; Fábio L. Pissetti; Talita S. Castro; Fabiano Magalhães (Water, Air, & Soil Pollution, 2017)

Ecology and recovery plans for the four Spanish endangered endemic butterfly species - M. L. Munguira; J. M. Barea-Azcón; S. Castro-Cobo; E. García-Barros; S. Miteva; J. Olivares; H. Romo (Journal of Insect Conservation, 2017)

Evaluating the predictive power of field variables for species and individual molecular identification on wolf noninvasive samples - Mónia Nakamura; Raquel Godinho; H. Rio-Maior; S. Roque; A. Kaliontzopoulou; J. Bernardo; D. Castro; S. Lopes; F. Petrucci-Fonseca; F. Álvares (European Journal of Wildlife Research, 2017)

The role of epigenetic modifiers in extended cultures of functional hepatocyte-like cells derived from human neonatal mesenchymal stem cells - M. Cipriano; J. C. Correia; S. P. Camões; N. G. Oliveira; P. Cruz; H. Cruz; M. Castro; J. L. Ruas; J. M. Santos; J. P. Miranda (Archives of Toxicology, 2017)

Recombinant Bacillus thuringiensis subsp. kurstaki HD73 strain that synthesizes Cry1Ac and chimeric ChiA74∆sp chitinase inclusions - Karen S. González-Ponce; Luz E. Casados-Vázquez; Rubén Salcedo-Hernández; Dennis K. Bideshi; María C. del Rincón-Castro; José E. Barboza-Corona (Archives of Microbiology, 2017)

A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography - Jairo Patiño; Robert J. Whittaker; Paulo A.V. Borges; José María Fernández‐Palacios; Claudine Ah‐Peng; Miguel B. Araújo; Sergio P. Ávila; Pedro Cardoso; Josselin Cornuault; Erik J. de Boer; Lea de Nascimento; Artur Gil; et al. (Journal of Biogeography, 2017)
Aims The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography , by Robert H. MacArthur and Edward O. Wilson, is a timely moment to review and identify key research foci that could advance island biology. Here, we take a collaborative horizon‐scanning approach to identify 50 fundamental questions for the continued development of the field. Location Worldwide. Methods We adapted a well‐established methodology of horizon scanning to identify priority research questions in island biology, and initiated it during the Island Biology 2016 conference held in the Azores. A multidisciplinary working group prepared an initial pool of 187 questions. A series of online surveys was then used to refine a list of the 50 top priority questions. The final shortlist was restricted to questions with a broad conceptual scope, and which should be answerable through achievable research approaches. Results Questions were structured around four broad and partially overlapping island topics, including: (Macro)Ecology and Biogeography, (Macro)Evolution, Community Ecology, and Conservation and Management. These topics were then subdivided according to the following subject areas: global diversity patterns (five questions in total); island ontogeny and past climate change (4); island rules and syndromes (3); island biogeography theory (4); immigration–speciation–extinction dynamics (5); speciation and diversification (4); dispersal and colonization (3); community assembly (6); biotic interactions (2); global change (5); conservation and management policies (5); and invasive alien species (4). Main conclusions Collectively, this cross‐disciplinary set of topics covering the 50 fundamental questions has the potential to stimulate and guide future research in island biology. By covering fields ranging from biogeography, community ecology and evolution to global change, this horizon scan may help to foster the formation of interdisciplinary research networks, enhancing joint efforts to better understand the past, present and future of island biotas.

Reaction overstepping and re-evaluation of peak P‒T conditions of the blueschist unit Sifnos, Greece: implications for the Cyclades subduction zone - Adrian E. Castro; Frank S. Spear (International Geology Review, 2017)

Life-cycle assessment of the soybean-sunflower production system in the Brazilian Cerrado - Marília I. S. Folegatti Matsuura; Fernando R. T. Dias; Juliana F. Picoli; Kássio R. Garcia Lucas; Cesar de Castro; Marcelo H. Hirakuri (The International Journal of Life Cycle Assessment, 2017)

Reliable methods for determination of triazine herbicides and their degradation products in seawater and marine sediments using liquid chromatography-tandem mass spectrometry - N. Rodríguez-González; R. Uzal-Varela; M.J. González-Castro; S. Muniategui-Lorenzo; E. Beceiro-González (Environmental Science and Pollution Research, 2017)

Inactivation, lysis and degradation by-products of Saccharomyces cerevisiae by electrooxidation using DSA - Lyliane F. Trigueiro; Larissa M. Silva; Luciana A. B. D. Itto; Thiago M. B. F. Oliveira; Artur J. Motheo; Carlos A. Martínez-Huitle; Janete J. F. Alves; Suely S. L. Castro (Environmental Science and Pollution Research, 2017)

Optimized treatment conditions for textile wastewater reuse using photocatalytic processes under UV and visible light sources - Maria Clara V. M. Starling; Luiz Augusto S. Castro; Rafaela B. P. Marcelino; Mônica M. D. Leão; Camila C. Amorim (Environmental Science and Pollution Research, 2017)

Identification and genetic characterization of classical swine fever virus isolates in Brazil: a new subgenotype - Marta N. F. Silva; Diogo M. F. Silva; Adriana S. Leite; Ana L. V. Gomes; Antonio C. Freitas; Jose W. Pinheiro-Junior; Roberto S. Castro; Andre L. S. Jesus (Archives of Virology, 2017)

Presence of Ureaplasma diversum in the genital tracts of female dairy cattle in Mato Grosso State, Brazil - Jaqueline B. Azevedo; Gustavo S. Silva; Priscylla S. Rocha; Letícia C. Pitchenin; Valéria Dutra; Luciano Nakazato; Anderson Castro Soares de Oliveira; Caroline A. Pescador (Tropical Animal Health and Production, 2017)

Best Practices of Nitrogen Fertilization Management for Sugarcane Under Green Cane Trash Blanket in Brazil - Sérgio Gustavo Quassi de Castro; Sérgio Tadeu Decaro; Henrique Coutinho Junqueira Franco; Paulo S. Graziano Magalhães; Alan Garside; Miguel Angelo Mutton (Sugar Tech, 2017)

Differential impact of hotter drought on seedling performance of five ecologically distinct pine species - Luis Matías; Jorge Castro; Pedro Villar-Salvador; José L. Quero; Alistair S. Jump (Plant Ecology, 2017)

Life cycle inference and phylogeny of Ortholinea labracis n. sp. (Myxosporea: Ortholineidae), a parasite of the European seabass Dicentrarchus labrax (Teleostei: Moronidae), in a Portuguese fish farm - L F Rangel; S Rocha; G Casal; R Castro; R Severino; C Azevedo; F Cavaleiro; M J Santos (Journal of Fish Diseases, 2017)
Ortholinea labracis n. sp. is described and its life cycle is inferred from a Southern Portuguese fish farm, with basis on microscopic and molecular procedures. This myxosporean parasite infects the urinary bladder of the European seabass Dicentrarchus labrax and the intestinal epithelium of a marine oligochaete of the genus Tectidrilus . Myxospores subspherical in valvular view and ellipsoidal in sutural view measuring 7.6 ± 0.3 (6.8–8.7) μm in length, 7.2 ± 0.2 (6.7–7.7) μm in width and 6.5 ± 0.4 (5.8–7.7) μm in thickness. Two polar capsules, 3.0 ± 0.2 (2.6–3.4) μm long and 2.4 ± 0.1 (2.0–2.9) μm wide, located at the same level, but with divergent orientation and opening to opposite sides of the suture line. Sequencing of the SSU rRNA gene revealed a similarity of 100% between the analysed myxospores and triactinomyxon actinospores. The phylogenetic setting of O. labracis n. sp. shows subgrouping in correlation with tissue tropism, but identifies this parasite as another exception to the main division of Myxosporea into the main freshwater and marine lineages.

Nitrogen Use Efficiency for Sugarcane-Biofuel Production: What Is Next? - R. Otto; S. A. Q. Castro; E. Mariano; S. G. Q. Castro; H. C. J. Franco; P. C. O. Trivelin (BioEnergy Research, 2016)

Simvastatin Treatment Modulates Mechanically-Induced Injury and Inflammation in Respiratory Epithelial Cells - N. Higuita-Castro; V. C. Shukla; C. Mihai; S. N. Ghadiali (Annals of Biomedical Engineering, 2016)

Asymmetric biocatalysis of the nerve agent VX by human serum paraoxonase 1: molecular docking and reaction mechanism calculations - Jaqueline Sartorelli; Alexandre A. de Castro; Teodorico C. Ramalho; Juliana O. S. Giacoppo; Daiana T. Mancini; Melissa S. Caetano; Elaine F. F. da Cunha (Medicinal Chemistry Research, 2016)

Assessment of plant growth promoting bacterial populations in the rhizosphere of metallophytes from the Kettara mine, Marrakech - L. Benidire; S. I. A. Pereira; P. M. L. Castro; A. Boularbah (Environmental Science and Pollution Research, 2016)

Unveiling the influence of the environment on the migration pattern of the Atlantic pomfret ( Brama brama ) in North‐eastern Atlantic waters - M. Quinzán; J. Castro; M. Marín; G. Costas; S. Monserrat; A. Amores; E. Massutí; M. Hidalgo (Fisheries Oceanography, 2016)
Hydroclimatic variability is one of the main factors that drives inter‐annual changes in fish migration patterns. This study analyses the relationship between climate‐oceanographic factors and migration of the Atlantic pomfret ( Brama brama ) in NE Atlantic waters. Geo‐referenced catch data from logbooks of longliners operating in European Atlantic waters from 2002 to 2013 were linked to environmental indices at different temporal and spatial scales. Our results point to a strong influence of temperature at 200 m depth as the key factor along with the upwelling in the Galician ( NW Iberian) waters. However, sea surface temperature ( SST ) indirectly affects the geographical display of Atlantic pomfret migration, and large migrations are observed in scenarios of high SST s in the migratory area ( c . above 14.7°C). Migrations are constrained during years when temperatures are below this threshold. A longer time‐series of annual landings (1950–2013) supports this evidence and highlights the significant influence of temperature at 200‐m depth along with the landings of the previous year. Length frequency distributions suggest an increase in size between consecutive seasons supporting the hypothesis that migration is a feeding strategy and a return to tropical waters of origin for spawning. Our study shows that the temperature of intermediate waters is a key variable in determining the northward migration of the Atlantic pomfret whereas density‐dependence and surface climatic conditions trigger secondary effects on the migration pattern of this species.

Pollen flow between flowers of the same morph in invasive populations of Oxalis pes-caprae L. in the western Mediterranean region - J. Costa; V. Ferrero; M. Castro; A. Jorge; A. Afonso; J. Loureiro; S. Castro (Plant Biosystems, 2016)

Erratum to: Preliminary study on serum paraoxonase-1 status and chemokine (C-C motif) ligand 2 in hospitalized elderly patients with catheter-associated asymptomatic bacteriuria - S. Iftimie; A. García-Heredia; I. Pujol; F. Ballester; I. Fort-Gallifa; J. M. Simó; J. Joven; J. Camps; A. Castro (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Preliminary study on serum paraoxonase-1 status and chemokine (C-C motif) ligand 2 in hospitalized elderly patients with catheter-associated asymptomatic bacteriuria - S. Iftimie; A. García-Heredia; I. Pujol; F. Ballester; I. Fort-Gallifa; J. M. Simó; J. Joven; J. Camps; A. Castro (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Genetic pool structure of local apple cultivars from Portugal assessed by microsatellites - V. Ferreira; A. M. Ramos-Cabrer; V. Carnide; O. Pinto-Carnide; A. Assunção; A. Marreiros; R. Rodrigues; S. Pereira-Lorenzo; I. Castro (Tree Genetics & Genomes, 2016)

Rhizobacterial communities associated with the flora of three serpentine outcrops of the Iberian Peninsula - Vanessa Álvarez-López; Ángeles Prieto-Fernández; Cristina Becerra-Castro; Carmela Monterroso; Petra S. Kidd (Plant and Soil, 2016)

Effect of galactofucan sulfate of a brown seaweed on induced hepatotoxicity in rats, sodium pentobarbital-induced sleep, and anti-inflammatory activity - Luiza Sheyla Evenni P. Will Castro; Allisson J. Gomes Castro; Marília da S. Nascimento Santos; Thuane de Sousa Pinheiro; Kahena de Quevedo Florentin; Luciana G. Alves; Eliane Marinho Soriano; Renata Mendonça Araújo; Edda Lisboa Leite (Journal of Applied Phycology, 2016)

Quality of the Solimões River water for domestic use by the riverine community situated in Manacapuru-Amazonas-Brazil - N. G. P. Pantoja; L. M. Castro; S. D. Rocha; J. A. Silva; J. S. P. Ribeiro; A. R. Donald; L. M. Silva; T. C. S. Oliveira (Environmental Science and Pollution Research, 2016)

Brazilian recreational fisheries: current status, challenges and future direction - K. M. F. Freire; R. A. Tubino; C. Monteiro‐Neto; M. F. Andrade‐Tubino; C. G. Belruss; A. R. G. Tomás; S. L. S. Tutui; P. M. G. Castro; L. S. Maruyama; A. C. Catella; D. V. Crepaldi; C. R. A. Daniel; et al. (Fisheries Management and Ecology, 2016)
Recreational fisheries in Brazil have increased in importance and attracted many foreign recreational fishers. The objectives of this article were to summarise the available data on Brazilian recreational fisheries, to discuss some of their features and to analyse how they are performing in different regions compared with international trends. A review of published and unpublished sources together with data from recreational fishing licences was used. The participation rate was low (0.9%). Overall, there was a high diversity of fish species, with the following species/group of species repeatedly reported: Menticirrhus spp., Centropomus spp., Cynoscion spp., and Micropogonias furnieri (marine/estuarine water), and Cichla spp., Hoplias malabaricus , and Piaractus mesopotamicus , together with the introduced Oreochromis niloticus and Coptodon rendalli (fresh water). The north‐eastern region differs from the other regions: fishing occurs mostly in marine waters and fishers acquire mainly shore‐based licences, have minimum fishing expenditures and rarely release fishes. There is no estimate of the total harvest or economic value. Conflicts include catch‐and‐release‐oriented freshwater and marine recreational fishers vs consumption‐oriented coastal fishers, tournament participants vs non‐participants, commercial fishers and other leisure activities, pollution, ports, species introductions and translocations, protected areas, and federal and state laws. Cases of smooth shifts from artisanal to recreational fishing were detected, possibly associated with changes in the societal relationship with natural resources.

Mine land valorization through energy maize production enhanced by the application of plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi - Helena Moreira; Sofia I. A. Pereira; Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Environmental Science and Pollution Research, 2016)

Do the invasive trees, Ailanthus altissima and Robinia pseudoacacia, alter litterfall dynamics and soil properties of riparian ecosystems in Central Spain? - S. Medina-Villar; P. Castro-Díez; A. Alonso; I. Cabra-Rivas; I. M. Parker; E. Pérez-Corona (Plant and Soil, 2015)

Regional climate modelling in CLARIS-LPB: a concerted approach towards twentyfirst century projections of regional temperature and precipitation over South America - E. Sánchez; S. Solman; A. R. C. Remedio; H. Berbery; P. Samuelsson; R. P. Da Rocha; C. Mourão; L. Li; J. Marengo; M. de Castro; D. Jacob (Climate Dynamics, 2015)

Acceptability and Cultural Appropriateness of Self-Help Booklets for Relapse Prevention in Puerto Rico - Nicole S. Menzie; Vani N. Simmons; Gwendolyn P. Quinn; Diana B. Diaz; Barbara Piñeiro; Julio Jimenez; Eida Castro; Thomas H. Brandon (Journal of Cancer Education, 2015)

New insights towards the establishment of phycocyanin concentration thresholds considering species-specific variability of bloom-forming cyanobacteria - Inês P. E. Macário; Bruno B. Castro; Maria I. S. Nunes; Sara C. Antunes; Cristina Pizarro; Carla Coelho; Fernando Gonçalves; Daniela R. de Figueiredo (Hydrobiologia, 2015)

Isotopic variation in five species of stream fishes under the influence of different land uses - D. R. Carvalho; D. Castro; M. Callisto; M. Z. Moreira; P. S. Pompeu (Journal of Fish Biology, 2015)
The aim of this study was to test if changes in land use alter the isotopic signature of fish species, promoting changes in the trophic position and food resource partitioning between these consumers. Three different systems were investigated: pasture streams ( n = 3), streams in sugar cane plantations ( n = 3) and reference streams ( n = 3). Fish species Aspidoras fuscoguttatus , Astyanax altiparanae , Characidium zebra , Hisonotus piracanjuba and Knodus moenkhausii were selected, and their nitrogen and carbon isotopic compositions were estimated to assess changes in the trophic level and partitioning of food items consumed. The composition of δ 13 C (‰) only differed among the land use categories for A. altiparanae , H. piracanjuba and K. moenkhausii. Resource partitioning was different for all species, with changes in the sources or proportions they consumed in each land use category, but only A. altiparanae introduced new food sources in large quantity in altered land uses. It is important to note, however, that the results from the resource partitioning analysis are limited due to large overlapping of isotopic signatures between the analysed food resources. All fish species exhibited variation in δ 15 N (‰), with the highest values found in streams under sugar cane or pasture influence. Despite the variation in nitrogen isotopic values, only C. zebra and H. piracanjuba displayed changes in trophic level. Therefore, it is believed that the increase in the δ 15 N (‰) value of the individuals collected in streams under the influence of sugar cane or pasture was due to the greater influence of livestock dung and chemical and organic fertilizers. The results also highlight the importance of studying consumer species along with all forms of resources available at each location separately, because the signatures of these resources also vary within different land uses.

Cannabidiol Exposure During Neuronal Differentiation Sensitizes Cells Against Redox-Active Neurotoxins - Patrícia Schönhofen; Liana M. de Medeiros; Ivi Juliana Bristot; Fernanda M. Lopes; Marco A. De Bastiani; Flávio Kapczinski; José Alexandre S. Crippa; Mauro Antônio A. Castro; Richard B. Parsons; Fábio Klamt (Molecular Neurobiology, 2015)

Expression of intercellular lipid transport and cholesterol metabolism genes in eggs and early larvae stages of turbot, Scophthalmus maximus, a marine aquaculture species - I. Cunha; S. Galante-Oliveira; E. Rocha; R. Urbatzka; L. F. C. Castro (Marine Biology, 2015)

Rhizobacteria isolated from a metal-polluted area enhance plant growth in zinc and cadmium-contaminated soil - S. I. A. Pereira; L. Barbosa; P. M. L. Castro (International Journal of Environmental Science and Technology, 2015)

Detection of a new QTL/gene for growth habit in chickpea CaLG1 using wide and narrow crosses - L. Ali; S. Azam; J. Rubio; H. Kudapa; E. Madrid; R. K. Varshney; P. Castro; W. Chen; J. Gil; T. Millan (Euphytica, 2015)

Dispersive liquid–liquid microextraction and HPLC to analyse fluoxetine and metoprolol enantiomers in wastewaters - Ana R. Ribeiro; Virgínia M. F. Gonçalves; Alexandra S. Maia; Cláudia Ribeiro; Paula M. L. Castro; Maria E. Tiritan (Environmental Chemistry Letters, 2015)

Evaluation of the Impact of Different Soil Salinization Processes on Organic and Mineral Soils - J. Jesus; F. Castro; A. Niemelä; Maria-Teresa Borges; A. S. Danko (Water, Air, & Soil Pollution, 2015)

Assessing the effect of domain size over the Caribbean region using the PRECIS regional climate model - Abel Centella-Artola; Michael A. Taylor; Arnoldo Bezanilla-Morlot; Daniel Martinez-Castro; Jayaka D. Campbell; Tannecia S. Stephenson; Alejandro Vichot (Climate Dynamics, 2015)

An environmentally friendly method for the determination of triazine herbicides in estuarine seawater samples by dispersive liquid–liquid microextraction - N. Rodríguez-González; E. Beceiro-González; M. J. González-Castro; S. Muniategui-Lorenzo (Environmental Science and Pollution Research, 2015)

Diversity and characterization of culturable bacterial endophytes from Zea mays and their potential as plant growth-promoting agents in metal-degraded soils - S. I. A. Pereira; P. M. L. Castro (Environmental Science and Pollution Research, 2014)

Fresh and vitrified bovine preantral follicles have different nutritional requirements during in vitro culture - S. V. Castro; A. A. Carvalho; C. M. G. Silva; F. W. Santos; C. C. Campello; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Banking, 2014)

Toward hemodynamic diagnosis of carotid artery stenosis based on ultrasound image data and computational modeling - Luísa C. Sousa; Catarina F. Castro; Carlos C. António; André Miguel F. Santos; Rosa Maria dos Santos; Pedro Miguel A. C. Castro; Elsa Azevedo; João Manuel R. S. Tavares (Medical & Biological Engineering & Computing, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Exploring N-Acylhydrazone Derivatives Against Clinical Resistant Bacterial Strains - Andressa C. Lannes; Bruno Leal; Juliana S. Novais; Viviane Lione; Georgia C. T. S. Monteiro; André L. Lourenço; Plínio C. Sathler; Alessandro K. Jordão; Carlos R. Rodrigues; Lúcio M. Cabral; Anna Claudia Cunha; Vinicius Campos; et al. (Current Microbiology, 2014)

Fucose-containing sulfated polysaccharides from brown macroalgae Lobophora variegata with antioxidant, anti-inflammatory, and antitumoral effects - Luiza Sheyla E. P. Will Castro; Thuane S. Pinheiro; Allisson J. G. Castro; Celina M. P. G. Dore; Naissandra B. da Silva; Monique Gabriela das C. Faustino Alves; Marilia S. Nascimento Santos; Edda Lisboa Leite (Journal of Applied Phycology, 2014)

Electrochemical removal of synthetic textile dyes from aqueous solutions using Ti/Pt anode: role of dye structure - Cynthia K. C. Araújo; Gustavo R. Oliveira; Nedja S. Fernandes; Carmem L. P. S. Zanta; Suely Souza Leal Castro; Djalma R. da Silva; Carlos A. Martínez-Huitle (Environmental Science and Pollution Research, 2014)

Phytomanagement of Cd-contaminated soils using maize (Zea mays L.) assisted by plant growth-promoting rhizobacteria - Helena Moreira; Ana P. G. C. Marques; Albina R. Franco; António O. S. S. Rangel; Paula M. L. Castro (Environmental Science and Pollution Research, 2014)

Rhizobacterial inoculants can improve nickel phytoextraction by the hyperaccumulator Alyssum pintodasilvae - M. I. Cabello-Conejo; C. Becerra-Castro; A. Prieto-Fernández; C. Monterroso; A. Saavedra-Ferro; M. Mench; P. S. Kidd (Plant and Soil, 2014)

Coyotes, deer, and wildflowers: diverse evidence points to a trophic cascade - Nickolas M. Waser; Mary V. Price; Daniel T. Blumstein; S. Reneé Arózqueta; Betsabé D. Castro Escobar; Richard Pickens; Alessandra Pistoia (The Science of Nature, 2014)

A genome-wide association study on copy-number variation identifies a 11q11 loss as a candidate susceptibility variant for colorectal cancer - C. Fernandez-Rozadilla; J. B. Cazier; I. Tomlinson; A. Brea-Fernández; M. J. Lamas; M. Baiget; L. A. López-Fernández; J. Clofent; L. Bujanda; D. Gonzalez; L. de Castro; K. Hemminki; et al. (Human Genetics, 2014)

Acquisition of resistant microorganisms and infections in HIV-infected patients admitted to the ICU - N. Cobos-Trigueros; M. Rinaudo; M. Solé; P. Castro; J. Pumarol; C. Hernández; S. Fernández; J. M. Nicolás; J. Mallolas; J. Vila; L. Morata; J. M. Gatell; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Is the effect of farming practices on songbird communities landscape dependent? A case study of olive groves in southern Spain - J. C. Castro-Caro; I. C. Barrio; F. S. Tortosa (Journal of Ornithology, 2014)

Early Spanish meteorological records (1780–1850) - F. Domínguez‐Castro; J. M. Vaquero; F. S. Rodrigo; A. M. M. Farrona; M. C. Gallego; R. García‐Herrera; M. Barriendos; A. Sanchez‐Lorenzo (International Journal of Climatology, 2014)
This article summarizes recent efforts on early instrumental data recovery in Spain conducted under the Salvà‐Sinobas project. We have retrieved and digitized more than 100 000 meteorological observations prior to 1850 in Spain. This data set contains measurements of air temperature, atmospheric pressure, wind direction and state of the atmosphere in 16 places located in Iberia and the Balearic Islands. Most of the observations are made on a daily basis. However, monthly and annual information has also been retrieved. The time coverage of the series is not homogeneous, with the earliest records starting in Seville in 1780. Prior to this work only two series were available in Spain (i.e. Cadiz and Barcelona), so this data set represents a great advance in the early data availability for Spain. Due to the lack of metadata in most of the series, their interpretation must be made with caution. © 2013 Royal Meteorological Society

Oxidative stress parameters in blood, liver, and kidney of diabetic rats treated with curcumin and/or insulin - Heloisa Einloft Palma; Patrícia Wolkmer; Miguel Gallio; Marcos M. B. Corrêa; Roberta Schmatz; Gustavo R. Thomé; Luciane B. Pereira; Verônica S. P. Castro; Andréia B. Pereira; Andressa Bueno; Lizielle S. de Oliveira; Debora Rosolen; et al. (Molecular and Cellular Biochemistry, 2014)

B-lymphocyte tolerance and effector function in immunity and autoimmunity - Wasif N. Khan; Jacqueline A. Wright; Eden Kleiman; Justin C. Boucher; Iris Castro; Emily S. Clark (Immunologic Research, 2013)

Influence of Several Sources and Amounts of Iron on DNA, Lipid and Protein Oxidative Damage During Anaemia Recovery - Javier Díaz-Castro; Yenela García; Inmaculada López-Aliaga; María J. M. Alférez; Silvia Hijano; Aurora Ramos; Margarita S. Campos (Biological Trace Element Research, 2013)

Fish Traders as Key Actors in Fisheries: Gender and Adaptive Management - Sara Fröcklin; Maricela de la Torre-Castro; Lars Lindström; Narriman S. Jiddawi (Ambio, 2013)

Body live weight and milk production parameters in the Majorera and Palmera goat breeds from the Canary Islands: influence of weight loss - Joana R. Lérias; Lorenzo E. Hernández-Castellano; Antonio Morales-delaNuez; Susana S. Araújo; Noemí Castro; Anastasio Argüello; Juan Capote; André M. Almeida (Tropical Animal Health and Production, 2013)

Genetic map of the primocane-fruiting and thornless traits of tetraploid blackberry - P. Castro; E. T. Stafne; J. R. Clark; K. S. Lewers (Theoretical and Applied Genetics, 2013)

Initial development of a set of introgression lines from Solanum peruvianum PI 126944 into tomato: exploitation of resistance to viruses - O. Julián; J. Herráiz; S. Corella; I. di-Lolli; S. Soler; M. J. Díez; A. Pérez-de-Castro (Euphytica, 2013)

Evaluation of an ensemble of regional climate model simulations over South America driven by the ERA-Interim reanalysis: model performance and uncertainties - Silvina A. Solman; E. Sanchez; P. Samuelsson; R. P. da Rocha; L. Li; J. Marengo; N. L. Pessacg; A. R. C. Remedio; S. C. Chou; H. Berbery; H. Le Treut; M. de Castro; et al. (Climate Dynamics, 2013)

Echeveria yalmanantlanensis (Crassulaceae): A new species from Cerro Grande, Sierra de Manantlán, western Mexico - J. Antonio Vázquez-García; David Jimeno-S.; Ramón Cuevas-G.; Miguel Cházaro-B.; Miguel A. Muñiz-Castro (Brittonia, 2013)

Tissue expression of PPAR-alpha isoforms in Scophthalmus maximus and transcriptional response of target genes in the heart after exposure to WY-14643 - R. Urbatzka; S. Galante-Oliveira; E. Rocha; L. F. C. Castro; I. Cunha (Fish Physiology and Biochemistry, 2013)

Reduced glutathione export during programmed cell death of Neurospora crassa - Andreia S. Fernandes; Ana Castro; Arnaldo Videira (Apoptosis, 2013)

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

PAH air pollution at a Portuguese urban area: carcinogenic risks and sources identification - K. Slezakova; J. C. M. Pires; D. Castro; M. C. M. Alvim-Ferraz; C. Delerue-Matos; S. Morais; M. C. Pereira (Environmental Science and Pollution Research, 2013)

Mapping wild pear trees ( Pyrus bourgaeana ) in Mediterranean forest using high-resolution QuickBird satellite imagery - S. Arenas-Castro; Y. Julien; J.C. Jiménez-Muñoz; J.A. Sobrino; J. Fernández-Haeger; D. Jordano-Barbudo (International Journal of Remote Sensing, 2013)

Storage and eruption of near-liquidus rhyolite magma at Cordón Caulle, Chile - Jonathan M. Castro; C. Ian Schipper; Sebastian P. Mueller; A. S. Militzer; Alvaro Amigo; Carolina Silva Parejas; Dorrit Jacob (Bulletin of Volcanology, 2013)

Effect of the metals iron, copper and silver on fluorobenzene biodegradation by Labrys portucalensis - Irina S. Moreira; Catarina L. Amorim; Maria F. Carvalho; António C. Ferreira; Carlos M. Afonso; Paula M. L. Castro (Biodegradation, 2013)

Improving performance of Cytisus striatus on substrates contaminated with hexachlorocyclohexane (HCH) isomers using bacterial inoculants: developing a phytoremediation strategy - C. Becerra-Castro; Á. Prieto-Fernández; P. S. Kidd; N. Weyens; B. Rodríguez-Garrido; M. Touceda-González; M. J. Acea; J. Vangronsveld (Plant and Soil, 2013)

Effect of diflubenzuron on the development of Pinus pinaster seedlings inoculated with the ectomycorrhizal fungus Pisolithus tinctorius - Miguel A. Ramos; Nadine R. Sousa; Albina R. Franco; Vítor Costa; Rui S. Oliveira; Paula M. L. Castro (Environmental Science and Pollution Research, 2013)

Can the red palm mite threaten the Amazon vegetation? - Manoel G. C. Gondim; Tatiane M. M. G. Castro; Alberto L. Marsaro; Denise Navia; José W. S. Melo; Peterson R. Demite; Gilberto J. de Moraes (Systematics and Biodiversity, 2012)

Assessment of spermatogenesis and plasma sex steroids in a seasonal breeding teleost: a comparative study in an area of influence of a tributary, downstream from a hydroelectric power dam, Brazil - Fabricio F. T. Domingos; Ralph G. Thomé; Fabio P. Arantes; Antonio Carlos S. Castro; Yoshimi Sato; Nilo Bazzoli; Elizete Rizzo (Fish Physiology and Biochemistry, 2012)

Performance of a multi-RCM ensemble for South Eastern South America - A. F. Carril; C. G. Menéndez; A. R. C. Remedio; F. Robledo; A. Sörensson; B. Tencer; J.-P. Boulanger; M. de Castro; D. Jacob; H. Le Treut; L. Z. X. Li; O. Penalba; et al. (Climate Dynamics, 2012)

Connection between NAO, weather types and precipitation in León, Spain (1948–2008) - S. Fernández‐González; S. del Río; A. Castro; A. Penas; M. Fernández‐Raga; A. I. Calvo; R. Fraile (International Journal of Climatology, 2012)
The variability of winter precipitation in the west of the Iberian Peninsula is strongly affected by the North Atlantic Oscillation (NAO). This study focuses on identifying the relationship that exists between precipitation registered in the city of León (in northwestern Spain), the NAO index and the associated weather type during the same period. In order to achieve this objective, the prevailing weather type has been calculated for each day in León from January 1948 to March 2009, using the objective Lamb Weather Types classification method. The most significant results appear in winter (from December to March). During these months an increase has been observed in the frequency of ‘anticyclonic’ weather type (A) (very dry), and a decrease in the ‘cyclonic’ (C), ‘south‐westerly’ (SW) and ‘westerly’ (W) types (the three rainiest weather types). The positive trend in the NAO index could be the main cause of the decrease in the frequency of the three rainiest weather types (C, SW and W) and therefore, responsible for the relevant decline in winter precipitation observed in the city of León. The high correlation coefficients between the NAO index, the frequency of the three rainiest weather types and winter precipitation suggests an interesting method to forecast rainfall. Using a binary logistic regression model, a downscaling model for daily precipitation has been obtained based on the weather types and the NAO index. The daily results obtained for the winter months are good (TSS = 0.64) bearing in mind that only sea level pressure data were used in the logistic model. Copyright © 2011 Royal Meteorological Society

Mapping resistance genes conferring tolerance to RWA (Diuraphis noxia) in barley (Hordeum vulgare) - E. Tocho; M. Ricci; M. S. Tacaliti; D. O. Giménez; A. Acevedo; U. Lohwasser; A. Börner; A. M. Castro (Euphytica, 2012)

Mycorrhizal symbiosis affected by different genotypes of Pinus pinaster - Nadine R. Sousa; Miguel A. Ramos; Albina R. Franco; Rui S. Oliveira; Paula M. L. Castro (Plant and Soil, 2012)

Score to identify the severity of adult patients with influenza A (H1N1) 2009 virus infection at hospital admission - A. Capelastegui; J. M. Quintana; A. Bilbao; P. P. España; O. Garin; J. Alonso; J. Astray; R. Cantón; J. Castilla; A. Castro; M. Delgado-Rodríguez; P. Godoy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Degradation of difluorobenzenes by the wild strain Labrys portucalensis - Irina S. Moreira; Catarina L. Amorim; Maria F. Carvalho; Paula M. L. Castro (Biodegradation, 2012)

Responses to excess iron in sweet potato: impacts on growth, enzyme activities, mineral concentrations, and anatomy - Janete M. Adamski; Rodrigo Danieloski; Sidnei Deuner; Eugênia J. B. Braga; Luis A. S. de Castro; José A. Peters (Acta Physiologiae Plantarum, 2012)

Confronting Feedbacks of Degraded Marine Ecosystems - Magnus Nyström; Albert V. Norström; Thorsten Blenckner; Maricela de la Torre-Castro; Johan S. Eklöf; Carl Folke; Henrik Österblom; Robert S. Steneck; Matilda Thyresson; Max Troell (Ecosystems, 2012)

Recent Progress in Interfacial Tissue Engineering Approaches for Osteochondral Defects - Nathan J. Castro; S. Adam Hacking; Lijie Grace Zhang (Annals of Biomedical Engineering, 2012)

Adenosine Deaminase Activity in Serum and Lymphocytes of Rats Infected with Sporothrix schenckii - Verônica S. P. Castro; Victor C. Pimentel; Aleksandro S. Da Silva; Gustavo R. Thomé; Patrícia Wolkmer; Jorge L. C. Castro; Márcio M. Costa; Cássia B. da Silva; Daniele C. Oliveira; Sydney H. Alves; Maria R. C. Schetinger; Sonia T. A. Lopes; et al. (Mycopathologia, 2012)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Matayba obovata, a new species of Matayba sect. Matayba (Sapindaceae) from Brazil - Rubens L. Gayoso Coelho; Vinicius Castro Souza; María S. Ferrucci (Brittonia, 2012)

Sea surface temperature anomalies, seasonal cycle and trend regimes in the Eastern Pacific coast - A. Ramos-Rodríguez; D. B. Lluch-Cota; S. E. Lluch-Cota; A. Trasviña-Castro (Ocean Science, 2012)
We used the extended reconstruction of sea surface temperature (ERSST) to analyze the variation of surface temperature and the seasonal cycle along the coast of the eastern Pacific (60° N–60° S, 61 pixels alongshore) from 1950 to 2010 (732 months). First, we analyzed the monthly anomalies and looked for a relationship of such anomalies with total solar irradiance (TSI) and then the Regime Shift Detector (RSD) was applied to detect possible temperature regimes in the series. Afterwards, we calculated a yearly temperature range per pixel (amplitude of seasonal cycle) and through the subtraction of a latitudinal theoretical curve of temperature based on solar irradiance, the residuals of the seasonal cycle were obtained. The results showed an almost complete spatial synchrony and dominance of negative anomalies from 1950 to mid-late 1970's, with a switch to near-zero and positive anomalies that lasted up to late 1990's when a new shift to negative values was detected. Such a shift lasted until the early 2000's when positive anomalies appeared again but there was a change to negative anomalies in the late 2000's. These results were supported by the RSD. The TSI variability shows a clear relationship with that of sea surface temperature anomalies and with the regime changes. This is probably due to a difference in the amount of energy received from the sun. Comparing the "cool regime" versus the "warm regime", the second one received 0.39% more energy (approximately 3 × 108 J m−2) from the sun. Seasonal cycles show larger ranges at northern latitudes (>40° N), northern tropical-temperate transition zone (20°–26° N) and in the tropical-equatorial band (0°–30° S). The smallest ranges occur at 0°–16° N and 50°–60° S. The residuals (seasonal minus the theoretical curve) indicated a clear modulation due to advection by ocean currents.

Agrobacterium rhizogenes-dependent production of transformed roots from foliar explants of pepper (Capsicum annuum): a new and efficient tool for functional analysis of genes - J. Aarrouf; P. Castro-Quezada; S. Mallard; B. Caromel; Y. Lizzi; V. Lefebvre (Plant Cell Reports, 2012)

Wind-Direction Effects on Urban-Type Flows - Jean Claus; O. Coceal; T. Glyn Thomas; S. Branford; S. E. Belcher; Ian P. Castro (Boundary-Layer Meteorology, 2012)

Effect of the insect growth regulator diflubenzuron on the predator Podisus nigrispinus (Heteroptera: Pentatomidae) - Ancidériton A. Castro; Mabio C. Lacerda; Teresinha V. Zanuncio; Francisco de S. Ramalho; Ricardo A. Polanczyk; José E. Serrão; José C. Zanuncio (Ecotoxicology, 2012)

First description of Edwardsiella tarda in Senegalese sole, Solea senegalensis (Kaup) - N Castro; A. E. Toranzo; S. Devesa; A. González; S. Nuñez; B. Magariños (Journal of Fish Diseases, 2012)

Functional dissimilarity of melanomacrophage centres in the liver and spleen from females of the teleost fish Prochilodus argenteus - H. J. Ribeiro; M. S. Procópio; J. M. M. Gomes; F. O. Vieira; R. C. Russo; K. Balzuweit; H. Chiarini-Garcia; Antonio Carlos Santana Castro; E. Rizzo; José Dias Corrêa (Cell and Tissue Research, 2011)

The natural diterpene ent-16β-17α-dihydroxykaurane down-regulates Bcl-2 by disruption of the Ap-2α/Rb transcription activating complex and induces E2F1 up-regulation in MCF-7 cells - Alvaro Morales; Annamil Alvarez; Francisco Arvelo; Alírica I. Suárez; Reinaldo S. Compagnone; Iván Galindo-Castro (Apoptosis, 2011)

Variability of the monthly European temperature and its association with the Atlantic sea‐surface temperature from interannual to multidecadal scales - S. R. Gámiz‐Fortis; M. J. Esteban‐Parra; D. Pozo‐Vázquez; Y. Castro‐Díez (International Journal of Climatology, 2011)
The relationships between the main patterns of variability of the Atlantic sea‐surface temperatures (SSTs) and the European land‐surface temperatures (LSTs) at interannual‐to‐multidecadal time scales are investigated along the period 1872–2004. Principal component analysis (PCA) is used firstly to obtain the main spatio‐temporal patterns of variability of the LSTs and SSTs. Singular Spectral Analysis (SSA) is then used to decompose the time series associated with these patterns into nonlinear trends and quasi‐periodic oscillations, searching for common oscillatory modes to the SSTs and LSTs. The potential predictability of the LSTs based on the SSTs is also analysed. Regarding the SSA results, three robust oscillations of periods around 13.7, 7.5 and 5.2 years, present both in the Atlantic SSTs and north‐western European LSTs, were isolated. These oscillations were found to be associated mainly with a quadripolar SST pattern in the North Atlantic region, usually related to the North Atlantic Oscillation (NAO) atmospheric mode of variability. The predictability study revealed that the SSTs of the Atlantic Ocean are able to account for about 12% of the north‐western European LSTs variance. Additionally, an oscillatory component with period around 3.6 years was identified, but no significant connection between SST and LST was found for this mode. In addition, at this time scale, we find that the El Niño‐Southern Oscillation (ENSO) is leading the Atlantic SST quadripolar pattern by 6 months. Finally, the analysis of the nonlinear trends showed the presence of oscillations with periods around 60–100 years, both in the SSTs and LSTs. At these later time scales, our results reveal that the multidecadal behaviour of the southern European LSTs is related to Atlantic Multidecadal Oscillation (AMO) during the period 1872–1940, unlike the northern and eastern European LSTs, while, during the period 1941–2004, the AMO sign seems to be present in whole Europe. Copyright © 2010 Royal Meteorological Society

Heavy Metal Accumulation in Plant Species Indigenous to a Contaminated Portuguese Site: Prospects for Phytoremediation - Helena Moreira; Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Water, Air, & Soil Pollution, 2011)

Soluble Fas and Fas ligand in HIV/HCV coinfected patients and impact of HCV therapy - M. Guzmán-Fulgencio; J. Berenguer; M. García-Álvarez; D. Micheloud; J. C. López; J. Cosín; I. Fernández de Castro; P. Catalán; P. Miralles; S. Resino (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Morpho-physiology and maize grain yield under periodic soil flooding in successive selection cycles - T. Corrêa de Souza; P. César Magalhães; F. José Pereira; E. Mauro de Castro; S. Netto Parentoni (Acta Physiologiae Plantarum, 2011)

Letter to the Editor in Chief: Rebuttal to the Letter to the Editor in Chief by Jörg Rinklebe, Rainer Wennrich, Sibylle Mothes Concerning the Article “A Simple and Accurate Method to Measure Total Gaseous Mercury Concentrations in Unsaturated Soils” by Moore et al., DOI:10.1007/s11270-010-0691-7 - Christopher W. Moore; Mark S. Castro; Steven B. Brooks (Water, Air, & Soil Pollution, 2011)

Erratum to: A Simple and Accurate Method to Measure Total Gaseous Mercury Concentrations in Unsaturated Soils - Christopher W. Moore; Mark S. Castro; Steven B. Brooks (Water, Air, & Soil Pollution, 2011)

A Simple and Accurate Method to Measure Total Gaseous Mercury Concentrations in Unsaturated Soils - Christopher. W. Moore; Mark S. Castro; Steven B. Brooks (Water, Air, & Soil Pollution, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Evaluation of the Sub-lethal Toxicity of Bleached Kraft Pulp Mill Effluent to Carassius auratus and Dicentrarchus labrax - Mário S. Diniz; Ruth Pereira; Ana C. Freitas; Teresa A. P. Rocha-Santos; Luisa Castro; Isabel Peres; Armando C. Duarte (Water, Air, & Soil Pollution, 2011)

Oxoquinoline Derivatives: Identification and Structure–Activity Relationship (SAR) Analysis of New Anti-HSV-1 Agents - Paula A. Abreu; Viveca A. G. G. da Silva; Fernanda C. Santos; Helena C. Castro; Cecília S. Riscado; Mariana T. de Souza; Camilly P. Ribeiro; Juliana E. Barbosa; Cláudio C. C. dos Santos; Carlos R. Rodrigues; Viviane Lione; Bianca A. M. Correa; et al. (Current Microbiology, 2011)

Morphological, morphometric, meristic and osteological evidence for two species of hake (Actinopterygii: Gadiformes: Merluccius ) in Argentinean waters - J. M. Díaz de Astarloa; S. I. Bezzi; M. González Castro; E. Mabragaña; D. Hernández; S. M. Delpiani; D. E. Figueroa; M. B. Cousseau; M. Y. Deli Antoni; L. Tringali (Journal of Fish Biology, 2011)
Morphologically, both classic and landmark‐based morphometry and meristic analyses of 241 specimens of Merluccius , along with the re‐examination of six paratype specimens of Merluccius hubbsi , the holotype and three paratypes of Merluccius patagonicus and the syntype of Merluccius australis revealed the presence of only two species of Merluccius in Argentinean waters. Internal structures (hyomandibula, urohyal and sagitta otolith) of M. hubbsi were compared to those reported for M. patagonicus and were shown to have identical morphology. Type specimens of M. patagonicus showed a complete overlap in morphometric and meristic characters with M. hubbsi , whereas M. australis had a greater number of second dorsal and anal‐fin rays, and more lateral‐line scales. In addition, M. australis had a smaller eye and longer snout than M. hubbsi and M. patagonicus . The results indicate that there is no evidence for a third hake species in Argentinean waters. Merluccius patagonicus is a synonym of M. hubbsi .

RETRACTED: Remediation of Heavy Metal Contaminated Soils: An Overview of Site Remediation Techniques - Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Critical Reviews in Environmental Science and Technology, 2011)

Anti-inflammatory properties of Doxycycline and Minocycline in experimental models: an in vivo and in vitro comparative study - Liz M. Leite; Antônio Germano G. Carvalho; Pollyanna L. F. Tavares Ferreira; Igor Xavier Pessoa; Danilo O. Gonçalves; Amanda de Araújo Lopes; Jean Guilherme dos Santos Góes; Victor Costa de Castro Alves; Luzia Kalyne A. M. Leal; Gerly Anne Brito; Glauce S. B. Viana (Inflammopharmacology, 2011)

Determining subsampling effort for the development of a rapid bioassessment protocol using benthic macroinvertebrates in streams of Southeastern Brazil - Renata B. S. Oliveira; Riccardo Mugnai; Carolina M. Castro; Darcilio F. Baptista (Environmental Monitoring and Assessment, 2011)

Phylogeography and conservation of the bull shark (Carcharhinus leucas) inferred from mitochondrial and microsatellite DNA - S. A. Karl; A. L. F. Castro; J. A. Lopez; P. Charvet; G. H. Burgess (Conservation Genetics, 2011)

Synthesis, characterization, and application of modified silica in the removal and preconcentration of lead ions from natural river water - Guilherme Ferreira; Laercio Caetano; Renata S. D. Castro; Pedro Magalhães Padilha; Gustavo Rocha Castro (Clean Technologies and Environmental Policy, 2011)

Principal components analysis to evaluate ventilatory variability: comparison of athletes and sedentary men - R. R. T. Castro; M. Magini; S. Pedrosa; A. R. K. Sales; A. C. L. Nóbrega (Medical & Biological Engineering & Computing, 2011)

Identification of Nor-β-Lapachone Derivatives as Potential Antibacterial Compounds against Enterococcus faecalis Clinical Strain - André L. Lourenço; Paula A. Abreu; Bruno Leal; Eufrânio N. da Silva Júnior; Antonio V. Pinto; Maria do Carmo F. R. Pinto; Alessandra M. T. Souza; Juliana S. Novais; Marcela B. Paiva; Lucio M. Cabral; Carlos R. Rodrigues; Vitor F. Ferreira; et al. (Current Microbiology, 2011)

Anti-Leptospira sp. agglutinins in ewes in the Federal District, Brazil - Luiza de S. Seixas; Cristiano Barros de Melo; Rômulo C. Leite; Élvio C. Moreira; Concepta M. McManus; Márcio B. de Castro (Tropical Animal Health and Production, 2011)

Similar Intracellular Peptide Profile of TAP1/β2 Microglobulin Double-Knockout Mice and C57BL/6 Wild-Type Mice as Revealed by Peptidomic Analysis - Leandro M. Castro; Denise A. Berti; Lilian C. Russo; Verônica Coelho; Fábio C. Gozzo; Vitor Oliveira; Emer S. Ferro (The AAPS Journal, 2010)

The anticancer drug perillyl alcohol is a Na/K-ATPase inhibitor - Diogo G. Garcia; Lidia M. F. Amorim; Mauro V. de Castro Faria; Aline S. Freire; Ricardo E. Santelli; Clóvis O. Da Fonseca; Thereza Quirico-Santos; Patricia Burth (Molecular and Cellular Biochemistry, 2010)

Management of nursery practices for efficient ectomycorrhizal fungi application in the production of Quercus ilex - Rui S. Oliveira; Albina R. Franco; Miroslav Vosátka; Paula M. L. Castro (Symbiosis, 2010)

Quercetin restores plasma nitrite and nitroso species levels in renovascular hypertension - Marcelo F. Montenegro; Evandro M. Neto-Neves; Carlos A. Dias-Junior; Carla S. Ceron; Michele M. Castro; Valeria A. Gomes; Alexandre Kanashiro; Jose E. Tanus-Santos (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Eutrophication and macroalgal blooms in temperate and tropical coastal waters: nutrient enrichment experiments with Ulva spp. - MIRTA TEICHBERG; SOPHIA E. FOX; YLVA S. OLSEN; IVAN VALIELA; PAULINA MARTINETTO; OSCAR IRIBARNE; ELIZABETI YURIKO MUTO; MONICA A. V. PETTI; THAÏS N. CORBISIER; MARTÍN SOTO‐JIMÉNEZ; FEDERICO PÁEZ‐OSUNA; PAULA CASTRO; et al. (Global Change Biology, 2010)
Receiving coastal waters and estuaries are among the most nutrient‐enriched environments on earth, and one of the symptoms of the resulting eutrophication is the proliferation of opportunistic, fast‐growing marine seaweeds. Here, we used a widespread macroalga often involved in blooms, Ulva spp., to investigate how supply of nitrogen (N) and phosphorus (P), the two main potential growth‐limiting nutrients, influence macroalgal growth in temperate and tropical coastal waters ranging from low‐ to high‐nutrient supplies. We carried out N and P enrichment field experiments on Ulva spp. in seven coastal systems, with one of these systems represented by three different subestuaries, for a total of nine sites. We showed that rate of growth of Ulva spp. was directly correlated to annual dissolved inorganic nitrogen (DIN) concentrations, where growth increased with increasing DIN concentration. Internal N pools of macroalgal fronds were also linked to increased DIN supply, and algal growth rates were tightly coupled to these internal N pools. The increases in DIN appeared to be related to greater inputs of wastewater to these coastal waters as indicated by high δ 15 N signatures of the algae as DIN increased. N and P enrichment experiments showed that rate of macroalgal growth was controlled by supply of DIN where ambient DIN concentrations were low, and by P where DIN concentrations were higher, regardless of latitude or geographic setting. These results suggest that understanding the basis for macroalgal blooms, and management of these harmful phenomena, will require information as to nutrient sources, and actions to reduce supply of N and P in coastal waters concerned.

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

Oral and parenteral vaccines against Flavobacterium columnare: evaluation of humoral immune response by ELISA and in vivo efficiency in Nile tilapia (Oreochromis niloticus) - C. A. G. Leal; G. A. Carvalho-Castro; P. S. C. Sacchetin; C. O. Lopes; A. M. Moraes; H. C. P. Figueiredo (Aquaculture International, 2010)

Effects of dose and period of sewage sludge application on soil, tree and pasture components in a Pinus radiata D. Don silvopastoral system - A. Rigueiro-Rodríguez; S. Castro; M. R. Mosquera-Losada (Agroforestry Systems, 2010)

Changes in metabolic substrates during early development in anchoveta Engraulis ringens (Jenyns 1842) in the Humboldt Current - M. C. Krautz; S. Vásquez; L. R. Castro; M. González; A. Llanos-Rivera; S. Pantoja (Marine Biology, 2010)

Genetic, Biochemical, and Individual Responses of the Teleost Fish Carassius auratus to Uranium - Joana Lourenço; B. B. Castro; R. Machado; B. Nunes; S. Mendo; F. Gonçalves; R. Pereira (Archives of Environmental Contamination and Toxicology, 2010)

Antioxidant system activation by mercury in Pfaffia glomerata plantlets - N. S. Calgaroto; G. Y. Castro; D. Cargnelutti; L. B. Pereira; J. F. Gonçalves; L. V. Rossato; F. G. Antes; V. L. Dressler; E. M. M. Flores; M. R. C. Schetinger; F. T. Nicoloso (BioMetals, 2010)

Leaf litter traits of invasive species slow down decomposition compared to Spanish natives: a broad phylogenetic comparison - Oscar Godoy; Pilar Castro-Díez; Richard S. P. Van Logtestijn; Johannes H. C. Cornelissen; Fernando Valladares (Oecologia, 2010)

Downscaling extreme month-long anomalies in southern South America - C. G. Menéndez; M. de Castro; J.-P. Boulanger; A. D’Onofrio; E. Sanchez; A. A. Sörensson; J. Blazquez; A. Elizalde; D. Jacob; H. Le Treut; Z. X. Li; M. N. Núñez; et al. (Climatic Change, 2010)

Frequency distribution of XbaIG > T and HaeIIIT > C GLUT1 polymorphisms among different Brazilian ethnic groups - G. C. S. Costa; L. C. J. Alcantara; R. Azevedo; G. Muricy; S. H. Kashima; D. T. Covas; B. Galvão-Castro; S. R. Gadelha (Molecular Biology Reports, 2010)

Polychlorinated Biphenyls and Biotransformation Enzymes in Three Species of Sea Turtles from the Baja California Peninsula of Mexico - K. L. Richardson; M. Lopez Castro; S. C. Gardner; D. Schlenk (Archives of Environmental Contamination and Toxicology, 2010)

Effects of ECF-Kraft pulp mill effluent treated with fungi (Rhizopus oryzae) on reproductive steroids and liver CYP1A of exposed goldfish (Carassius auratus) - M. S. Diniz; I. Peres; L. Castro; A. C. Freitas; T. A. P. Rocha-Santos; P. M. Costa; R. Pereira; A. C. Duarte (Ecotoxicology, 2009)

Influence of Pseudomonas putida AF7 inoculation on soil enzymes - Célia Maria M. de Souza Silva; Vera Lúcia S. S. de Castro; Pablo Roberto de Oliveira; Aline de Holanda Nunes Maia (Ecotoxicology, 2009)

Remediation of Heavy Metal Contaminated Soils: Phytoremediation as a Potentially Promising Clean-Up Technology - Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Critical Reviews in Environmental Science and Technology, 2009)

Relationship Between pH and Stream Water Total Mercury Concentrations in Shenandoah National Park - C. W. Moore; B. J. Cosby; J. N. Galloway; M. S. Castro (Water, Air, & Soil Pollution, 2009)

Biology and life cycle of Amblyomma incisum (Acari: Ixodidae) - Matias Pablo J. Szabó; Lucas de F. Pereira; Márcio B. Castro; Marcos V. Garcia; Gustavo S. Sanches; Marcelo B. Labruna (Experimental and Applied Acarology, 2009)

First isolation of Tenacibaculum maritimum from wedge sole, Dicologoglossa cuneata (Moreau) - J R López; S Núñez; B Magariños; N Castro; J I Navas; R De La Herran; A E Toranzo (Journal of Fish Diseases, 2009)
The first isolation of Tenacibaculum maritimum from wedge sole, Dicologoglossa cuneata, is reported. The pathogen was recovered from ulcers of cultured fish, from three different outbreaks. The six isolates obtained were biochemically and serologically characterized and diagnosis was confirmed by polymerase chain reaction using specific primers and partial 16S rRNA gene sequencing. The isolates constituted a homogeneous phenotypic group; however, they belong to two of the different serotypes described within this species. A virulence evaluation of the isolates using Wedge sole fry was also performed.

High frequency of hemolytic and cytotoxic activity in Aeromonas spp. isolated from clinical, food and environmental in Rio de Janeiro, Brazil - Magda C. B. Castilho; Tatiana L. A. Castro; Viviane S. Araújo; Rosemere S. Trajano; Paula A. Santos; Paula M. C. Pimenta; Kely Lucheze; Janyne T. B. Melo; Aline M. Gonçalves; Raquel T. Nogueira; Maria Graças de Luna; Angela C. Freitas-Almeida (Antonie van Leeuwenhoek, 2009)

Observed tendencies in maximum and minimum temperatures in Zacatecas, Mexico and possible causes - Luis Brito‐Castillo; Sara C. Díaz Castro; Raúl S. Ulloa Herrera (International Journal of Climatology, 2009)
At a global level, warming caused by the increase in greenhouse gases has been reported in different parts of the world. This warming resulted in a reduction in the diurnal temperature range (DTR), caused by a faster rate of increase in minimum temperatures. However, the tendency toward warming is not obvious in Zacatecas, Mexico. The tendencies in maximum and minimum temperatures are partly linked to the state of the low frequency variability of large‐scale atmospheric flow patterns, as depicted by the 700‐mb geopotential height anomalies. Analyses of maximum and minimum temperatures from 23 climate stations, from 1963 to 2002, show that the DTR in southern Zacatecas is increasing from a rise in maximum temperatures and drop in minimum temperatures, while the DTR in northern Zacatecas is decreasing from a faster rate of decline in maximum temperatures than the increase in minimum temperatures. The regional series related to the F1 and F2 leading modes, after applying a Varimax‐rotated empirical orthogonal function analysis to the 23 DTR series, acceptably reproduce the north–south dipole of DTR changes, while the point‐correlation analysis between the two regional series, the 700‐mb geopotential height anomalies and the indices of Pacific Decadal Oscillation and Atlantic Multidecadal Oscillation indicate that the DTR in Zacatecas, Mexico is related to fluctuations in subtropical and extratropical circulations. Copyright © 2008 Royal Meteorological Society

The occurrence of Mt Barca flank eruption in the evolution of the NW periphery of Etna volcano (Italy) - S. Branca; P. Del Carlo; M. D. Lo Castro; E. De Beni; J. Wijbrans (Bulletin of Volcanology, 2009)

Mapping quantitative trait loci for growth responses to exogenously applied stress induced hormones in wheat - A. M. Castro; M. S. Tacaliti; D. Giménez; E. Tocho; O. Dobrovolskaya; A. Vasicek; M. Collado; J. W. Snape; A. Börner (Euphytica, 2008)

Molecular epidemiology of hepatitis B virus in an isolated Afro-Brazilian community - A. R. C. Motta-Castro; R. M. B. Martins; N. M. Araujo; C. Niel; G. B. Facholi; B. V. Lago; F. C. A. Mello; S. A. Gomes (Archives of Virology, 2008)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

The Effects of Tannery Wastewater on the Development of Different Plant Species and Chromium Accumulation in Phragmites australis - Cristina S. C. Calheiros; António O. S. S. Rangel; Paula M. L. Castro (Archives of Environmental Contamination and Toxicology, 2008)

An experimental test of the effects of inorganic sediment addition on benthic macroinvertebrates of a subtropical stream - Márlon de Castro Vasconcelos; Adriano S. Melo (Hydrobiologia, 2008)

Isozyme polymorphisms within Pyrenophora tritici-repentis population in Argentina - María Virginia Moreno; María S. Tacalitti; Ana M. Castro; Analía E. Perelló (World Journal of Microbiology and Biotechnology, 2008)

Growth of Bradyrhizobium sp. SEMIA 6144 in Response to Methylglyoxal: Role of Glutathione - E. Bianucci; A. Fabra; S. Castro (Current Microbiology, 2008)

Immunosuppressive properties of surfactant in alveolar macrophage NR8383 - J. Kerecman; S. B. Mustafa; M. M. Vasquez; P. S. Dixon; R. Castro (Inflammation Research, 2008)

Vaccination of turbot, Psetta maxima (L.), against the protozoan parasite Philasterides dicentrarchi : effects on antibody production and protection - M L Sanmartín; A Paramá; R Castro; S Cabaleiro; J Leiro; J Lamas; J L Barja (Journal of Fish Diseases, 2008)
The efficacy of a vaccine against the fish pathogen Philasterides dicentrarchi was evaluated in turbot by measuring the production of specific antibodies and duration of protection. Four groups of turbot were vaccinated twice, on days 0 and 30, with phosphate‐buffered saline, mineral oil adjuvant, antigen or antigen plus adjuvant. Specific serum antibodies were determined on day 0 and 1 month after the first and the second vaccinations. Protection was evaluated 1 month after the first vaccination and 1 and 5 months after the second vaccination. Serum antibody titres, measured by enzyme‐linked immunosorbent assay, and protection, assessed by challenges, increased significantly 1 month after the second vaccination in the group injected with antigen plus adjuvant and the protection lasted for at least a further 5 months in this group. The relative protection was 77% and 66% 1 and 5 months after the second vaccination, respectively. Administration of antigen or adjuvant separately had no effect on antibody response or protection. The results indicate that emulsion containing antigen plus adjuvant induced durable protection against P. dicentrarchi after the administration of the two vaccinations, and that this preparation can be used as a vaccine against the pathogen.

Population genetic structure of Earth's largest fish, the whale shark ( Rhincodon typus ) - A. L. F. CASTRO; B. S. STEWART; S. G. WILSON; R. E. HUETER; M. G. MEEKAN; P. J. MOTTA; B. W. BOWEN; S. A. KARL (Molecular Ecology, 2007)
Large pelagic vertebrates pose special conservation challenges because their movements generally exceed the boundaries of any single jurisdiction. To assess the population structure of whale sharks ( Rhincodon typus ), we sequenced complete mitochondrial DNA control regions from individuals collected across a global distribution. We observed 51 single site polymorphisms and 8 regions with indels comprising 44 haplotypes in 70 individuals, with high haplotype ( h = 0.974 ± 0.008) and nucleotide diversity (π = 0.011 ± 0.006). The control region has the largest length variation yet reported for an elasmobranch (1143–1332 bp). Phylogenetic analyses reveal no geographical clustering of lineages and the most common haplotype was distributed globally. The absence of population structure across the Indian and Pacific basins indicates that oceanic expanses and land barriers in Southeast Asia are not impediments to whale shark dispersal. We did, however, find significant haplotype frequency differences (amova, F ST = 0.107, P

Flow cytometric and cytogenetic analyses of Iberian Peninsula Festuca spp. - J. Loureiro; D. Kopecký; S. Castro; C. Santos; P. Silveira (Plant Systematics and Evolution, 2007)

A linearization technique for multi-species transport problems - Neyva M. L. Romeiro; Rigoberto G. S. Castro; Sandra M. C. Malta; Luiz Landau (Transport in Porous Media, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Sugar fermentation by Fusarium oxysporum to produce ethanol - E. Ruiz; I. Romero; M. Moya; S. Sánchez; V. Bravo; E. Castro (World Journal of Microbiology and Biotechnology, 2007)

Relationship Between Wetlands and Mercury in Brook Trout - Mark S. Castro; Robert H. Hilderbrand; Joe Thompson; A. Heft; S. E. Rivers (Archives of Environmental Contamination and Toxicology, 2007)

Glutamate Is Involved in Acid Stress Response in Bradyrhizobium sp. SEMIA 6144 (Arachis hypogaea L.) Microsymbiont - V. Natera; L. Sobrevals; A. Fabra; S. Castro (Current Microbiology, 2006)

Interspecific differentiation and intraspecific substructure in two closely related clupeids with extensive hybridization, Alosa alosa and Alosa fallax - P. Alexandrino; R. Faria; D. Linhares; F. Castro; M. Le Corre; R. Sabatié; J. L. Baglinière; S. Weiss (Journal of Fish Biology, 2006)
In this study, the evolutionary relationships within and among populations of European shads, Alosa alosa and Alosa fallax , was investigated. Screening of allelic variation across eight allozyme loci and sequencing 448 bp of the mtDNA cytochrome b gene in 14 rivers throughout the range of the species supported that the two taxa were independent lineages (1·3% net nucleotide divergence) despite extensive hybridization. Genetic diversity and structure was considerably higher in A. fallax than A. alosa and the former species revealed evidence of distinct lineages in the Mediterranean and Atlantic basins. A Bayesian clustering approach combined with gill raker counts verified that individuals of the two species could be assigned to their parent group with relatively high confidence. Evaluation of hybridization in the Lima and Mondego Rivers in Portugal provided evidence that introgression is extensive but is not currently obscuring (through hybrid swarming) the diagnosability of the two species.

Mean Flow and Turbulence Statistics Over Groups of Urban-like Cubical Obstacles - O. Coceal; T. G. Thomas; I. P. Castro; S. E. Belcher (Boundary-Layer Meteorology, 2006)

Different native arbuscular mycorrhizal fungi influence the coexistence of two plant species in a highly alkaline anthropogenic sediment - Rui S. Oliveira; Paula M. L. Castro; John C. Dodd; Miroslav Vosátka (Plant and Soil, 2006)

Characterization of Edwardsiella tarda strains isolated from turbot, Psetta maxima (L.) - N Castro; A E Toranzo; J L Barja; S Núñez; B Magariños (Journal of Fish Diseases, 2006)
The biochemical, serological and molecular characteristics of a group of 21 Edwardsiella tarda strains isolated from turbot, Psetta maxima , in two different areas of Europe were analysed and compared with a total of 13 strains of this bacterial species with different geographical and host origins. All the turbot isolates were biochemically identical to the E. tarda strains included as reference. The use of different techniques including microagglutination, dot blot and Western blot of lipopolysaccharides allowed us to determine that all the turbot isolates constitute an homogeneous and distinctive serological group. Genetic analysis by randomly amplified polymorphic DNA (RAPD) analysis demonstrated that although the E. tarda strains from turbot were compiled in a unique group using the primers P3 and P6, two clonal lineages could be detected when oligonucleotides P4 and P5 were employed.

Coat protein gene sequence of a Mexican isolate of Sugarcane mosaic virus and its infectivity in maize and sugarcane plants - F. Espejel; D. Jeffers; J. C. Noa-Carrazana; S. Ruiz-Castro; L. Silva-Rosales (Archives of Virology, 2006)

Interaction of stannous chloride leads to alteration in DNA, triphosphate nucleotides and isolated bases - José C. P. de Mattos; Claudia Lage; Flávio J. S. Dantas; Milton O. Moraes; Ana P. M. Nunes; Roberto J. A. C. Bezerra; Mauro V. Castro Faria; Alvaro C. Leitão; Adriano Caldeira-de-Araujo (Molecular and Cellular Biochemistry, 2005)

Studies on the diversity of arbuscular mycorrhizal fungi and the efficacy of two native isolates in a highly alkaline anthropogenic sediment - R. S. Oliveira; M. Vosátka; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2005)

Isolation in cell culture and detection by PCR‐based technology of IPNV‐like virus from leucocytes of carrier turbot, Scophthalmus maximus (L.) - J M Cutrín; C López‐Vázquez; J G Olveira; S Castro; C P Dopazo; I Bandín (Journal of Fish Diseases, 2005)
A non‐destructive procedure was utilized to determine the infectious pancreatic necrosis virus (IPNV) status of an apparently healthy turbot broodstock. Blood samples were used to detect IPNV by reverse transcriptase‐polymerase chain reaction (RT‐PCR), Southern blot hybridization and nested PCR. In addition, viral isolation from turbot leucocytes was performed. Around 22% of the fish were IPNV positive by RT‐PCR, and this increased to close to 60% when nested PCR was performed. The present report supports the use of blood samples for the detection of IPNV‐like viruses in brood fish. In addition, we demonstrate that it is possible to isolate the virus from the blood of carrier fish, as a non‐lethal detection method, although it is much less sensitive than RT‐PCR and nested PCR as a IPNV‐like strain was isolated from only five of the 15 blood sample pools assayed. The viral isolate was identified as type Dry Mills (genogroup I) by means of restriction fragment length polymorphisms and DNA sequencing.

Phytostructural characterization of several vegetation types in northern Portugal. II. The structural expressivity and the resistance of the vegetation - A. Crespí; S. Bernardos; A. Castro; C. P. Fernandes; F. Amich (Plant Biosystems, 2005)

Persistent Organochlorine Pesticide Levels in Breast Adipose Tissue in Women with Malignant and Benign Breast Tumors - S. M. Waliszewski; M. T. Bermudez; R. M. Infanzon; C. S. Silva; O. Carvajal; P. Trujillo; S. Gomez Arroyo; R. Villalobos Pietrini; V. A. Saldanña; G. Melo; S. Esquivel; F. Castro; et al. (Bulletin of Environmental Contamination and Toxicology, 2005)

Use of natural marks on population estimates of the nurse shark,Ginglymostoma cirratum, at Atol das Rocas Biological Reserve, Brazil - Andrey L. F. Castro; Ricardo S. Rosa (Environmental Biology of Fishes, 2005)

High prevalence of hepatitis B virus infection among tuberculosis patients with and without HIV in Rio de Janeiro, Brazil - C. A. Blal; S. R. L. Passos; C. Horn; I. Georg; M. G. Bonecini-Almeida; V. C. Rolla; L. Castro (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

El Niño–southern oscillation events and associated European winter precipitation anomalies - D. Pozo‐Vázquez; S. R. Gámiz‐Fortis; J. Tovar‐Pescador; M. J. Esteban‐Parra; Y. Castro‐Díez (International Journal of Climatology, 2005)
The winter precipitation anomalies in the European area have been analysed over the period 1900–98 based on the El Niño–Southern oscillation (ENSO) state. A set of winter and autumn ENSO events is first selected using the Sea‐Surface temperature (SST) data of the Niño 3 region, with the constraint that the ENSO event is well developed during the winter and autumn of study, and that it is an extreme event. Cold and warm ENSO events and periods that can be regarded as normal are selected. For the selected winter ENSO events and for the winter following the selected autumn ENSO events, composites of European winter precipitation anomalies have been obtained and compared with each other. A study of the consistency among events of the relationship between ENSO and precipitation anomalies was also carried out. The analysis of the winter precipitation anomalies based on the selected winter ENSO events shows the existence, for the European area and during La Niña events, of a statistically significant precipitation anomaly pattern with positive precipitation anomalies north of the British Isles and in the Scandinavian area and negative anomalies in southern Europe, resembling the precipitation pattern associated with the positive phase of the North Atlantic oscillation (NAO). Particularly, for the southwestern area of the Iberian Peninsula, the negative anomaly reaches 20% of the winter average precipitation. The consistency analysis shows that this precipitation pattern is not the result of a few major events, but rather that it is stable and qualitatively similar to that found during the positive phase of the NAO. A non‐linear response to ENSO is found in the eastern Mediterranean area: negative precipitation anomalies are found, having similar amplitude anomalies, both during El Niño and La Niña events. The analysis of the precipitation anomalies for the winter following the selected autumn ENSO events shows very similar results to those found for the previous analysis, thus suggesting the existence of a potential source of seasonal forecasting of European precipitation. An analysis of the sensitivity of the precipitation anomalies to the strength of the ENSO events shows that, when the strength of the ENSO increases, the magnitude of the rainfall anomalies does not change, but the area influenced and the coherence between events do increase slightly. Copyright © 2005 Royal Meteorological Society

Development of European Educational Strategies: Design of Veterinarian Profiles Identified by Market needs for the Year 2020 - P. De Castro; S. Zucconi (Veterinary Research Communications, 2004)

High CO2 Levels in Boreholes at El Teide Volcano Complex (Tenerife, Canary Islands): Implications for Volcanic Activity Monitoring - V. Soler; J. A. Castro-Almazán; R. T. Viñas; A. Eff-Darwich; S. Sánchez-Moral; C. Hillaire-Marcel; I. Farrujia; J. Coello; J. de la Nuez; M. C. Martín; M. L. Quesada; E. Santana (Pure and Applied Geophysics, 2004)

Multiple Paternity in Norway Lobster ( Nephrops norvegicus L.) Assessed with Microsatellite Markers - M. L. Cancela; R. Streiff; S. Mira; M. Castro (Marine Biotechnology, 2004)

Input-Output Budgets of Inorganic Nitrogen for 24 Forest Watersheds in the Northeastern United States: A Review - John L. Campbell; James W. Hornbeck; Myron J. Mitchell; Mary Beth Adams; Mark S. Castro; Charles T. Driscoll; Jeffrey S. Kahl; James N. Kochenderfer; Gene E. Likens; James A. Lynch; Peter S. Murdoch; Sarah J. Nelson; et al. (Water, Air, & Soil Pollution, 2004)

Accumulation, assembly, and digestibility of amarantin expressed in transgenic tropical maize - Q. Rascón-Cruz; S. Sinagawa-García; J. A. Osuna-Castro; N. Bohorova; O. Paredes-López (Theoretical and Applied Genetics, 2004)

Gynogenesis Assessment Using Microsatellite Genetic Markers in Turbot ( Scophthalmus maximus ) - J. Castro; C. Bouza; L. Snchez; R. M. Cal; F. Piferrer; P. Martnez (Marine Biotechnology, 2003)

Role of nitric oxide in thermoregulation during septic shock: involvement of vasopressin - Alexandre Giusti-Paiva; Luiz G. S. Branco; Margareth de Castro; José Antunes-Rodrigues; Evelin C. Carnio (Pflügers Archiv - European Journal of Physiology, 2003)

Assortative Mating and Fertility in two Drosophila subobscura Strains with different Mitochondrial DNA Haplotypes - José A. Castro; Pedro Oliver; John S. Christie; Antònia Picornell; Misericòrdia Ramon; Andrés Moya (Genetica, 2003)

Mapping and pyramiding of qualitative and quantitative resistance to stripe rust in barley - A. J. Castro; F. Capettini; A. E. Corey; T. Filichkina; P. M. Hayes; A. Kleinhofs; D. Kudrna; K. Richardson; S. Sandoval-Islas; C. Rossi; H. Vivar (Theoretical and Applied Genetics, 2003)

Alternative reproduction pathway inAspergillus nidulans - F. Baptista; M. F. P. S. Machado; M. A. A. Castro-Prado (Folia Microbiologica, 2003)

Detection of an Intracellular Protease Inhibitor in Archaea - Mara I. Gimnez; Jorge J. Snchez; Rosana E. De Castro (Current Microbiology, 2003)

Recombinagenic effect of cryptolepine inuvsH +//uvsH + anduvsH//uvsH diploid strains ofAspergillus nidulans - S. J. R. Chiuchetta; M. A. A. Castro-Prado (Folia Microbiologica, 2002)

Total Mercury Concentrations in Lakes and Fish of Western Maryland, USA - M. S. Castro; E. N. McLaughlin; S. L. Davis; R. P. Morgan, II (Archives of Environmental Contamination and Toxicology, 2002)

Molecular relationships in Genista L. Sect. Spartocarpus Spach (Fabaceae) - O. De Castro; S. Cozzolino; S. L. Jury; P. Caputo (Plant Systematics and Evolution, 2002)

Differential Esterase Expression in Developmental Mutants of Aspergillus nidulans - Maria de Fátima P. S. Machado; Marialba A. A. de Castro-Prado (Biochemical Genetics, 2001)

Hydrogenated fish fat for grazing dairy cows in summer - M. R. Gallardo; S. E. Valtorta; P. E. Leva; H. C. Castro; J. A. Maiztegui (International Journal of Biometeorology, 2001)

A study of NAO variability and its possible non-linear influences on European surface temperature - D. Pozo-Vázquez; M. J. Esteban-Parra; F. S. Rodrigo; Y. Castro-Díez (Climate Dynamics, 2001)

Identification of wheat chromosomes involved with different types of resistance against greenbug (Schizaphis graminum, Rond.) and the Russian wheat aphid (Diuraphis noxia, Mordvilko) - A.M. Castro; S. Ramos; A. Vasicek; A. Worland; D. Giménez; A.A. Clúa; E. Suárez (Euphytica, 2001)

Combined Effects of Food Concentration and the Herbicide 2,4-Dichlorophenoxyacetic Acid on the Population Dynamics of Brachionus patulus (Rotifera) - S. S. S. Sarma; T. Ramíez-Pérez; S. Nandini; I. Peñalosa-Castro (Ecotoxicology, 2001)

Expression of the Major Heat Shock Proteins DnaK and GroEL in Streptococcus pyogenes : A Comparison to Enterococcus faecalis and Staphylococcus aureus - Marinella S. Laport; Angela C.D. de Castro; Adriana Villardo; Jose Abelardo C. Lemos; Maria do Carmo F. Bastos; Marcia Giambiagi-deMarval (Current Microbiology, 2001)

Biological responses of microflora to treatment with CA and/or fumigation - J. L. Zettler; S. Navarro; Maria Fernanda Penteado M. de Castro; J. O. do Vale; Neura Bragnolo; M. F. F. Leitao; Eliane Salvadego Anichiareo; K. A. Mills (Phytoparasitica, 2001)

Lowest effective and optimum poultry manure dose for reclaiming burnt soils: pot experiments - A. Castro; S. J. González-Prieto; M. C. Villar; T. Carballas (Biology and Fertility of Soils, 2000)

Nosocomial Spread of Hepatitis B Virus in Two Hemodialysis Units, Investigated by Restriction Fragment Length Polymorphism Analysis - L. De Castro; N. M. Araujo; R. R. Sabino; F. Alvarenga; C. F. T. Yoshida; S. A. Gomes (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Behavioral and demographic changes following the loss of the breeding female in cooperatively breeding marmosets - C. Lazaro-Perea; C. S. S. Castro; R. Harrison; A. Araujo; M. F. Arruda; C. T. Snowdon (Behavioral Ecology and Sociobiology, 2000)

Coat protein sequence comparisons of three Mexican isolates of papaya ringspot virus with other geographical isolates reveal a close relationship to American and Australian isolates - L. Silva-Rosales; N. Becerra-Leor; S. Ruiz-Castro; D. Téliz-Ortiz; J. C. Noa-Carrazana (Archives of Virology, 2000)

A high incidence of Shigella -induced arthritis in a primate species: major histocompatibility complex class I molecules associated with resistance and susceptiblity, and their relationship to HLA-B27 - J. A. Urvater; S. N. McAdam; J. H. Loehrke; T. M. Allen; J. L. Moran; T. J. Rowell; S. Rojo; J.A. López de Castro; J. D. Taurog; D. I. Watkins (Immunogenetics, 2000)

Input–Output Budgets of Major Ions for a Forested Watershed in Western Maryland - Mark S. Castro; Raymond P. Morgan (Water, Air, & Soil Pollution, 2000)

Secretory cavities and pellucid dots in leaflets ofLonchocarpus (Leguminosae, Papilionoideae, Millettieae) - S. de P. Teixeira; M. de M. Castro; A. M. G. de A. Tozzi (Plant Systematics and Evolution, 2000)

Obtainment of a carbon-13-, nitrogen-15-labelled burnt soil - S. J. González-Prieto; A. Cabaneiro; A. Castro; M. C. Villar; A. Martín; T. Carballas (Biology and Fertility of Soils, 1999)

Host-specific transcription of nucleopolyhedrovirus gene homologues in productive and abortive Anticarsia gemmatalis MNPV infections - M. E. B. Castro; M. L. Souza; S. L. Bilimoria (Archives of Virology, 1999)

On the Use of the Jesuit Order Private Correspondence Records in Climate Reconstructions: A Case Study from Castille (Spain) for 1634–1648 A.D. - F. S. Rodrigo; M. J. Esteban-Parra; Y. Castro-Diez (Climatic Change, 1998)

Spatial and temporal patterns of precipitation in Spain for the period 1880–1992 - M. J. Esteban-Parra; F. S. Rodrigo; Y. Castro-Diez (International Journal of Climatology, 1998)

Biochemical alterations in Bradyrhizobium sp USDA 3187 induced by the fungicide Mancozeb - A. Fabra; J. Angelini; A. Donolo; M. Permigiani; S. Castro (Antonie van Leeuwenhoek, 1998)

Interaction of the fungicide mancozeb and Rhizobium sp. in pure culture and under field conditions - S. Castro; Marta Vinocur; Marcela Permigiani; Carlos Halle; Tania Taurian; Adriana Fabra (Biology and Fertility of Soils, 1997)

Agricultural development vs biodiversity conservation: the Mediterranean semiarid vegetation in El Ejido (Almera, southeastern Spain) - J. F. Mota; J. Peas; H. Castro; J. Cabello; J. S. Guirado (Biodiversity and Conservation, 1996)

Late preventive effects against carbon tetrachloride-induced liver necrosis of the calcium chelating agent calcion - E. C. de Ferreyra; M. C. Villarruel; A. S. Bernacchi; G. Fernández; O. M. de Fenos; J. A. Castro (Archives of Toxicology, 1989)

l-Alanine as an end product of glycolysis inSaccharomyces cerevisiae growing under different hypoxic conditions - E. Chico; J. S. Olavarría; I. Núñez de Castro (Antonie van Leeuwenhoek, 1978)

Developmental genetics of the alcohol dehydrogenase locus of the Japanese quail - S. Ohno; L. Christian; C. Stenius; E. Castro-Sierra; J. Muramoto (Biochemical Genetics, 1969)